Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

UFMylation in lipid metabolism disorders-associated diseases - Zi-Ping Ning; Ya-Ling Tang; Lin Cao; Hong-Feng Gu (Molecular Biology Reports, 2026)

Impacts of different ozone treatments on the growth and soil bacterial community of Pinellia ternata - Yucheng Qiu; Xi Feng; Xiangrui Fu; Xiaoying Shang; Yunsheng Zhao; Donglai Ma; Huiyong Fang; Xian Gu (Brazilian Journal of Microbiology, 2026)

UVR8-mediated regulation of anthocyanin metabolism in plants: molecular mechanisms, signaling networks, and adaptive functions - Yu Chu; Hui Ma; Jiaxin Cai; Rihan Feng; Yuanpeng Gu; Ziyi Fang; Yunjiang Liang; Yang Li (Plant Science, 2026)

Numerical investigation on collapse-induced impact among reinforced concrete frame structures based on DEM - Qian-Qian Yu; Chen-Chen Lu; Xiang-Lin Gu; Tian Zhou; Feng Lin (Engineering Structures, 2026)

Eutrophication mitigation and climate warming coincide with divergent shifts in harmful algal bloom dynamics in Shandong coastal waters - Nina Ma; Chunli Liu; Zhenzhou Feng; Weihua Feng; Zhibing Jiang; Zhifu Wang; Fangqin Zheng; Jian Qian; Weifang Gu (Water Research, 2026)

Polyphase tectonics and gold mineralization in the Liziyuan district, West Qinling orogen, China: Insights from structural analysis, quartz EBSD, and trace element geochemistry - Ruilin Wang; Huan Li; Mohamed Faisal; Bo Feng; Shangyi Gu; Yuanlin Chen (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

An integrated source–exposure–transport framework for risk-oriented management of mining-impacted groundwater contamination - Chang Liu; Yimin Sang; Fan Feng; Tingyu Yang; Qingyue Wang; Yanwei Wang; Heming Wang; Fujun Ma; Qingbao Gu (Journal of Environmental Chemical Engineering, 2026)

Hydrometallurgical recovery of spent Li-ion batteries driven by thermal reduction: Opportunities, challenges, and prospects - Hui Liu; Jingkun Han; Yuheng Feng; Chongqing Nong; Jing Gu; Haoran Yuan (Journal of Environmental Chemical Engineering, 2026)

Comparative metabolomics reveals distinct metabolic profiles and in vitro activities of fermented noni juice from Samoa and China's Hainan - Qianjin Ni; Meimei Nie; Linlin Han; Mingfei Gu; Lingming Xiong; Yayuan Xu; Lei Feng; Liying Niu; Runqiang Yang; Dajing Li; Zhuqing Dai (Food Chemistry, 2026)

Structural regulation of intergrown twin ZSM-5 zeolites for shape-selective toluene-methanol co-conversion to produce p-xylene and light olefins - Xiaolin Zhu; Bing Feng; Zhengchao Wang; Mengqi Wang; Tianhua Sun; Guowei Wang; Bingxu Chen; Longqin Gu; Chunyi Li; Chaohe Yang; Xiang Feng (Chemical Engineering Journal, 2026)

Ginkgo Biloba Leaves Biochar Doped with K/Mg Promotes Peroxymonosulfate Activation for Tetracycline Removal in Aqueous Media Via Singlet Oxygen Generation - Shuaishuai Zhang; Yulong Feng; Xinan Sun; Meizhu Hou; Peng Sun; Zhenchao Gu; Lianke Zhang (Water, Air, & Soil Pollution, 2026)

Large Stokes shift red-emissive CDs-based ternary complexes for ratiometric/visual detection of triethylamine - Guoliang Liu; Shaofei Wang; Zhendi Yu; Xinyu Li; Miao Gu; Da-Qian Feng (Analytica Chimica Acta, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Multimodal deep fusion of Low-Field NMR and proton Density-Weighted imaging for interpretable detection of Saline-Alkali stress in wheat - Ying Gu; Guoqing Feng; Ya’nan Zhou; Han Zhang; Cheng Wang; Liping Chen; Bin Luo (Computers and Electronics in Agriculture, 2026)

Retraction notice to “Efficient adsorption and degradation of Di-(2-ethylhexyl) phthalate (DEHP) by Nanomaterial-modified biochar: insights into microbial communities, functional genes, and metabolic pathways” [Water Research 289 (2026) 124986] - Weijian Zhang; Jingyi Feng; Xueyan Bai; Lu Jiang; Lei Gao; Siyu Gu (Water Research, 2026)

Algal blooms drive plasmid-mediated ARG conjugation in eutrophic lakes: Mechanistic insights from field mobilome to molecular regulation - Chao-Nan Wang; Er-Xue Gu; Xing-Yan Xue; Cun-Lu Li; Dong-Feng Liu; Fu-Liu Xu (Water Research, 2026)

Impact of tannic acid on starch structure, properties, and applications: Comprehensive review - Feng Jiang; Mengyuan Qin; Yan Hong; Lingjin Li; Li Cheng; Zhengbiao Gu (Trends in Food Science & Technology, 2026)

Urban ecological environment quality and brain aging: epidemiological evidence from a middle-aged and elderly population-based cohort - Zihuan Shao; Shenghao Yuan; Jiawei Gu; Yujia Bao; Jingyun Feng; Hongxuan Wu; Wenqi Qian; Dayi Lai; Tianlang Tong; Chen Shen; Xiaobei Deng; Jinjun Ran (Sustainable Cities and Society, 2026)

Long-day photoperiod promotes growth of pea (Pisum sativum L.) via auxin biosynthesis and polar transport - Luping Gu; Tao Wan; Wenjie Chen; Guiyu Zhou; Huiyu Zhang; Chang Tan; Lars H. Wegner; Sergey Shabala; Xuewen Li; Jiayou Liu; Yingming Feng; Renfang Shen; et al. (Plant Science, 2026)

Multifunctional drug-loaded cement for microenvironment remodeling to promote osteoporotic bone regeneration in Kümmell's disease - Dongping Wang; Yihan Gao; Shuling Gu; Ziqi Feng; Zhizhao Li; Guanxiong Wang; Chang Liu; Yihao Zhu; Yang Shao; Qingtao Li; Yongxian Li; Xiaodong Cao; et al. (Chemical Engineering Journal, 2026)

Regulation mechanisms of substrate macronutrient balance on energy allocation and metabolic homeostasis in black soldier fly larvae - Feng Luo; Tao Xu; Kuang Sheng; Jun Ni; Hengfeng Miao; Kunlun Yang; Peng Gu; Xueli Ren; Zengshuai Zhang (Bioresource Technology Reports, 2026)

Protein-DNA Binding Sites Prediction via Integrating Pretrained Large Language Models and Contrastive Learning - Zhen Feng; Hui Yu; Xiaoya Guan; Zhenyu Yue; Lichuan Gu; Ke Li; Xiaobo Zhou (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Distribution of soil organic carbon in root zones at different distances from the maize basal stem axis and its response to organic materials - Kaixuan Wang; Sen Dou; Baozhao Feng; Boyan Zhang; Yuhan Xia; Dilimulati Yalihong; Yue Gu; Jingmin Yang (Journal of Soils and Sediments, 2026)

Simulating Martian Atmospheric Processes and Local Dust Events with a Global Variable-Resolution Model (iAMAS-Mars) - Yongxuan Zhao; Chun Zhao; Lulu Li; Li Dong; Jiawang Feng; Jun Gu; Gudongze Li; Chao Wang; Qi Chen (Advances in Atmospheric Sciences, 2026)

Monoterpenoid indole alkaloids from the aerial parts of Tabernaemontana divaricata (L.) R. Br. ex Roem. & Schult. and their anti-inflammatory activity and cytotoxicity on acute leukaemia cells - Wan-Qi Yang; Cai-Xia Wen; Er-Gu Chen; Ren-Feng Ye; Min Jiang; Gui-Guang Cheng; Ya-Ping Liu (Natural Product Research, 2026)

Pore size-matched adsorption of organic pollutants and its pilot application in advanced wastewater treatment - Baogui Wang; Yingxu Liu; Bowen Hou; Qiang Li; Di Mao; Xiangnan Li; Shanshan Feng; Yunfei Tan; Dongsong Zhao; Hongwei Yu; Zhenao Gu; Chengzhi Hu (Water Research, 2026)

Microplastics threaten agroecosystem multifunctionality: A global systematic review with national-scale evidence from China - Zhongke Qu; Zexin Meng; Jie Han; Fulai Yan; Feng Wang; Fangyan Zhang; Yiping Wu; Huayang Zhen; Zhaolin Gu (Journal of Environmental Management, 2026)

Data-Driven Co-management: synergizing soil quality and crop productivity for sustainable agriculture - Xiaowen Gu; Pengqi Liu; Kang Wang; Qingwen Shi; Yuxiao Wu; Junwei Sun; Wen-Feng Cong; Hao Ying (Journal of Cleaner Production, 2026)

New development on cultural heritage microbiology in China - Xiaobo Liu; Fasi Wu; Youzhi Feng; Ji-Dong Gu (International Biodeterioration & Biodegradation, 2026)

Oak fossils reveal a cooler climate in northern Thailand during the late Oligocene–Early Miocene - Napussawan Thongsangtum; Jian Huang; Yupa Thasod; Yi-Qing Gu; Nguyen Ba Hung; Shu-Feng Li; Tao Su (Geobios, 2026)

Topical maltotetraose alleviates chronic pruritus by restoring skin barrier function and cutaneous homeostasis in C57BL/6J mice - Fuqiang Gao; Rong Feng; Haocun Kong; Yixiong Tian; Danyang Li; Caiming Li; Xiaofeng Ban; Zhengbiao Gu; Zhaofeng Li (Food Research International, 2026)

Egg yolk phospholipid peptides as dual-functional nanocarriers for curcumin: Enhanced hypolipidemic effects and mechanism - Ruyi Zhang; Wenhui Feng; Lili Jiang; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Yi Wang; Junhua Li (Food Research International, 2026)

Single-nucleus RNA sequencing reveals cellular heterogeneity in Holstein dairy cows with different milk production volumes - Chuanchuan Wang; Yafei Chen; Xiaofang Feng; Chao Yan; Yun Ma; Xiaohua Tian; Xiaoyun Ji; Lin Xue; Hua Wang; Juan Zhang; Yaling Gu (Food Bioscience, 2026)

Food-relevant exposure to bisphenol A diglycidyl ether induces hepatotoxicity in zebrafish through a putative PPARα-related mechanism - Dandan Gu; Qianyi Deng; Lei Ai; Zanhui Chen; Guanghua Mao; Yao Chen; Ting Zhao; Yangyang Ding; Weiwei Feng; Xiangyang Wu (Food Bioscience, 2026)

Chemical constituents from Belamcanda chinensis (Linnaeus) Redouté and their chemotaxonomic significance - Guangju Gu; Yunhua Qianshi; Jun Jin; Linlan Tao; Feng Zhang; Dahong Li; Xiaojiang Hao; Yanan Li; Chunmao Yuan (Biochemical Systematics and Ecology, 2026)

Contrasting Photochemistry and Ozone Pollution at Coastal and Marine Sites in the Pearl River Estuary, South China - Lirong Hui; Guizhen Fang; Yi Chen; Hao Sun; Xin Feng; Yang Xu; Jia Guo; Yao Chen; Penggang Zheng; Dasa Gu; Yanli Zhang; Yee-Jun Tham; et al. (Atmospheric Environment, 2026)

A pentose bisphosphate pathway of nucleotide degradation in Promethearchaeum syntrophicum - Li Liu; Chengxiang Gu; Xiaoyuan Feng; Meng Li (Science China Life Sciences, 2026)

Synergistic foliar application of zinc and manganese reduces Cd accumulation in rice by enhancing leaf sequestration and modulating Cd transporter gene expression - Chang Li; Hang Zhou; Xia Zhou; Peng Zeng; Lin Song; Lan-Xin Ma; Jiao-Feng Gu (Plant and Soil, 2026)

Exogenous phytohormones as protective agents against high light-induced bleaching in Betaphycus gelatinae - Zexu Liu; Haolong Zheng; Xiangyu Wu; Shouguo Yang; Han Yang; Yifang Zhao; Yixuan Xing; Xianming Tang; Zhifeng Gu; Yaohua Shi; Feng Yu (Journal of Applied Phycology, 2026)

Molecular identification and functional characterization of glucose‐dependent insulinotropic peptide ( GIP ) and its receptor ( GIPR ) in Micropterus salmoides - Mingyue Yin; Shihui Guo; Jianing Gu; Ying Zhang; Lili Yang; Yanmin Zhang; Xindang Zhang; Xulu Chang; Shikun Feng; Mohammed A. E. Naiel; Guokun Yang; Xiaolin Meng (Journal of Fish Biology, 2026)
As the cheapest feed ingredient, carbohydrates exert a protein‐sparing effect. However, excessive carbohydrate intake can induce hepatic metabolic disorders and lead to metabolic diseases in fish. The GIP/GIPR axis plays a vital role in regulating lipid metabolism and glucose uptake. To evaluate the functions of GIP and GIPR in largemouth bass, we cloned their cDNA sequences. We analysed the tissue‐specific expression of both genes and assessed the role of GIP in regulating glucose and lipid metabolism using hepatocyte studies and GIP interference assays. The largemouth bass gip gene (318 bp) encodes a protein of 105 amino acids, whereas the gipr gene (1614 bp) encodes a protein of 537 amino acids. Tissue distribution analysis revealed high expression of gip mRNA in the stomach. Additionally, gipr mRNA was highly expressed in the brain, foregut, midgut and hindgut. Both high‐carbohydrate and high‐fat intake in largemouth bass resulted in higher gip mRNA in the stomach and lower gipr mRNA expression in the foregut. Primary hepatocyte experiments showed that GIP treatment increased the expression of g6pase , acc1 and fas and decreased the expression of gk , pfk , hsl and lpl . Intraperitoneal injection of GIP small interfering RNA (siRNA) demonstrated that inhibiting GIP expression significantly reduced serum glucose and triglyceride levels. It also decreased the hepatic expression of g6pase , fbp1 , pygl , acc1 , fas and lpl , while increasing the expression of gys2 and hsl . These results suggest that GIP and GIPR regulate glucose and lipid metabolism in largemouth bass.

Arbuscular mycorrhizal fungi orchestrate belowground microbiomes in plant holobionts - Letian Wang; Lin Zhang; Matthias C. Rillig; Marcel G.A. van der Heijden; Nancy C. Johnson; Gu Feng (Trends in Plant Science, 2026)

Integrating digital PCR and metagenomics to quantify potential soilborne bacterial pathogens in urban ecosystem - Tong Li; Kai Feng; Shang Wang; Xiongfeng Du; Jingjing Li; Songsong Gu; Bo Zhao; Xingsheng Yang; Xi Peng; Qing He; Yingcheng Wang; Danrui Wang; et al. (Journal of Hazardous Materials, 2026)

Road networks facilitate invasive dominance by squeezing native mesopredators into niche margins - Yuhang Li; Zixi Zhao; Xinmiao Chen; Kai Wang; Puyang Zheng; Linyou Gu; Jing Liao; Wenwen Yan; Feng Xu; Yang Liu; Le Yang; Zhongqiu Li (Journal of Environmental Management, 2026)

Decade-long conservation tillage enhances crop productivity by improving soil health in the Northeast China Plain - Weijian Zhang; Jingyi Feng; Xueyan Bai; Lu Jiang; Kunjie Wang; Lei Gao; Siyu Gu (European Journal of Agronomy, 2026)

Seismic performance of steel tube-embedded socket-connected precast bridge piers: Experimental and finite element analysis - Wenqin Deng; Zhaoyang Xu; Chengxiang Miao; Qing Zhang; Xiaonan Feng; Jiancheng Gu; Xinhao He (Engineering Structures, 2026)

Multi-layer fluid-soil-structure interaction SPH modeling of suction bucket foundation installation process - Lin Gan; Hao Wang; Can Yi; Renji Gu; Dianlei Feng (Computers and Geotechnics, 2026)

Covalent organic frameworks membrane with gradient hydrophilic channel for moisture-enabled electric generation - Jun Zhang; Jing-Dong Feng; Ruo-Meng Zhu; Yong Liu; Yu-Ou He; Yu-Ting Que; Shuai Geng; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

Distinct mantle metasomatism in the mantle source of ultrapotassic magma revealed by CaBa isotopes - Yu Chen; Yi-Xiang Chen; Xiao-Feng Gu; Riccardo Avanzinelli; Sandro Conticelli (Chemical Geology, 2026)

Analyzing Muscle Contraction Dynamics Through Continuous Vector Segmentation and Tracking - Wenze Wu; Wenyu Chen; Liuhe Li; Junnan Feng; Zhe Liu; Wei Gu; Lin Gao; Jiankang He; Dichen Li (Annals of Biomedical Engineering, 2026)

Mapping conformational IgE epitopes of arginine kinase in Oratosquilla oratoria - Fei Huan; Ye-Xin Chen; Shi-Qiang Yang; Shuai Gao; Yi Gu; Yi-Yu Chen; Meng Liu; Dong Lai; An-Feng Xiao; Guang-Ming Liu (Marine Life Science & Technology, 2026)

Fenitrothion induces sex-specific glucose metabolism dysregulation in rats by targeting PK/glycolysis in males and IDH3/TCA cycle in females - Yuchao Guo; Dandan Gu; Emmanuel Sunday Okeke; Weiwei Feng; Yao Chen; Guanghua Mao; Liuqing Yang; Ting Zhao; Xiangyang Wu (Archives of Toxicology, 2026)

ALKBH5 promotes the progression of cisplatin-resistant oral squamous cell carcinoma by regulating FOXA1 expression via m6A RNA methylation - Ying Wang; Hui-Xin Yang; Yu-Jia Gu; Mei Tian; Qi-Feng Geng (DARU Journal of Pharmaceutical Sciences, 2026)

HF-STGN: A robust and unified residual-enhanced spatio-temporal graph network for urban meteorological forecasting - Zhongke Qu; Hantao Wu; Feng Wang; Yuan Zhai; Chengwei Li; Zhichao Liu; Nan Yin; Xilian Luo; Zhaolin Gu (Urban Climate, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Ranking-aware continual learning for LiDAR place recognition - Xufei Wang; Gengxuan Tian; Junqiao Zhao; Siyue Tao; Qiwen Gu; Qiankun Yu; Tiantian Feng (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Simulation of acid fracturing using a thermal-hydraulic-mechanical-chemical coupling model integrating fracture initiation and propagation - Haochen Gu; Feng Ma (Geomechanics for Energy and the Environment, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Trajectories of meteorological and air pollution exposures during pregnancy and risk of childhood asthma: A population-based cohort study - Wangyang Gu; Yabin Hu; Qingpeng Li; Huike Feng; Yihao Xue; Linling Xu; Yang Chen; Dan Wang; Guiyan Yang; Shilu Tong; Shijian Liu (Environmental Research, 2026)

A comprehensive bibliometric and systematic review of bio-based construction materials: From supplementary components to cornerstones of sustainable construction - Suwen Gao; Yue Gu; Xintian Wang; Zhuangzhuang Liu; Hao Zhang; Pan Feng; Zhenhua Wei; Linhua Jiang (Energy and Buildings, 2026)

Analysis of the characteristics of rumen microorganisms and their metabolites and plasma metabolites in crossbred beef cattle at different stages - Xiaohua Tian; Yuan Feng; Chuanchuan Wang; Wei Zhao; Lin Xue; Ling Zhu; Xiaoyun Ji; Hua Wang; Yaling Gu; Qiufei Jiang; Juan Zhang (Veterinary Research Communications, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Marine-derived Bacillus tequilensis Bt-RS fermentation broth mitigates salt stress in banana by regulating ion homeostasis, antioxidant defense, and rhizosphere microbiome - Na Deng; Zhengquan Feng; Xiujun Lv; Hanjie Gu; Huiqin Huang; Yonghua Hu (Plant and Soil, 2026)

Deciphering bacterial community composition and function at critical interfaces of plant-arbuscular mycorrhizal fungi-bacterial holobiont - Letian Wang; Jiachao Zhou; Wenjun Wei; Timothy S. George; Gu Feng (Mycorrhiza, 2026)

The protective shade alters prokaryotic community dynamics on sandstone biofilm: Evidence from DNA and RNA-based high-throughput sequencing for heritage conservation - Yong Zhang; Fasi Wu; Zengyang Han; Penghui Guo; Xinghua Ding; Dongpeng He; Xiaobo Liu; Pengfei Hu; Ji-Dong Gu; Huyuan Feng (Applied Soil Ecology, 2026)

Bats as pest-fighting pioneers: Seasonal contributions in South China’s mountainous agroecosystem - Chen Zhang; Hao Gu; Jie Peng; Zheng Cheng; Gang Liu; Jiang Feng; Ying Liu (Agriculture, Ecosystems & Environment, 2026)

Attributing extreme rainfall–runoff dynamics in karst watersheds: An LSTM-based mechanistic modeling and interpretation framework - Zhonghua He; Xiaolin Gu; Feng Qiu; Maoqiang Wang; Mingjin Xu (Advances in Water Resources, 2026)

Promoter-driven enhancement of PHBV synthesis in recombinant Escherichia coli using glucose and propionate as carbon sources - Zhao-song Huang; Cheng-jiao Yu; Zi-miao Yan; Chang-feng Miao; Ling-yi Hou; Peng-fei Gu; Xiang-yu Fan; Qiang Li (Archives of Microbiology, 2026)

N-glycosylation of ERLIN2 promotes hepatocellular carcinoma progression by enhancing CCNB1 stability - Sijie Li; Huanhuan Huang; Jiahui Feng; Qiang Gu; Daquan Sun (Molecular and Cellular Biochemistry, 2026)

Genetic analysis and reproductive interventions in families affected by congenital cataracts: a study of 107 cases - Yun-hao Li; Qi Wang; Yao Peng; Juan Du; Liang Hu; Zhen-hua Tan; Feng Gu; Hao Hu; Qian-jun Zhang; Ge Lin; Guang-xiu Lu; Yue-Qiu Tan; et al. (Journal of Applied Genetics, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Non-destructive detection of moisture dynamics and net ion fluxes in wheat seedlings under saline-alkali stress - Ying Gu; Guoqing Feng; Xiaotong Jin; Hongtu Dong; Quan Gao; Bin Luo; Liping Chen (Biosystems Engineering, 2026)

Efficient and stable membrane fouling control in MFC-MBR system facilitated by conductive membrane electrodes - Xiao Zhu; Yiling Gu; Nan Jiang; Jiaping Wu; Wenxin Chen; Suhao Feng; Ding Huang; Jianmao Yang; Manhong Huang (Journal of Water Process Engineering, 2026)

Text mining and machine learning based health risk prediction for soil polycyclic aromatic hydrocarbons at typical coal-fired industrial sites in china - Lu Han; Hanyuan Gu; Mengfang Chen; Zhanfei He; Yufei Jia; Yudong Feng; Jing Li; Ya Zhu; Ye zou (Journal of Hazardous Materials, 2026)

Charge-regulated thermomagnetic dual-responsive particle aggregation strategy for in-situ detection of Vibrio parahaemolyticus in complex food matrices - Guoyang Chen; Xianhu Wei; Yanmei Feng; Ling Chen; Qihui Gu; Jingjing Zou; Qinghua Ye; Moutong Chen; Liang Xue; Yu Ding; Yuwei Wu; Youxiong Zhang; et al. (Chemical Engineering Journal, 2026)

Starch as a designable platform for oral drug delivery: From structural modulation to application in inflammatory bowel disease - Mengyuan Qin; Feng Jiang; Yan Hong; Lingjin Li; Yongmin Cui; Canran Jin; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Xiaofeng Ban (Carbohydrate Polymers, 2026)

AdaBoost-based satellite detection of summer daytime sea fog and low clouds in ice floe fields of the Arctic - Huiyun Ma; Jiedong Liu; Zengwei Liu; Huihui Feng; Guannan Li; Runxi Gu (Atmospheric Research, 2026)

Maintained quantity, yet degraded suitability of global croplands from 1990 to 2019 - Ziyue Chen; Jianqiang Hu; Chaoqun Zhang; Bingbo Gao; Manchun Li; Jing Yang; Yuxue Wang; Zhaozhong Feng; Baojing Gu (Science Bulletin, 2026)

Discovery of renewable rosin-based 1,2,4-triazole preservative derivatives to control Valsa mali for postharvest disease management of apple fruit - Renle Xu; Xiaoyu Yan; Yuge Hu; Jiuhui Ye; Pengpeng Liu; Yi Zhang; Zida Zhang; Yanqing Gao; Kai Li; Wangxia Wang; Feng Gu; Jian Li (Postharvest Biology and Technology, 2026)

Interpretation of soil deformation characteristics based on in-situ test: A comprehensive review - Zhongkun Ouyang; Hualei Feng; Jun Yang; Xiaoqiang Gu; Jie Shi; Haoxi Li (Ocean Engineering, 2026)

Mineral-associated organic carbon promotes phosphorus accumulation in a long-term fertilized black soil - Naiyu ZHANG; Xiuzhi ZHANG; Yanhua CHEN; Lehlogonolo Abner MATELELE; Ping ZHU; Hongfang LIU; Xianmei ZHANG; Hongjun GAO; Gu FENG; Chang PENG; Shuxiang ZHANG (Pedosphere, 2026)

A novel salt-tolerant purple photosynthetic bacterium Afifella marina TC201-1 for sustainable treatment of saline aquaculture wastewater - Shuai Liang; Kai-Hua Geng; Ding-xian Xu; Ya-Juan Wang; Wei-Yu Du; Yun-Feng Liu; Ya-Nan Lu; Li Wang; Yuan Wang; Jing Gu; Yu-Ting Cong; Lian-Shun Wang; et al. (Journal of Water Process Engineering, 2026)

Synchronous mechanochemical remediation of petroleum-contaminated soil and attapulgite-biochar composite for enhanced Cr(VI) removal from water - Feng Li; Guizhou Gu; Tao Zhang; Jingxin Xiao; Guang Lu; Xiaona Wei; Zheng Li; Changfei Gao (Journal of Cleaner Production, 2026)

Seasonal and process-dependent microbial dynamics drive performance variations in full-scale AAO and modified UNITANK sewage treatment systems - Xiaodan Gu; Feng Wang; Wei Wang; Chuangchuang Gao; Yongwei Ding (Journal of Environmental Chemical Engineering, 2026)

Organic fertilization shapes diazotrophic microbiomes in legume and grass rhizospheres of the Qinghai-Tibet Plateau - Wenli Shen; Chengliang Yan; Huilin Yan; Xueli Zhou; Yingcheng Wang; Xingsheng Yang; Xi Peng; Songsong Gu; Danrui Wang; Kai Feng; Qing He; Shang Wang; et al. (Journal of Environmental Sciences, 2026)

Comparative genomics reveals that Bifidobacterium longum subsp. longum BZG4 alleviates constipation in mice via synergistic xylooligosaccharide - YaXin Gu; Qingqiu Ye; Xin Feng; Junzhu Li; Zichen He; Ming Zhang; Yanling Hao; Zhengyuan Zhai (Food Bioscience, 2026)

Achieving long-life high-voltage Ni-rich cathodes by mitigating lattice and grain-boundary degradation - Jun Chen; Haoji Wang; Junguang Sun; Zebo Gu; Junyong Deng; Guorong Liu; Kun Huang; Siyao Zhang; Hao Feng; Wentao Wang; Hao Chen; Xinya Tang; et al. (Chemical Engineering Journal, 2026)

Thermal runaway behaviour induced by localised aluminium-water reaction at low temperature - Hai-Fang Mao; Jia-Wei Fang; Yi-Kang Deng; Jun Zhang; Yan-Li Zhao; Yao Feng; Min Xiong; Hui-Ting Gu; Xiao Feng; Jian-Hao Fang; Jian-Hua Chen; Chi-Min Shu; et al. (Chemical Engineering Journal, 2026)

Functionalizing 3D DNA crystals by replacing non-framework strands - Xinyu Feng; Li Xu; Yunhan Zhang; Shuheng Wei; Dongbao Yao; Huichao Chen; Yueye Wang; Yujing Wu; Hui Hou; Xiao Cui; Qian Meng; Yue Gu; et al. (Chemical Engineering Journal, 2026)

Unveiling the mechanisms of mechanical stirring for enhanced performance and stability of algal-bacterial flocs treating low C/N synthetic wastewater - Jun-Jie Gu; Bin-Di Mao; Xiao-Xiao Dou; Bin-Xin Zhang; Jia-Wei Xu; Chun-Wan Fu; Bang-Jie Lan; Xin-Jie Zhang; Zhe Xu; Feng Gao (Bioresource Technology, 2026)

Exploring the mechanism of Cucurbitacin B against myocardial ischemia reperfusion injury based on network pharmacology and experimental validation - Xingdong Cheng; Dengyan Zhu; Haizhou Guo; Tianliang Zheng; Bin Wu; Yinliang Sheng; Feng Li; Guangcheng Sun; Song Zhao; Li Ke; Zhuoyu Gu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Distribution and Removal Efficiency of Microplastics in Urban Wastewater Treatment Plants - Ting Cai; Yunfeng Feng; Wenxiu Li; Tao Gu; Kaixiong Huang; Hui Luan; Chu Peng; Zhihe Tang (Bulletin of Environmental Contamination and Toxicology, 2026)

Urban greening mitigates surface warming induced by urbanization in China - Feng Liu; Lunche Wang; Qian Cao; Xihui Gu; Wen Xiao; Xiang Zhang; Jun Gao; Liang Zheng; Zixin Zhang (Agricultural and Forest Meteorology, 2026)

Neural dynamics in tinnitus: differential effects of hearing status on temporal brain activity variability - Haoliang Du; Xiaoyun Qian; Xia Gao; Chenjie Yu; Junguo Wang; Ao Li; Yajun Gu; Xu Feng (Brain Imaging and Behavior, 2026)

The effect of intranasal oxytocin on the neuropsychological substrates of intergroup categorization - Yuhe Wang; Xia Tian; Yuqing Zhou; Zixin Zheng; Xiaoqing Li; Ruida Zhu; Jiaxin Shi; Ruolei Gu; Wenbo Luo; Chunliang Feng (Brain Imaging and Behavior, 2026)

Influence of variable-speed traffic loads on dynamic response and long-term performance of layered pavements on saturated subgrade - Hao Lei; Jian-Gu Qian; Jia-Feng Zhang; Tian-Wen Hu; Xueyu Geng (Transportation Geotechnics, 2026)

Multi-gas monitoring system with enhanced chemical resilience for intelligent grain management - Xuemei Jiang; Yiao Zou; Haojie Li; Ting Guan; Mincheng Bai; Yufeng chen; Lanyue Huang; Hao Feng; Bingzhao Zheng; Zhaolin Gu; Zhongke Qu (Journal of Stored Products Research, 2026)

Coated ferrous sulfate requirement for alleviating hypoxia-induced hepatopancreatic inflammation in sub-adult grass carp (Ctenopharyngodon idella) - Yu-Juan Yang; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Hong-Yun Zhang; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Ying-Gu Kuang; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

Trade-Off Between Microwave Absorption and Mechanical Properties in Core-Shell Zr-Si-C/O Fibrous Aerogels via Phase Transformation - Jinfeng Jiang; Wei Xia; Yu Feng; Weihua Gu; Weiwei Wang; Cao Wu; Wenbo Du; Yong Yang; Hailiang Deng; Yusuke Yamauchi (Chemical Engineering Journal, 2026)

Covalently assembled dual-functional triple-helix lentinan-Au for cervical cancer therapy - Xinjian Lu; Lei Feng; Li Zhang; Fengying Gu; Zuwei Liu; Haibo Xi; Hao Wan (Carbohydrate Polymers, 2026)

Photovoltaic and Aquaculture Environments Consistently Reduce Bacterial Diversity but Divergently Influence Ecological Stability: New Insights from Subsidence Lakes - Xingchen Li; Lei Zhang; Yijie An; Sixu Gu; Feng Xu; Hua Cai (Environmental Management, 2026)

Low-frequency signal inversion and reconstruction via the spatial structure regularization - Wei-wei Gu; Hao Li; Dong-feng Zhao; Peng-fei Wang; Guo-fa Li (Applied Geophysics, 2026)

Sub-chronic exposure to copper nanoparticles and copper sulfate dysregulated the microbiota-gut-liver axis in large yellow croaker, Larimichthys crocea - Xuebin Zheng; Chen Du; Qingtao Miao; Xinming Gao; Binbin Feng; Shenwei Gu; Yang Liu; Li Wang; Jie Ding; Weiliang Shen; Daojun Tang; Yiner Chen; et al. (Marine Pollution Bulletin, 2026)

Strength characteristics of South China coastal soft clay solidified by all solid waste geopolymer materials and its durability under dry/wet cycles of loading - Deluan Feng; Junsheng Zheng; Yanzhe Gu; Shihua Liang (Sustainable Chemistry and Pharmacy, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Immune modulation of Spodoptera litura larvae parasitized by Meteorus pulchricornis and role of the host β-1, 3-glucan-binding protein in parasitism success - Yan Song; Zhi-Xiang Liu; Feng-ming Gu; Ping Li; Wei-Hong Zhou; Jun Wang; Fu-An Wu; Sheng Sheng (Pesticide Biochemistry and Physiology, 2026)

Landscape of environmental pollutant–driven alterations of nucleic acid modifications in hepatoma cells - Tian Feng; Yao-Hua Gu; Qiu-Shuang Hu; Neng-Bin Xie; Shu-Yi Gu; Fang-Yin Gang; Jun Xiong; Bi-Feng Yuan (Journal of Hazardous Materials, 2026)

Integrative metagenomic, metabolomic, and transcriptomic analyses unravel flavor development driven by a defined starter cocktail in cocoa fermentation - Haode Chang; Quanmiao Zhang; Pégnonsienrè Lacina Soro; Wenjing Zhang; Liru Ma; Zhen Feng; Chunhe Gu (Food Research International, 2026)

Micronutrient uptake, partitioning and accumulation in cotton under drip irrigation with mulch in response to phosphorus application in root morphology changes - Yue Ma; Zupeng Ye; Wei Li; Juanhong Wang; Qingxuan Che; Qinghui Wang; Bolang Chen; Gu Feng (Field Crops Research, 2026)

Seismic strengthening of rural masonry buildings via external precast RC subframes: Concept, experiment and application - Xu-Yang Cao; De-Cheng Feng; Dongsheng Gu; Xuliang Qian; Gang Wu (Engineering Structures, 2026)

EFKAN: A KAN-integrated neural operator for efficient magnetotelluric forward modeling - Feng Wang; Hong Qiu; Yingying Huang; Xiaozhe Gu; Renfang Wang; Bo Yang (Computers & Geosciences, 2026)

An agro-bionic approach to co-chelating ultrafine high-entropy metal phosphosulfide nanoparticles for superior Li/K-ion storage - Bing-Jie Feng; Jia-Jie Liu; Xiao-Hui Wu; Zhi-Qiang Gu; Li-Zhong Liu; Li-Bing Yang; Chen Dai; Ke Han; Ming-Jun Zhao; Wei-Jun Jiang; Yi Zhao (Chemical Engineering Journal, 2026)

One-pot synthesis of sandwich-structured ZnO/CsPbX3/ZnO quantum dots with continuously tunable emission for white LEDs - Yi Zhu; Feng Tong; Hui Si; Liji Su; Wenguang Dai; Shu Nie; Zheng Chen; Sheng Huang; Xiuquan Gu (Chemical Engineering Journal, 2026)

Patient-derived 3D bioprinted glioblastoma models with defined physicochemical ECM properties for long-term maintenance and CAR-T therapy evaluation - Xiaohui Li; Fei Zhao; Shengqiang Xu; Chunxia Ji; Zupeng Xu; Zhuoxiao Cao; Yexin Gu; Tianyi Feng; Yanbo Wang; Min Tang; Zhengyu Jiang; Yu Yao; et al. (Chemical Engineering Journal, 2026)

Association between Lipid Accumulation Product and 3-Month Functional Outcome after Ischemic Stroke: the Obesity-Stroke Paradox - Yuan Ren; Ying Zhou; Tian-yu Gu; Yang Cheng; Wei-hua Wu; Xiao-guang Dong; Feng-e Li; Yu-sheng Zhang (Translational Stroke Research, 2026)

Low phosphorus promotes caryophyllene biosynthesis by regulating AaTPS3 in Artemisia argyi - ZhongWen Ma; Ping Lu; Quan Gu; ShiMin Zhang; ZhiYuan Feng; YongPing Cai; Lin Liu (Plant Cell Reports, 2026)

Characterization and production optimization of genistein by the novel endophytic fungus Aspergillus sydowii J11 isolated from pigeon pea (Cajanus cajan) and its antibacterial and antioxidant properties - Bin-bin Li; Xuexia Gao; Min Lv; Wen-juan Ning; Jing-tao Liang; Xin-yu Fan; Xin-ming Lv; Jin-feng Song; Xiao-han Yuan; Cheng-bo Gu (Biotechnology Letters, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Heavy metal pollution in the Jiaodong peninsula: Spatial patterns, elemental mobility, and source-derived ecological impacts - Yang Liu; Xiaoyuan Gu; Jianwei Sun; Haigen Wang; Qingtong Wang; Binghui Feng; Yuhai Chen; Chunhui Ma; Xiangwei Ge; Fengbin Zhu; Shixiong Yang (Marine Pollution Bulletin, 2026)

Recombinant Amuc_1100 Lactococcus lactis regulates metabolism and intestinal health of largemouth bass fed high starch diet - Guokun Yang; Mingyue Yin; Shihui Guo; Boya Yang; Jianing Gu; Ying Zhang; Yanmin Zhang; Xindang Zhang; Xulu Chang; Shikun Feng; Xiaolin Meng (Aquaculture, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Effects of P-AKK on glucose and lipid metabolism and immunity of Micropterus salmoides induced by high starch diet - Guokun Yang; Boya Yang; Tianhao Tan; Mingyue Yin; Jianing Gu; Ying Zhang; Yanmin Zhang; Xindang Zhang; Xulu Chang; Shikun Feng; Xiaolin Meng (Aquaculture, 2026)

Enhanced deep OC-SORT with YOLOv8-seg for robust fry tracking and behavior analysis in aquaculture - Chenli Xi; Meng Cui; Jingtao Yin; Hao Gu; Ting Ouyang; Juan Feng; Lihua Zeng (Aquaculture, 2026)

RETRACTED: Efficient adsorption and degradation of Di-(2-ethylhexyl) phthalate (DEHP) by Nanomaterial-modified biochar: Insights into microbial communities, functional genes, and metabolic pathways - Weijian Zhang; Jingyi Feng; Xueyan Bai; Lu Jiang; Lei Gao; Siyu Gu (Water Research, 2026)

Ceritinib–ibuprofen synergistic hepatotoxicity: Insights from real-world data and liver organoid models - Shiyi Tan; Yun Yang; Li Ma; Xulei Zuo; Jianhua Rao; Yuepu Pu; Feng Cheng; Zhongze Gu; Juan Zhang (Toxicology, 2026)

Difference between static and dynamic small strain shear stiffness of anisotropic granular materials: a DEM study - Hechen Zhou; Xiaoqiang Gu; Xiaomin Liang; Zhihao Zhou; Feng Yu (Soil Dynamics and Earthquake Engineering, 2026)

Oxygen–deficient Fe2O3 bearing pyridine n moieties for spatially decoupled selective H2S oxidation into sulfur at intermediate temperatures - Mingming Guo; Ruiyi Wang; Jia-nan Gu; Yu Feng; Furong Guo; Guangming Zhan; Lijun Wang; Kan Li; Hao Li; Jinping Jia; Tonghua Sun (Journal of Hazardous Materials, 2026)

Fenitrothion exposure induces hyperglycemia in juvenile rats: Impeded glycolysis and promoted gluconeogenesis mediated by acetyl-CoA and oxaloacetate metabolism dysregulation - Yuchao Guo; Dandan Gu; Emmanuel Sunday Okeke; Weiwei Feng; Yao Chen; Guanghua Mao; Liuqing Yang; Ting Zhao; Xiangyang Wu (Journal of Hazardous Materials, 2026)

Seasonal response greenhouse gas accounting model supporting regionalized carbon reduction in wastewater treatment plants - Xuedian Gu; Shih-Hsin Ho; Zixiang He; Yujie Feng; Nanqi Ren (Journal of Cleaner Production, 2026)

Two-stage partial nitritation/Anammox (PN/A) for mainstream wastewater treatment: Achieving high nitrogen removal at elevated loading rates under low-temperature conditions - Xiaodan Gu; Feng Wang; Yongwei Ding; Wenhui Huang; Yong Huang (Journal of Environmental Management, 2026)

Occurrence, distribution, and risk assessment of antibiotics in post-harvest and drained ponds of Sheyang River estuary in Jiangsu Province: Implications for sustainable aquaculture management - Wenqian Shan; Shiya Gu; Wangrong Cui; Xinyun Feng; Xin Song; Jianwei Dong; Hui Xie; Da Li (Journal of Contaminant Hydrology, 2026)

A novel phage lysin Lys19 can serve as potential biocontrol agent against Clostridium perfringens and Streptococcus suis - Yalu Ji; Yuqing Zhou; Yao Fu; Changjiang Sun; Wenyu Han; Xin Feng; Jingmin Gu (International Journal of Food Microbiology, 2026)

Co-pyrolysis of polyolefin separators and active materials from lithium batteries: Thermal conversion performance, interaction behaviors, and products - Hui Liu; Jingkun Han; Jing Gu; Yuheng Feng; Gongqi Liu; Haoran Yuan (Fuel, 2026)

Pre-harvest application of co-assembled Berberine-integrated herbal hydrogel for enhancing strawberry quality and shelf life - Mingping La; Jiamei Le; Hong Gu; Guangyu Zhao; Xiaohong Zhu; Feng Chen; Cui Li (Food Chemistry, 2026)

The role of air pollution, seasonal variations, and sunlight in childhood food allergy: A systematic review and meta-analysis - Yihao Xue; Wangyang Gu; Qingpeng Li; Huike Feng; Linling Xu; Shilu Tong; Shijian Liu (Environmental Research, 2026)

Soil aggregates, carbon and nitrogen content, and water retention across land uses in the Reshui River Catchment - Jing Zheng; Jianxiong Zhang; Bing Ren; Hongyu Lin; Ziyang Li; Feng Gu; Bo Zhu; Barthelemy Harerimana; Minghua Zhou (Ecological Engineering, 2026)

Sodium sulfamate-modified luffa cellulose fiber separator for efficient modulation of Zn2+ transport - Xianghua Kong; Chenguang Feng; Bolin Zhang; Zirui Cao; Hongyu Chen; Haijiao Xie; Jinghuan Zhang; Yuanxiang Gu (Chemical Engineering Journal, 2026)

Pachymic acid suppresses proliferation and invasion in colon cancer by inhibiting glycolysis via PPARγ/ENO1 pathway - Zhiwei Wang; Peiyao Wu; Chuanzhuo Zhang; Ting Zhang; Chunlin Gu; Xiaodong Xie; Xiao Feng; Zhiwei Jiang (Chemico-Biological Interactions, 2026)

Classification of extreme precipitation events in Pakistan and their multiscale interaction mechanisms - Taichen Feng; Hongjia Lei; Chunxuan Zhao; Yu Gu; Xuehua An; Zhiwei Zhu; Qianrong Ma; Guolin Feng (Atmospheric Research, 2026)

Editorial Expression of Concern: Minocycline Protects Against NLRP3 Inflammasome-Induced Inflammation and P53-Associated Apoptosis in Early Brain Injury After Subarachnoid Hemorrhage - Jianru Li; Jingsen Chen; Hangbo Mo; Jingyin Chen; Cong Qian; Feng Yan; Chi Gu; Qiang Hu; Lin Wang; Gao Chen (Molecular Neurobiology, 2026)

Fenitrothion: an up-to-date review of the environmental occurrence, exposure, toxicity, and molecular mechanisms - Yuchao Guo; Dandan Gu; Emmanuel Sunday Okeke; Weiwei Feng; Yao Chen; Guanghua Mao; Liuqing Yang; Ting Zhao; Xiangyang Wu (Environmental Geochemistry and Health, 2026)

Darkfield illumination enhancing artificial-intelligence-assisted digital microfluidics for on-site pathogen detection - Zerui Song; Jingsong Xu; Kunlun Guo; Zhanli Wu; Boyi Feng; Wanxin Tang; Hua Wang; Zhen Gu; Huifeng Wang (Analytica Chimica Acta, 2026)

Innovative design of CXCR4 cyclic peptide via molecular docking for 99mTc-Labeled SPECT/CT imaging in melanoma - Xianrui Yin; Xin Wang; Chengwei Chen; Shenglan Jia; Wanhong Li; Yihong Wu; Xin Chen; Danling Feng; Wai Ping Cecilia Tsang; Zhihao Han; Yueqing Gu (Analytica Chimica Acta, 2026)

TGCDNet: A type-guided change detection network for very high-resolution remote sensing images - Jiangfan Feng; Xinyu Yang; Zhujun Gu (Advances in Space Research, 2026)

EVCBiLNet: Carbon Emission forecasting Model Based on CNN-BiLSTM and Secondary Feature Decomposition - Shuo Feng; Yu Gu; Yanyan Zhao; Lei Chen; Xu Tang; Xinkai Qiao; Danli Wang (Emission Control Science and Technology, 2025)

From plant-based food waste to biochar: A green strategy for agri-food supply chain waste valorization–a comprehensive review - Xuejiao Chen; Yanbo Hao; Wei Lin; Liya Xie; Rui Yang; Wenliang Xiang; Zhilian Gong; Feng Gu; Hongyan Liu; Jie Tang (Trends in Food Science & Technology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

A new bisbenzoquinone with cytotoxicity from Chaetomium trilaterale - Xin-Xin Liang; Lei Li; Jia-Yi Zhang; Xin-Yue Zhang; Yi-Kun Feng; Chen Gu; Si-Cheng Jin; Xiang-Guo Meng (Phytochemistry Letters, 2025)

Evaluation of quinazolin-4(3H)-one derivatives containing the bioactive acetohydrazide group as fungicidal candidates - Wenfei Zhang; Jiacheng Liu; Sifei Qi; Zihan Li; Yiwen Chen; Yufei Gong; Xiangkun Luo; Shuo Wang; Feng Liu; Yu-Cheng Gu; Xuewen Hua (Pesticide Biochemistry and Physiology, 2025)

Multi-objective optimization of a semi-submersible floating wind Platform: Integrating cost, stability, and strength - Siqi Lai; Hongwei Liu; Yajing Gu; Rongfu Li; Long Fang; Yonggang Lin; Souleymane Drabo; Xiangheng Feng (Ocean Engineering, 2025)

Power prediction of offshore wind farms based on a fusion-driven of physical knowledge and operational data - Xinyao Xin; Shangshang Wei; Dachuan Feng; Chang Xu; Xiarong Ying; Mingxuan Gu (Ocean Engineering, 2025)

Impacts of geography, climate, soil properties and vegetation characteristics on soil C:N and N:P stoichiometry across the Qinghai-Tibetan Plateau - Wenlan FENG; Pierre MARIOTTE; Jun GU; Xiaodong SONG; Jinling YANG; Fei YANG; Yuguo ZHAO; Ganlin ZHANG (Pedosphere, 2025)

Thermal decomposition characteristics, products, and thermal transformation mechanisms of fluorine-containing organic components in lithium-ion batteries - Hui Liu; Jingkun Han; Yuheng Feng; Chongqing Nong; Yu Liu; LeiLei Cheng; Jing Gu; Haoran Yuan (Journal of Environmental Chemical Engineering, 2025)

Egg yolk phospholipid peptide-dihydromyricetin nano-composites: Temperature-driven assembly and evaluation of stability and pharmacokinetics - Yingxin Wei; Jinping Zhang; Wenhui Feng; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2025)

From energy drain to resource gain: A high-rate system for synergistic carbon capture and ammonia retention - Ruize Gu; Dongyi Li; Yujie Zhu; Yanling Yu; Wenyong Qin; Weiyan Li; Xinlei Chu; Weihua He; Yujie Feng (Chemical Engineering Journal, 2025)

A hierarchically porous AgNW-TPU composite with “pores-in-pore” architecture for bifunctional flexible sensors and energy harvesters - Rui Tao; Yang Feng; Cong Chang; Chengding Gu; Chuncai Shan; Xu Zhang; Yongyun Mao (Chemical Engineering Journal, 2025)

Phengite controls on thallium elemental and isotopic systematics in subduction-zone fluids - Yunchao Shu; Sune G. Nielsen; Veronique Le Roux; Ryan McKenzie; Jerzy Blusztajn; Chadlin M. Ostrander; Shun Guo; Xiao-Feng Gu; Juan Xu; Chuan-Zhou Liu (Chemical Geology, 2025)

Contact time and dissolved oxygen concentration modulate carbon capture via shifting microbial metabolism preference in high-rate contact stabilization process - Dongyi Li; Ruize Gu; Tongtong Liu; Fangyue Peng; Dandan Liang; Weihua He; Yujie Feng (Bioresource Technology, 2025)

Dissection of B subgenome of Brassica juncea through monosomic addition lines in Brassica napus: phenomic, cytological and genotypic insights - Lingli Yuan; Chunxing Sun; Mingyang Hu; Lang Liu; Feng Yu; Tuo Zeng; Lei Gu; Xuye Du; Zaiyun Li; Hongcheng Wang; Bin Zhu (Theoretical and Applied Genetics, 2025)

Analysis of the dynamic reaction and instability deformation differences of loess slopes with different landforms - Jiapei Gu; Fanchao Meng; Chaoyu Chang; Yunhui Zhao; Feng Qiao; Tao Chen; Hang Jin; Jianfeng Wang (Natural Hazards, 2025)

Nano-sized heterogeneous photocatalyst Fe3O4@V/TiO2-catalyzed synthesis and antimycobacterial evaluation of 2-substituted benzimidazoles - Lijian Bao; Xiaodong Chen; Yanli Li; Guangyuan Zhu; Jingjun Wang; Mingyue Chen; Xingyu Bian; Qiang Gu; Yumin Zhang; Feng Lin (Molecular Diversity, 2025)

FAK mediates mechanical signaling to maintain epithelial homeostasis through YAP/TAZ-TEADs - Yang Peng; Qiuyun Yuan; Shuting Zhou; Jianguo Gan; Zhengzhong Shen; Xiaoqiang Xia; Yuchen Jiang; Qianming Chen; Yao Yuan; Gu He; Qiang Wei; Xiaodong Feng (Histochemistry and Cell Biology, 2025)

Deep learning method for collembola identification using single species and community combinations images - Xiaohao Zhuang; Bin Wang; Zhijing Xie; Zhihong Qiao; Jun Feng; Jocelyn E. Behm; Clément Schneider; Beining Shi; Jiayin Zheng; Yunyi Gu; Yuanyuan Meng; Xin Sun; et al. (Soil Ecology Letters, 2025)

MyD88-induced microglia polarization promotes inflammatory response in ischemic stroke: a single-cell transcriptomic analysis - Huixiao Wang; Zhou Lu; Jiajie Gu; Feng Gao (Neurophysiology, 2025)

Projection of Population Exposure to Compound Extreme Climate Events in the Yangtze River Basin - Xiaojun Wu; Jiakun Liu; Zigeng Niu; Pengcheng Qin; Yang Feng; Xihui Gu; Jie Gong; Rui He (Journal of Earth Science, 2025)

Instant organic carbon addition regulating microbial-mediated P mobilization in calcareous soil: An incubation experiment - Yi Peng; Gu Feng (Applied Soil Ecology, 2025)

Alpha-linolenic acid modulates the biochemical composition and promotes lipid production in green microalga Desmodesmus sp. SZ - Zhenglan Gong; Yongjie Feng; Ximeng He; Hong Gu; Xueling Chen; Jinkun You; Peng Zhao (Algal Research, 2025)

Circ_0000972 Inhibits Hepatocellular Carcinoma Cell Stemness by Targeting miR-96-5p/PFN1 - Jintian Tang; Runjuan Tang; Feng Xue; Peng Gu; Jing Han; Wukui Huang (Biochemical Genetics, 2025)

Arbuscular Mycorrhizal Fungi Drive Soil Multifunctionality and Productivity Enhancement in Leymus Chinensis Grasslands Under Phosphate Fertilizer Condition - Xiaoguo Zhou; Yutong Hu; Junhui Cheng; Jiandong Sheng; Gu Feng (Journal of Soil Science and Plant Nutrition, 2025)

Pollution profiles and human health risk assessment of BPA analogues in seafood from a Chinese coastal city - Yuehong Shen; Haonan Chen; Mengyuan Liang; Liguo Guo; Jie Gu; Lili Shi; Feng Ge; Guixiang Ji (Marine Pollution Bulletin, 2025)

Isotopic evidence of hydrological niche segregation and species coexisting mechanism of desert shrubs Reaumuria songarica and Nitraria sphaerocarpa - Huli Gu; Hai Zhou; Guopeng Chen; Heng Ren; Bing Liu; Xibin Ji; Xiangyan Feng; Qiyue Yang; Mingyan Fan; Wenzhi Zhao (Journal of Hydrology, 2025)

Online characterization of particle size distribution and molecular structure of cigarette smoke aerosols and their exposure risk assessment - Feng Zhao; Jian Wang; Zhen Lei; Zuoying Wen; Jia Wang; Zhandong Wang; Christa Fittschen; Xiaoxiao Lin; Xuejun Gu; Weijun Zhang; Xiaofeng Tang (Journal of Hazardous Materials, 2025)

Thermal dynamics and economic parametric analysis of repurposed abandoned wells: Field evidence from full-well section temperature monitor - Feng Gu; Youwu Li; Yue Zhang; Ying Gao; Jingyao Sun; Peng Yang; Anran Wang (Geothermics, 2025)

Morphological design of telescopic scissor structures with Bi -objective spatial forms - Qiuyue Zhong; Qian Zhang; Yeqing Gu; Wenwen Jia; Jian Feng; Jianguo Cai (Engineering Structures, 2025)

A dynamic prediction model for maximum lateral displacement of foundation pit enclosure structure using multi-source fusion method - He Wei Kuang; Zhi Yong Ai; Gan Lin Gu; Hong Wei Huang; Zeng Zhi Qian; Da Xing Zhou; Yu Xin Zhai; Hai Feng Guo (Computers and Geotechnics, 2025)

Multidimensional electrode engineering for high-performance vanadium redox flow batteries: Bridging atomic-scale design to macroscopic durability - Yang Su; KeKe Pan; Tiantian Gu; Banghua Peng; Gang Wang; Feng Yu (Chemical Engineering Journal, 2025)

S-doped VO2 induced oxygen vacancies for achieving high performance aqueous zinc ion batteries - Youye Dai; Di Li; Xianghua Kong; Chenguang Feng; Yuanxiang Gu (Chemical Engineering Journal, 2025)

Fabrication of copper(II)-doped nanocarriers with pathogen-responsive properties for enhanced fungicidal activity - Yahui Yang; Yonghui Zhang; Yingjie Liu; Lifang Wang; Wenlong Feng; Xiufang Wang; Guangwei Ren; Pengjun Xu; Yong Gu; Chenyu Su (Chemical Engineering Journal, 2025)

Genome and transcriptome analysis provide insights into the genetics and breeding of Salix suchowensis growth traits - Wei Liu; Shaobo Gu; Mingjia Zhu; Yu Han; Xiaogang Dai; Huaitong Wu; Tongming Yin; Linjie Guo; Landi Feng; Yanjun Zan; Jianquan Liu (New Forests, 2025)

Compound drought-heatwaves in China: driving factors and risks - Anlan Feng; Qiang Zhang; Xihui Gu; Vijay P. Singh; Lei Hu; Yixin Sun; Jiaqi Zhao (Natural Hazards, 2025)

Climate-mediated land use effects on soil organic carbon storage in karst ecosystems - Haiyang Guan; Yunxing Bai; Yunchao Zhou; Fenghua Tang; Jian Feng; Mei Fan; Zaike Gu; Li Qin; Tao Song; Jiaojiao Du (Journal of Soils and Sediments, 2025)

Identifying the optimum irrigation strategies to maximize canola yield and profitability under climate change in Guanzhong Plain, China - Qaisar Saddique; De Li Liu; Ali Ajaz; Bin Wang; Xiaobo Gu; Muhammad Adnan; Puyu Feng; Yunfei Wang; Yufeng Zou; Huanjie Cai (Irrigation Science, 2025)
Climate change has a substantial impact on Chinese canola production, introducing a high level of uncertainty regarding future climatic conditions and their potential impact on canola production and gross margins. This study focused on identifying the optimal irrigation strategy to enhance the profitability of canola production in the Guanzhong Plain under future climate change conditions. In this study, we used the calibrated Agricultural Production Systems sIMulator (APSIM)-Canola model with the downscaled daily climate projections from 27 general circulation models (GCMs). These simulations were conducted under two Shared Socio-economic Pathways scenarios (SSP245 and SSP585) to assess the impact of climate change on canola phenology, rainfed and irrigated crop yield. We also conducted a gross margin analysis to assess the profitability dynamics of supplying irrigation to rainfed canola crop. An increase in rainfed canola yield was observed for all simulation periods, with an average increase of 11%, 15%, and 17% for the 2030s, 2060s, and 2090s, respectively. Supplementary irrigation using a threshold of 10–60% of plant available water capacity (PAWC) was found to be effective. Overall, it led to a 28% increase in yield for rainfed and an 85% improvement in gross margin. Beyond the threshold of 60% PAWC, additional irrigation did not result in statistically significant increases in yield and gross margin. We identified the optimal amount of irrigation for achieving maximum water productivity (WP) ranges from 85 to 150 millimeters. By avoiding irrigation when the soil’s plant available water capacity (PAWC) is over 60%, up to 44% of water can be saved. These findings could be useful for policymakers and farmers in planning for sustainable and enhanced canola production in the region.

Agroecosystem services and disservices in Beijing-Tianjin-Hebei region, China: Spatial heterogeneity, trade-off relationships, and driving mechanisms - Yuhan Ren; Guangji Fang; Xiao Sun; Yanhua He; Chenrui Wang; Junwei Gu; Zhe Feng (Applied Geography, 2025)

Two-parameter conceptual instantaneous unit hydrograph method with flood peak delay time and shape coefficient - Junwei Zhou; Yi Zhang; Feng Ma; Jisi Fu; Xianyong Gu; Dianguang Ma (Hydrological Sciences Journal, 2025)

TDDet: A novel lightweight and efficient tea disease detector - Yange Sun; Zhihao Li; Huaping Guo; Yan Feng; Yongqiang Tang; Wensheng Zhang; Jingqiu Gu (Computers and Electronics in Agriculture, 2025)

Online detection of broken and impurity rates in half-feed peanut combine harvesters based on improved YOLOv8-Seg - Man Gu; Haiyang Shen; Jie Ling; Zhaoyang Yu; Weiwen Luo; Feng Wu; Fengwei Gu; Zhichao Hu (Computers and Electronics in Agriculture, 2025)

Trade-offs between arbuscular mycorrhizal symbiosis and root hairs in phosphorus source utilization are determined by functional divergence of the rhizosphere bacterial microbiome in barley - Letian Wang; Jiachao Zhou; Timothy S. George; Gu Feng (Soil Biology and Biochemistry, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Impacts of geography, climate, soil properties and vegetation characteristics on soil C:N and N:P stoichiometry across the Qinghai-Tibetan Plateau - Wenlan FENG; Pierre MARIOTTE; Jun GU; Xiaodong SONG; Jinling YANG; Fei YANG; Yuguo ZHAO; Ganlin ZHANG (Pedosphere, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

Metagenomic insights into the synergistic properties and mechanisms of sludge microbial communities degrading polystyrene and polypropylene - Ying Zhou; Wei-hua Gu; Jian-feng Bai; Rui-xue Wang; Cheng-long Zhang; Yao-guang Guo; Cong Lu; Shan-ping Chen (Journal of Hazardous Materials, 2025)

Corrigendum to “Microwave ultra-narrow band antenna sensor based on TiO2/MXene for room-temperature acetone detection” [J. Environ. Chem. Eng. 13 (5) (2025) 118803] - Jie Wei; En-Kang Wu; Ji-Hao Zhang; Zhen Zhang; Xiao-Cong Tang; Tian Qiang; Yongwoo Jang; Xiao-Feng Gu; Meng Zhao; Svetlana von Gratowski; Jun-Ge Liang; Ming-Yang Yan; et al. (Journal of Environmental Chemical Engineering, 2025)

Microwave ultra-narrow band antenna sensor based on TiO2/MXene for room-temperature acetone detection - Jie Wei; En-Kang Wu; Ji-Hao Zhang; Zhen Zhang; Xiao-Cong Tang; Tian Qiang; Yong-Woo Jang; Xiao-Feng Gu; Meng Zhao; Svetlana von Gratowski; Jun-Ge Liang; Ming-Yang Yan; et al. (Journal of Environmental Chemical Engineering, 2025)

In-situ remediation experiment and field application of horizontal wells in contaminated sites - Lingrong Kong; Yu Wang; Bin Zhang; Chao Feng; Ailiang Gu; Xuan Huang (Journal of Environmental Chemical Engineering, 2025)

From waste to flavor enhancer: differential pressure explosion puffing modifies spent coffee grounds for microbial consortia-driven flavor synthesis in craft beer systems - Jingchuan Zheng; Shunqi Luo; Muhammad Aaqil; Yuwei Guo; Feng Zhang; Xiaolin Huang; Yaling Gu; Zhen Zhang; Fanrui Li; Cunchao Zhao; Yang Tian (Food Research International, 2025)

Kill two birds with one stone: In-situ carbon dots-integrated rGO achieves ultra-efficient solar steam generation driving artificially hydrologic cycle towards soil remediation - Jia-Wei Zhu; Qiang Tang; Jinhua Feng; Lin Gu; Qing-Yun Wu (Chemical Engineering Journal, 2025)

Preparation of WO3 nanosheet arrays@Co3O4 nanoneedle arrays composite heterojunction as supercapacitor electrode material - Jiajun Chen; Feng Zheng; Tao Yu; Xingjie Gu; Haonan Wang; Weihao Deng; Peng Li; Yi Yu (Chemical Engineering Journal, 2025)

Insights into excitonic dynamics in conformational distorted porphyrinic covalent organic frameworks for efficient selective photooxidation - Wang-Kang Han; Jiayu Li; Kang Deng; Jing-Dong Feng; Ruo-Meng Zhu; Ming-De Li; Zhi-Guo Gu (Chemical Engineering Journal, 2025)

Hydrogen bond network assisted rapid proton transport of proton exchange membranes modified with heteropoly blue for hydrogen conversion - Zhimei Zhang; Xiangwei Li; Rou Li; Zhen Li; Yiman Gu; Kuirong Feng; Jiayao Yang; Hongqi Liang; Na Li; Yuchao Wang; Zhe Wang (Chemical Engineering Journal, 2025)

Seasonal Variations and Potential Sources of Black Carbon at a Mountain Site in the Central Yunnan Plateau, China - Yanli Wang; Yan Cheng; Song Liu; Feng Xiang; Limei Bi; Qiaoli Wu; Xuan Tian; Shiting Chen; Zechen Gu; Feng Wu (Aerosol Science and Engineering, 2025)

Two-layered structure of subtidal sediment flux across intertidal mudflats due to tidal surges and surface waves - Qianjiang Zhang; Chuangshou Wu; Weifang Gu; Feng Zhou (Frontiers in Marine Science, 2025)
Introduction and Methods Field observations were conducted on an intertidal mudflat along the Zhejiang coast to investigate the influence of tidal surges and waves on subtidal sediment flux. This study reveals a two-layer structure in subtidal sediment flux: landward flux occurs above the mid-depth of the water column, while seaward flux is observed in the near-bed layer. Results Strong tidal surges were observed at both the beginning and end of tidal cycles, enhancing sediment transport. Wave height and mean wave periods peaked during high tide and decreased during tidal surges. In the water column layers above mid-depth, flood surges with high suspended sediment concentrations (SSC) induced landward sediment flux in the subtidal time scale. In the near-bed layer, SSC exhibited peaks during flood surges, ebb surges, and high tide. Discussion During high tide, upward diffusion of sediment by tidal currents balances the downward sediment setting at the near-bed layer, promoting the accumulation of sediment setting from upper layer. The wave shear stress suspended the seabed sediment during high tide, facilitating the formation of near-bed high SSC. Tidal currents showed shorter durations during the flood phase and longer durations during the ebb phase. The high SSC transported seaward by weak ebb currents during high tide accounted for approximately 30% of the total ebb sediment flux, playing a significant role in offshore subtidal sediment transport. The macrotides and strong wave activity provide suitable condition for the development of the two-layer structure of sediment transport in intertidal mudflats.

Effects of nitrogen forms on growth and soil bacterial diversity of Cinnamomum camphora ct. citral seedlings - Zufei Xiao; Yixin Gu; Ying Ding; Feng Li (Environmental Science and Pollution Research, 2025)

Photocatalytic degradation of jellyfish polyps: A sustainable approach to combat jellyfish blooms - Wei Zhang; Jinzeng Gu; Jianing Lin; Song Feng; Ziwei Wang; Zhenhui Gao (Marine Pollution Bulletin, 2025)

Bioengineered iron-based heterojunction orientation in optimizing activation pathways for superoxide radical-mediated photoreduction of Cr(VI) from water - Chunyao Gu; Quanliu Yang; Xiaowen Zhang; Ran Feng; Shuyang Wang; Tianye Liu; Peng He; Huaqun Yin; Jianyu Zhu; Min Gan (Water Research, 2025)

Urban environmental quality of shrinking cities in China improved less than that of non-shrinking cites during 2000-2020: A quantitative comparison based on propensity score matching method - Kaihong Yue; Kang Wu; Qingxu Huang; Yijin Wang; Tianci Gu; Yiming Hou; Xingyun Feng; Shiyu Zhang; Yizhou Xie; Jiasheng Wang (Sustainable Cities and Society, 2025)

Phytohormone-augmented microalgae: A dual-functional solution for pharmaceutical contaminants removal and resource recovery - Jun-Jie Gu; Xiao-Xiao Dou; Jin-Long Zhou; Si-Yuan Guo; Ashiwin Vadiveloo; Xiao-Ling Zhang; Kai-Yuan Li; Dong-Zhi Chen; Feng Gao (Journal of Hazardous Materials, 2025)

Reassessing systemic blind spots in modern water disinfection paradigms - Yang Liu; Jialiang Gu; Kun Feng; Yangyang Zhang; Zheng Zhong; Sitong Liu; Defeng Xing (Journal of Hazardous Materials, 2025)

Novel quantitative method of reactive losses of ambient VOCs coupling chemical transport model simulation with receptor measurement - Yao Gu; Baoshuang Liu; Simeng Ma; Zhongwei Luo; Jinqiu Zhang; Danni Liang; Yafei Li; Yufen Zhang; Yinchang Feng (Journal of Hazardous Materials, 2025)

Restoration of mitochondrial homeostasis by Wnt3a/β-catenin/c-Myc alleviates cadmium-induced neural stem cell senescence and cognitive impairment in mouse hippocampus - Yuwei Zhang; Qiuyun Gu; Yixi Li; Jiayi Li; Yaxin Han; Longfei Feng; Xutong Qin; Jiming Zhang; Zhijun Zhou; Xiuli Chang (Journal of Hazardous Materials, 2025)

LHRS-Bot-Nova: Improved multimodal large language model for remote sensing vision-language interpretation - Zhenshi Li; Dilxat Muhtar; Feng Gu; Yanglangxing He; Xueliang Zhang; Pengfeng Xiao; Guangjun He; Xiaoxiang Zhu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Recent progress on biodeterioration and protection of Cultural Heritage: a conference report of the 2nd international symposium held in Dunhuang, China - Yuxin Chen; Ji-Dong Gu; Huyuan Feng; Clara Enza Urzì; Fasi Wu (International Biodeterioration & Biodegradation, 2025)

From error ellipse to Bayesian estimation: Strategies for optimizing T-W diagrams in UPb dating - Yao Mu; Can Ge; Fangyue Wang; Xiuyu Li; He Sun; Haiou Gu; Feng Yuan (Geochemistry, 2025)

Quality characteristics and structure-function relationships of peanut proteins from different phase sources by aqueous enzymatic extraction - Xin Guo; Wen-ye Xie; Hui Hu; Feng-ying Gu; Fu-sheng Chen; Xing-feng Guo; Bo Jiao; Qiang Wang (Food Chemistry, 2025)

Paeoniae Radix alba polysaccharide modulates gut microbiota to restore metabolites and promote the enteric nervous system development in colitis mice - Chao-Wen Zhang; Si-Zhe Shui; Shuang Liao; Yu-Chao Kuang; Dai-Zheng Yin; Yi Gu; Banaz Jalil; Michael Heinrich; Xing-Fu Chen; Zhong-Qiong Yin; Chun Wu; Xu Song; et al. (Food Bioscience, 2025)

Radical and non-radical peroxymonosulfate activation induced by a novel ferromagnetic Fe1-xS/lignin-based biochar nanocomposite: Multi-pathway synergistic effects for bisphenol A removal - Minglu Zhang; Zunqing Wen; Longquan Zhang; Qingyun Wang; Lihua Zang; Qing Feng; Yawei Gu; Wenyu Wang; Ke Ma; Hao Zhang; Dandan Ji; Jun Liu; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Mechanically tuned dual-network scaffolds orchestrate neuro-angio-osteo coupling for enhanced bone regeneration” [chemical engineering journal 516 (2025) 1–22/CEJ_164176] - Mengmeng Yang; Yang Liu; Wenjie Li; Pengyin Li; Shaoqing Chen; Chun Liu; Bang An; Qiangsheng Dong; Cheng Wang; Feng Xue; Chenglin Chu; Jing Bai; et al. (Chemical Engineering Journal, 2025)

Multi-response hydrogel for real-time monitoring of changes in environmental factors - Yuxuan He; Feng Gu; Zhiguang Guo (Chemical Engineering Journal, 2025)

Trade-offs between bio-flocculation and oxidation: Carbon capture pathway governed by SRT in high-rate contact stabilization process - Dongyi Li; Ruize Gu; Fangyue Peng; Zhengyu Yan; Yanfang Song; Tongtong Liu; Dandan Liang; Weihua He; Yujie Feng (Chemical Engineering Journal, 2025)

Investigating the Impact of Drought During Returning Green and Jointing Stages on Different Tillers Position of Winter Wheat - Muhammad Fraz Ali; Ping Li; Lijuan Ma; Changjie Feng; Shubo Gu; Xiang Lin; Dong Wang (Journal of Plant Growth Regulation, 2025)

Gene cloning, phenol-responsive transcriptional profiling and recombinant protein characterization of phenol hydroxylase in Candida tropicalis GY8 - Jianhua Lv; Xiangnan Gu; Minmin Hui; Yingjie Luo; Wenbo Luo; Huiting Zhao; Shuqin Yin; Yan Feng; Zhiquan Xue (Brazilian Journal of Microbiology, 2025)

Vegetation-induced hydrodynamic alterations on convex slopes: Mechanisms of flow resistance and erosion control - Fangzheng Gu; Huilan Zhang; Huiru Gao; Weicheng Yuan; Di Zhang; Linghan Wang; Feng Li (Journal of Mountain Science, 2025)

Responses of multi-trophic microbial communities to altered precipitation affected soil respiration in coastal wetlands - Yuqi Zhou; Xinge Li; Shuzhen Li; Xiongfeng Du; Zheng Zhang; Zhaojing Zhang; Kai Feng; Xi Peng; Wen Song; Song Gu; Pengpeng Duan; Baohua Xie; et al. (Applied Soil Ecology, 2025)

Transport-corrected flux-moment homogenization method for generating P0 multigroup cross-section based on continuous energy Monte-Carlo - Yuyang Shen; Yiwei Wu; Qufei Song; Kuaiyuan Feng; Hui Guo; Hanyang Gu (Annals of Nuclear Energy, 2025)

Design of Organic Rankine Cycle Recovering Multi-Grade Waste Heat from a Two-Stroke Marine Engine - Jinfeng Feng; Yuncheng Gu; Shengjun Han; Xunhu Zhao; Yujun Tang; Sipeng Zhu; Hao Yuan; Guihua Wang (Journal of Marine Science and Engineering, 2025)
Waste heat recovery using Organic Rankine Cycle (ORC) systems shows significant potential for reducing CO2 emissions from ships. This study designs and analyzes ORC systems for recovering multi-grade waste heat from the exhaust gas, jacket water, and scavenging air of a marine two-stroke diesel engine. A thermodynamic model is developed to investigate the effects of working fluid preheating temperature, evaporation pressure, and heat source conditions on system performance. Results show that appropriately increasing the preheating temperature of the working fluid can enhance power output. For hydrocarbons with higher critical temperatures, power output exhibits an extremum as preheating temperature increases, while for fluids with lower critical temperatures, power output increases continuously until the evaporation pressure limit is reached. Increasing evaporation pressure decreases power output but improves thermal efficiency, with a corresponding increase in heat transfer and exergy loss rates in the exhaust gas preheater. Additionally, the temperature of the heat source has an important effect on the energy and exergy balance distribution and power output of the ORC. For every 10 K rise in exhaust temperature, the bottoming cycle power output of cyclohexane increases by approximately 12.3%. This study provides theoretical support for efficient marine waste heat recovery and working fluid selection.

Alkaloids from Zanthoxylum nitidum and their anti-proliferative activity against A549 cells by regulating the EGFR/AKT/mTOR pathway - Fan-Fan Wang; Ping-Fang Tao; Yu-Jun Zhong; Yun-Qiong Gu; Cai Yi Wang; Feng Qin (Natural Product Research, 2025)

Mechanism of the effect of Juan-Tong-Yin on endoplasmic reticulum stress-autophagy in endometriosis rats based on protein kinase R-like endoplasmic reticulum kinase/eukaryotic cell initiation factor 2α pathway - Qi-Yu Liu; Jing Li; Feng-Qun Gu; Feng-Yun Meng; Ying Liu; Wei-Hong Li (Tissue and Cell, 2025)

Barium isotope variation during granitic magma differentiation: implications for the discrimination of crystal fractionation and fluid-magma interaction - Nian-Qin Zhang; Kun Zhou; Yi-Xiang Chen; Fang Huang; Xiao-Feng Gu; Lin-Hui Dong; Gengxin Deng; Peng Gao (Geochimica et Cosmochimica Acta, 2025)

Cellulose/ionic hydrogel moisture electric generators with enhanced output and stability - Gangli Zhao; Fangzhou Li; Linglan Guo; Dingyun Zhang; Haotian Luo; Jiaxing Huo; Zechao Han; Peicheng Han; Qiaolin Gu; Ran Tang; Yanjie Su; Feng Zhan; et al. (Chemical Engineering Journal, 2025)

A state of art review on carbon, nitrogen, and phosphorus cycling and efficient utilization in paddy fields - Zeyu Zhang; Dongxing Xie; Wenhao Teng; Feng Gu; Rui Zhang; Kui Cheng; Zhuqing Liu; Ying Zhao; Fan Yang (Plant and Soil, 2025)

Nuclear Magnetic Resonance-Based Metabolomics Reveals Systemic Metabolic Disarray in the Transition from Acute Kidney Injury To Chronic Kidney Disease - Lingxiao Wang; Xiuru Wang; Tingxiao Zou; Feng Su; Ying Yao; Jinping Gu (Phenomics, 2025)

A fast and dynamic tracking-based Micropterus salmoides fry counting method in highly occluded scenarios - Haofeng Liu; Meng Cui; Hao Gu; Juan Feng; Lihua Zeng (Aquacultural Engineering, 2025)

Nightshade curly top virus infecting Solanum nigrum was first detected in Jiangsu province, China - Duxuan Liu; Haoyu Chen; Yanhong Hua; Chenwei Feng; Tianxiao Gu; Xiao Guo; Jinlong Yin; Kun Zhang; Kai Xu (Journal of Plant Pathology, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Trash or treasure? Unlocking dark matter of enantiomeric natural products in innovative drugs discovery for potent angiogenesis inhibitors - Yan-Wei Wu; Xiao-Feng Mou; Zhong-Yuan Chen; Xiao-Jia Xue; Wen-Hui Wang; Jin-Zhou Guo; Bo-Qi Zhang; Ting-Ting Xue; Qun Zhang; Mei-Yan Wei; Yu-Cheng Gu; Gulab Said; et al. (Marine Life Science & Technology, 2025)
The occurrence and development of tumors rely on the nutritional supply from blood vessels, which also serve as the main pathway for tumor metastasis. Inhibiting angiogenesis is one of the main strategies for cancer treatments. Chiral drugs, encouraged and inspired by chiral natural products, make up a major portion of marketed drugs. However, as an important source for synthetic chemistry and drug discovery, the counterpart of chiral natural products, the enantiomers, has received little attention. Here, we constructed a compound library containing 100 racemates ( ±)- 1 – 100 and 4 pairs of enantiomers ( 33 , 48 , 59 , 68 ) of 3,4-dioxygenated-4-aryl-quinolin-2(1 H )-one alkaloids. Through extensive activity screening, we found that the compounds with 3 R , 4 R configuration, opposite to the natural products, exhibited potent angiogenesis inhibitory activity in zebrafish, while the 3 S , 4 S -configured natural derivatives have no effects. More importantly, compound ( +)- 48 , named as (3 R , 4 R )-CHNQD-00728, significantly inhibited hepatic tumor growth in doxycin hydrochloride-induced liver-specific enlargement zebrafish. Examining the phenomenon and unlocking dark matter of enantiomeric natural products in innovative drugs discovery can provide a new perspective on organic synthesis and medicinal chemistry, thus enabling a broader exploration.

Association between organic micropollutants in tap water and human exposure and birth outcomes: Implications for environmental health in northern Puerto Rico - Yinmei Feng; Justin Manjourides; Stephanie L. Rich; Guangyu Li; Carmen Velez Vega; Ingrid Y. Padilla; Zaira Rosario-Pabón; Akram N. Alshawabkeh; Damian E. Helbling; Griffith Gao; David Kaeli; John D. Meeker; et al. (Journal of Hazardous Materials, 2025)

Identifying key contributors to the sweet aftertaste of raw Pu-erh tea through analytical and sensory methods - Xiaoping Yuan; Xian Chen; Chunrong Chai; Min Feng; Yongdan Hu; Zhibiao Yi; Ying Gu; Linguang Ruan; Lunzhao Yi (Food Chemistry, 2025)

Exploring the role of carbon source types in trace-level sulfamethoxazole removal and greenhouse gas emissions in AnMBRs - Wanli Yan; Lide Gu; Haoran Li; Jianguo Li; Shikan Zheng; Mingbao Feng; Xin Yu (Environmental Research, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Mechanically tuned dual-network scaffolds orchestrate neuro-angio-osteo coupling for enhanced bone regeneration - Mengmeng Yang; Yang Liu; Wenjie Li; Pengyin Li; Shaoqing Chen; Chun Liu; Bang An; Qiangsheng Dong; Cheng Wang; Feng Xue; Chenglin Chu; Jing Bai; et al. (Chemical Engineering Journal, 2025)

Bacterial N-acyl-homoserine lactone enhances the degradation of sulfamethoxazole by microalgae and the associated metabolic regulatory mechanisms - Bin-Di Mao; Kai-Yuan Li; Ashiwin Vadiveloo; Jun-Jie Gu; Feng Gao (Bioresource Technology, 2025)

Maternal transcription factor OTX2 directly induces SETD1A and promotes embryonic genome activation in human pre-implantation embryos - Tianlei Zhang; Ziyan Peng; Fei Meng; Zhuo Li; Junru Chen; Qinwei Zhou; Lizhi Leng; Hao Bo; Guangxiu Lu; Yun Deng; Feng Gu; Ge Lin (Science China Life Sciences, 2025)

Morphometric comparison of phytoliths in wild rice (Oryza rufipogon) and domesticated rice (Oryza sativa subsp. japonica and Oryza sativa subsp. indica): taxonomic implications - Yuenan Li; Mingjuan Jiang; Yansheng Gu; Min Zheng; Shaofan Fang; Yifei Du; Liang Feng (Science China Earth Sciences, 2025)

Research on section-based canopy leaf area online calculation model for the whole growth period of fruit trees - Hanjie Dou; Mengmeng Wang; Changyuan Zhai; Yanlong Zhang; Chenchen Gu; Fan Feng; Chunjiang Zhao (Computers and Electronics in Agriculture, 2025)

Lipid surface droplet 2 (LSD2) regulates lipid metabolism and male reproductive physiology in adult Sitotroga cerealella - Sakhawat Shah; Yu Li; Wen-Han Yan; Lianyun Liu; Tianyu Gu; Karam Khamis Elgizawy; Gang Wu; Feng-Lian Yang (Pesticide Biochemistry and Physiology, 2025)

Anti-inflammatory sesquiterpenoids from Chloranthus japonicus - Wei-Jiao Feng; Pei-Zhi Huang; Li-Mei Zhang; Qian Ma; Hong-Yu Hu; Yue Gu; Ya Li; Kun Gao (Phytochemistry, 2025)

Phylogenetic relationships and species composition of host community influence the transmission of coronaviruses in sympatric bats - Chen Zhang; Hao Gu; Jie Peng; Biao He; Yuhang Liu; Xiaomin Yan; Jiang Feng; Ying Liu (Molecular Phylogenetics and Evolution, 2025)

Impacts of disinfection methods in a granular activated carbon (GAC) treatment system on disinfected drinking water toxicity - Yinmei Feng; Stephanie S. Lau; William A. Mitch; Caroline Russell; Greg Pope; April Z. Gu (Journal of Hazardous Materials, 2025)

Resource utilization of the waste lithium slag in oil-well cement under high temperature: Mechanical property, hydration behavior and environmental effect - Zhao Feng; Zeng Xueling; Long Dan; Gu Anlin; Mei Kaiyuan; Zhang Chunmei; Cheng Xiaowei (Journal of Environmental Chemical Engineering, 2025)

Hydrothermal temperature-dependent compositions and copper complexing behaviors of hydrochar-derived dissolved organic matter: Insights from FT-ICR MS and multi-spectroscopic analysis - Bingfa Chen; Xincai Gu; Muhua Feng; Yanfang Feng; Bingyu Wang; Bensheng You; Jingcheng Zheng; Hong Liu; Shiqun Han (Journal of Environmental Sciences, 2025)

Surface pyrolysis towards graphite heterojunctions for aqueous Zinc-ion capacitor - Lingqi Huang; Jiayang Gu; Beinuo Wang; Wenqing He; Shengwei Xiao; Junbin Liao; Ziyang Chang; Zhixin Jia; Shangru Zhai; Yi He; Heyang Liu; Fei Zhang; et al. (Chemical Engineering Journal, 2025)

Immobilizing PdCd dual-atom sites on rhombic dodecahedral nitrogen-doped carbon matrix for enhancing electrocatalytic CO2 reduction reaction - Yanlong Gong; Xiaoli Ran; Xiaohong Yang; Shixian Xiong; Feng Gu; Shufen Wang; Jiangcheng Li; Haitao Fu; Xizhong An (Chemical Engineering Journal, 2025)

Controllable fabrication of hierarchical porous anode for exoelectrogens internal colonization in microbial electrochemical system - Yujie Zhu; Dandan Liang; Ruize Gu; Shujuan Liu; Pinpin Yang; Lijuan Zhang; Weihua He; Yujie Feng (Bioresource Technology, 2025)

Parametric Simulation of Stress Wave Propagation Affected by High-Temperature Damage in Rocks Using a Coupled DLSM-DDA Method - Yuliang Zhang; Yiming Gu; Lifeng Fan; Gao-Feng Zhao; Fuxin Rui (Rock Mechanics and Rock Engineering, 2025)

Distinct effects of abundant and rare microbial communities on ecosystem multifunctionality across the soil profiles in agricultural Isohumosols - Haidong Gu; Zhuxiu Liu; Qin Yao; Feng Jiao; Junjie Liu; Jian Jin; Xiaobing Liu; Guanghua Wang (Soil Ecology Letters, 2025)

Development of deep-sea mining and its environmental impacts: a review - Wen Yao; Chi Tian; Yao Teng; Feng Diao; Xinguang Du; Peng Gu; Weixin Zhou (Frontiers in Marine Science, 2025)
With the increasing demand for mineral resources and the continuous depletion of terrestrial mineral deposits, deep-sea mining has garnered significant attention from governments, industries, and research institutions. However, the current deep-sea mining technologies remain incompletely developed, and their environmental impacts cannot be overlooked. This review presents a brief introduction to the three primary mineral resources found in the deep sea and the relative deep-sea mining system, along with their potential environmental risks. As the deep-sea benthic ecosystem is particularly vulnerable, the impacts on environment of each phase of deep-sea mining should be monitored and controlled. The movement and operation of seafloor mining vehicles generate both direct and indirect environmental impacts, including seabed destruction and plume generation. These effects pose significant threats to benthic organisms and alter the deep-sea environment. Finally, we present future perspectives and insights for subsequent research and the industrialization of deep-sea mining.

Dynamic motion response of a large-scale steel aquaculture cage during towing - Shuai Niu; Zhi Wang; Lianyi Guo; Lianghao Tang; Tianyu Gu; Can Cui; Dejun Feng; Fukun Gui; Xu Yang (Frontiers in Marine Science, 2025)
As global aquaculture ventures further into offshore environments, the safe transport of large-scale aquaculture net cages across varied marine conditions has become a critical technical concern. This study conducts a detailed numerical simulation of the wet towing process for an octagonal aquaculture cage using AQWA software, systematically examining the effects of towline length, towing speed, towing configuration, and environmental factors on the cage’s dynamic response and towline load characteristics. The findings reveal that towline length and towing speed are pivotal in determining the pitch amplitude of the cage and the resulting towline tension. Compared to a towline length of 200 m, using a towline length of 150 m combined with a towing speed of 0.5 m/s reduces pitch amplitude by 51.6% and towline tension by 24.8%. Additionally, an interval towing arrangement significantly enhances cage stability while minimizing towline stress. Under conditions of low wave height and longer wave period, the cage’s motion response remains stable, contributing to enhanced transport safety. This research offers critical theoretical foundations and optimization strategies for the wet towing design considerations of offshore aquaculture cages, providing valuable insights to advance transport safety in challenging marine environments.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Pronounced advance on typhoon track forecast with global convection-permitting model - Jun Gu; Chun Zhao; Gudongze Li; Jiawang Feng; Mingyue Xu; Qiuyan Du; Zihan Xia; Yubin Li; Guanghua Chen; Xiaoyu Hao; Junshi Chen; Hong An (Science Bulletin, 2025)

Blue carbon potential from rehabilitating urban mangrove forests in coastal city - Peiyang Qiao; Yue Meng; Changxin Liu; Tingting Zhang; Mei Li; Liangxia Feng; Qinchang Chen; Jialin Zhang; Chen Lin; Xiaoxuan Gu; Luzhen Chen (Estuarine, Coastal and Shelf Science, 2025)

Synergistic intensification of membrane reactor with biochar catalyst for efficient production of clean syngas from biomass gasification - Ajing Ding; Qiaoqiao Zhou; Wei Wei; Shuncheng Li; Huanhao Chen; Feng Zeng; Yuting Zhang; Zhaoxiang Zhong; Anthony De Girolamo; Lian Zhang; Xuehong Gu (Chemical Engineering Journal, 2025)

Smart temperature sensors based on flexible CB/TPU/ PVDF membranes for eliminating pressure interference - Shuo Li; Jiaxin Sun; Feng Tong; Guo Chen; Zhefu Mu; Xiaoqiang Zhang; Sheng Huang; Zheng Chen; Lei Xu; Changyun Li; Peng Wang; Xiuquan Gu (Chemical Engineering Journal, 2025)

A novel N/C co-modified FeS2 nanocomposite synthesized by wet-mechanochemical method for efficient peroxymonosulfate activation and nearly 100% SO4•─ selective generation - Longquan Zhang; Guangfei Gao; Xiaoguo Shi; Zunqing Wen; Minglu Zhang; Qingyun Wang; Qing Feng; Jing Sun; Xuezheng Liu; Ying Zhao; Yawei Gu; Wenqiang Jiang (Chemical Engineering Journal, 2025)

Advances of microalgae-based enhancement strategies in industrial flue gas treatment: From carbon sequestration to lipid production - Kai-Yuan Li; Jin-Long Zhou; Si-Yuan Guo; Xiao-Xiao Dou; Jun-Jie Gu; Feng Gao (Bioresource Technology, 2025)

Association between multiple metals mixture and diabetic retinopathy in older adults with diabetes mellitus: a cross-sectional study in China - Shuren Ding; Yirong Xie; Feng Wang; Jieyi Liu; Hongya Li; Heng Su; Zhiqiang Zhao; Qing Wei; Shurong Pi; Fubin Chen; Qian Gu; Baixiang Xiao; et al. (Environmental Geochemistry and Health, 2025)

Optically pH-Sensing in smart wound dressings towards real-time monitoring of wound states: A review - Hongchun Gu; Xinxing Sun; Hongyang Bao; Xun Feng; Yang Chen (Analytica Chimica Acta, 2025)

Dynamically managing soil phosphorus could halve phosphorus losses from cropland in lake basins - Pengqi Liu; Qingwen Shi; Zhuo Chen; Mingyang Wang; Feiyu Ying; Xiaowen Gu; Yuxiao Wu; Zhi Yao; Wen-Feng Cong; Zhengxiong Zhao; Hao Ying (Agriculture, Ecosystems & Environment, 2025)

Multi-angular spectroscopic detection of winter wheat nitrogen fertilizer utilization status using integrated feature selection and machine learning - Haiyan Zhang; Li He; Qiwen Chen; Mukhtar Iderawumi Abdulraheem; Geng Ma; Yanfei Zhang; Jingjing Gu; Jiandong Hu; Chenyang Wang; Wei Feng (Computers and Electronics in Agriculture, 2025)

Modulation of CO2 hydrogenation selectivity through microstructural phase evolution-induced electronic transfer on Ni/TiO2 - Yunhao Zang; Xuetan Lin; Jiangying Qu; Feng Gao; Jianfeng Gu; Taipeng Wei; Rongrong Wang (Fuel, 2025)

In-situ pore forming bone adhesives targeting disordered osteoimmune microenvironment and bone metabolic balance to promote osteoporotic fracture healing - Haiyue Zhao; Lingjun Wang; Kun Xi; Wei Wang; Xinzhao Jiang; Jiahao Wang; Liang Zhou; Wenbo Wang; Feng Cai; Meng Han; Jincheng Tang; Yu Feng; et al. (Chemical Engineering Journal, 2025)

Air oxidation behavior of wet-mechanochemically synthesized pyrite FeS2: Fenton performance regulated by Fe species, sulfur vacancy and crystal facet ratio - Zunqing Wen; Xiaoguo Shi; Huiying Sui; Minglu Zhang; Longquan Zhang; Yawei Gu; Qing Feng; Ke Ma; Na Zhang; Mingzhe Wang; Ruiyan Zhang; Chongqing Xu; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “A double-network polysaccharide-based composite hydrogel for skin wound healing” [Carbohydrate Polymers; June 2021, volume 261, issue 261C, 117870] - Yuxin He; Yang Li; Yadong Sun; Shijia Zhao; Miao Feng; Guoming Xu; Haofang Zhu; Peihong Ji; Hongli Mao; Yiyan He; Zhongwei Gu (Carbohydrate Polymers, 2025)

Dextran from human feces-derived Weissella cibaria facilitates intestinal mucosal barrier function by modulating gut bacteria and propionate levels - Huan Zhao; Sakandar Abbas; Jing Ren; Haibin Huang; Ying Song; Xiaoning Su; Qiuyang Wu; Yane Ma; Hao Tang; Yi-Zhou Gao; Yuanzhe Li; Xiaoming Gu; et al. (Carbohydrate Polymers, 2025)

Identification and study of mood-related biomarkers and potential molecular mechanisms in type 2 diabetes mellitus - Menglong Wang; Tongrui Wang; Yang Liu; Lurong Zhou; Yuanping Yin; Feng Gu (Journal of Molecular Histology, 2025)

Role of Glucose Metabolism in the Effects of Serum Metals on Telomere Length: Findings in Chinese Diabetic Population - Shuren Ding; Qian Gu; Zhiqiang Zhao; Yirong Xie; Feng Wang; Jieyi Liu; Hongya Li; Heng Su; Qing Wei; Shurong Pi; Fubin Chen; Baixiang Xiao; et al. (Biological Trace Element Research, 2025)

A simple and effective algorithm to retrieve total suspended matter from GOCI data in Hangzhou Bay, China - Mingjun He; Shuangyan He; Shiming Lu; Yanzhen Gu; Feng Zhou; Xiaobo Ni; Chengyue Zhu; Peiliang Li (Science of The Total Environment, 2025)

Comprehensive analysis of transplacental transfer of environmental pollutants detected in paired maternal and cord serums - Ke-Yu Yuan; Yao-Hua Gu; Yi-Hao Pei; Si-Yu Yu; Tian-Zhou Li; Tian Feng; Yu Liu; Jianbo Tian; Xiaoping Miao; Jun Xiong; Min Hu; Bi-Feng Yuan (Journal of Hazardous Materials, 2025)

Accumulation characteristics and fate modeling of phthalic acid esters in surface water from the Three Gorges Reservoir area, China - Shuai Sun; Bing Zhang; Junjie Hu; Wen Gu; Zhen Wang; Deling Fan; Feng Ge; Lili Shi; Lei Wang (Journal of Environmental Sciences, 2025)

Dynamic changes in nutritions and antioxidant activities of germinated black bean based on solid-state fermentation of Ganoderma oregonense - Xiaoqin Ren; Qiongling Chen; Feng Wang; Helin Guo; Yu Wang; Fengying Gu (Innovative Food Science & Emerging Technologies, 2025)

Cyclization: A potential effective modification strategy for umami peptides - Zhiyong Cui; Yanyang Yu; Tianxing Zhou; Chengliang Qi; Jiaming Gu; Ninglong Zhang; Xiaoxiao Feng; Zhiwei Zhang; Yiwen Zhu; Yin Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Characterizing sources and health risks of airborne Carbonyl compounds in a subtropical coastal atmosphere in South China - Yang Xu; Penggang Zheng; Xin Feng; Hao Sun; Mingyao Sun; Lirong Hui; Yao Chen; Yi Chen; Dasa Gu; Zhi Ning; Jian Zhen Yu; Zhe Wang (Environmental Pollution, 2025)

Crop yield and soil quality of soya bean-maize rotation in response to 8-year keep stubble with no tillage practices on the Northeast China - Weijian Zhang; Jingyi Feng; Xueyan Bai; Wanying He; Jixian Mo; Qiance Gao; Kunjie Wang; Siyu Gu (European Journal of Agronomy, 2025)

Covalent organic frameworks supported geminal-atom catalysts for upcycling nitrate into single-cell protein - Jing-Dong Feng; Wen-Da Zhang; Han Zhao; Bixuan Gu; Yong Liu; Xiaomei Lyu; Huan Pang; Liangliang Xu; Zhi-Guo Gu (Chemical Engineering Journal, 2025)

Outer membrane vesicles from Pseudomonas aeruginosa induce autophagy-regulated pyroptosis in THP-1 cells - Jing Ge; Yaoyang Liu; Tianqi Wu; Sitian Yi; Jiang Pu; Juan Gu; Feng Wang; Juan Yu (Archives of Microbiology, 2025)

Exploring strategies for kitchen waste treatment and remediation from the perspectives of microbial ecology and genomics - Zheyu Gu; Lei He; Tao Liu; Meiyan Xing; Leiyu Feng; Guilin Luo (Chemosphere, 2025)

Wheat Fusarium head blight severity grading using generative adversarial networks and semi-supervised segmentation - Guoqing Feng; Ying Gu; Cheng Wang; Dongyan Zhang; Rui Xu; Zhanwang Zhu; Bin Luo (Computers and Electronics in Agriculture, 2025)

Effects of three naturally extracted polysaccharides on the growth, antioxidant capacity, and intestinal health during early-stage of juvenile lined seahorses (Hippocampus erectus) via trophic transfer - Haolong Zheng; Weilong Zhou; Xiaofei Ma; Xiabin Zhang; Xing Zheng; Xianming Tang; Shouguo Yang; Yaohua Shi; Feng Yu; Zhifeng Gu (Aquaculture, 2025)

Acidosis induces autophagic cell death through ASIC1-mediated Akt/mTOR signaling in HT22 neurons - Miao Guo; Ming-Yue Qiu; Lin Zeng; Ya-Xiong Nie; Ya-Ling Tang; Yan Luo; Hong-Feng Gu (Toxicology, 2025)

Hyphosphere core taxa link plant-arbuscular mycorrhizal fungi combinations to soil organic phosphorus mineralization - Letian Wang; Lin Zhang; Timothy S. George; Gu Feng (Soil Biology and Biochemistry, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Seasonal dynamics of water-use strategies and response to precipitation in different habitats of Nitraria L. - Huli Gu; Guopeng Chen; Heng Ren; Bing Liu; Qiyue Yang; Xiangyan Feng; Mingyan Fan; Hai Zhou (Journal of Hydrology, 2025)

Structural and dynamic characteristics of horseshoe vortex systems in front of rigid vegetation inclined upstream under conditions of overland flow - Feng Li; Huilan Zhang; Fangzheng Gu; Shaoqin Xia; Yuan He; Linghan Wang; Di Zhang (Journal of Hydrology, 2025)

Genomic analysis of modern maize inbred lines reveals diversity and selective breeding effects - Kaijian Fan; Mohsin Ali; Kunhui He; Yingwei Feng; Tingxi Yu; Hao Zhang; Tai An; Weiwei Zeng; Junjie Fu; Ying Zhou; Yanfang Heng; Fei Gu; et al. (Science China Life Sciences, 2025)

Genome-wide CRISPR screens identify CLC-2 as a drug target for anti-herpesvirus therapy: tackling herpesvirus drug resistance - Fayu Yang; Nan Wei; Shuo Cai; Jing Liu; Qingping Lan; Hao Zhang; Lu Shang; Bo Zheng; Mi Wang; Yingchun Liu; Lifang Zhang; Chenzhong Fei; et al. (Science China Life Sciences, 2025)

Development and verification of an MC/MOC two-step scheme for neutronic analysis of FCM-fueled micro gas-cooled reactor - Kuaiyuan Feng; Qufei Song; Yuyang Shen; Lei Lou; Yao Xiao; Hui Guo; Hanyang Gu (Annals of Nuclear Energy, 2025)

Satellite-based re-examination of global soil moisture variation - Huihui Feng; Shu Wang; Shijie Li; Wei Wang; Jingya Li; Runxi Gu; Jixian Huang (Advances in Space Research, 2025)

Correction: Digital evolution and interaction of green initiatives with institutional instruments: emerging determinants of SDGs2030 of BRICS - Qiming Yang; Yan Yang; Gaoshang Yang; Lang Gu; Jing Feng; Zia Ur-Rehman; Faiz Nayabb (Environment, Development and Sustainability, 2025)

Ivermectin induces oxidative stress and mitochondrial damage in Haemonchus contortus - Cuifang Gu; Haoran Zhong; Xiaoping Luo; Jianqi Yuan; Gaowa Gong; Ying Feng; Xingfu Zhang; Xingang Feng; Yamei Jin; Junyan Li (Veterinary Parasitology, 2025)

Anthropogenic exacerbations of summer-autumn compound dry-hot severity in the middle and lower reaches of the Yangtze River - Shuyun Feng; Xihui Gu; Yansong Guan; Quan J. Wang; Lunche Wang; Lingtong Du; Jie He; Xiang Zhang; Dongdong Kong (Journal of Hydrology, 2025)

Mechanistic study of synergetic stabilization of Pickering emulsions by corn glutelin and starch complexes - Yanqi Wang; Yuying Chen; Liping Feng; Fengzhang Wang; Ting Liu; Fengying Gu; Feng Wang; Qingrong Huang; Jinkai Zheng (Food Chemistry, 2025)

Effect of temperature regulation on microbial community, volatile flavours, amino acid profiles, and iridoid glycosides during noni (Morinda citrifolia L.) fruit fermentation - Chao Zhang; Chunhe Gu; Mengrui Wang; Junxia Chen; Haode Chang; Ziqing Chang; Junping Zhou; Mingzhe Yue; Wenjing Zhang; Quanmiao Zhang; Zhen Feng (Food Chemistry, 2025)

Efficient microplastic removal in aquatic environments using iron–nitrogen co-doped layered biocarbon materials - Xu Feng; Xiangyu Gu; Guohui Xuan; Hao Wu; Songgeng Li (Chemical Engineering Journal, 2025)

Multifunctional electrolyte additives enabled adaptable interface toward stabilizing Zn metal anodes - Yanrui Zhao; Chunyan Cao; Ni Zhang; Fanghua Liang; Huilong Dong; Honggang He; Shanshan Li; Yu Feng; Ruiqing Li; Wenyan Gu; Bin Fei; Mingzheng Ge (Chemical Engineering Journal, 2025)

An oxidation-adsorption site separation strategy for stabilizing Pd-Pt/SSZ-13 PNA materials under high CO pressure - Chen Wang; Xue Kang; Yuntao Gu; Feng Gao (Chemical Engineering Journal, 2025)

A singular spectrum analysis-enhanced BiTCN-selfattention model for runoff prediction - Wen-chuan Wang; Feng-rui Ye; Yi-yang Wang; Miao Gu (Earth Science Informatics, 2025)

Trends in conductive MOFs for sensing: A review - Lingli Qu; Yiwen Xu; Weikang Cui; Lingjuan Wu; Yi Feng; Yangyang Gu; Hongzhi Pan (Analytica Chimica Acta, 2025)

A Method for Aliasing Metal Particle Recognition Based on Three-Coil Sensor Using Frequency Conversion - Di Wu; Yucai Xie; Chenyong Wang; Xian’an Gu; Feng Gu; Guoqing Li; Hongpeng Zhang; Yunsheng An; Rui Li; Changzhi Gu (Journal of Marine Science and Engineering, 2024)
The diesel engine on a ship is crucial as it serves as the primary power source, significantly influencing both the vessel’s efficiency and safety. Monitoring metal wear particles found in lubricating oil is essential for assessing the lubrication condition of mechanical equipment onboard and anticipating potential failures. Analyzing these metal wear particles allows us to gauge the wear status of bearing pairs within the machinery, thereby providing a technical foundation for routine maintenance activities. However, under real operating conditions, it can be challenging to prevent multiple metal particles from simultaneously passing through sensors. To address this issue, this research introduces an innovative three-coil induction sensor that employs a variable-frequency excitation technique to explore how induction and eddy currents interact. The findings indicate that when the excitation frequency changes, the peak value of the signal from 337 μm iron particles only increases by 3.35 times, while the peak value of the signal from 340 μm copper particles increases by 22.69 times. Consequently, this study recommends using changes in excitation frequency to differentiate between mixed metal particles made of various materials.

Digital evolution and interaction of green initiatives with institutional instruments: emerging determinants of SDGs-2030 of BRICS - Qiming Yang; Yan Yang; Gaoshang Yang; Lang Gu; Jing Feng; Zia Ur-Rehman; Faiz Nayabb (Environment, Development and Sustainability, 2024)

USP13 promotes acute myeloid leukemia cell proliferation and autophagy by promoting ATG5 - Yuchu Yuan; Meizhu Xue; Feng Zhou; Lifang Gu (Tissue and Cell, 2024)

A comprehensive evaluation of the optimum amount of phosphate fertilizer for drip irrigation of cotton under mulch based on root morphology, physiology, and mycorrhizal symbiosis - Bolang Chen; Zupeng Ye; Xuexia Tang; Zhongping Chai; Yue Ma; Jiandong Sheng; Gu Feng (Soil and Tillage Research, 2024)

Design and tests of a marine current turbine in low flow velocity - Hongwei Liu; Jiangyuan Fang; Yajing Gu; Zhiyuan Gao; Xiangheng Feng (Ocean Engineering, 2024)

Removal of 48 per- and polyfluoroalkyl substances (PFAS) throughout processes in domestic and general industrial wastewater treatment plants: Implications for emerging alternatives risk control - Yueqing Zhang; Ruochen Dong; Feng Ge; Minghui Hong; Zhanghao Chen; Yunqiao Zhou; Jing Wei; Cheng Gu; Deyang Kong (Journal of Hazardous Materials, 2024)

Novel fuel-efficient cryogenic carbon capture system for the combustion exhaust of LNG-powered ships - Qingfeng Jiang; Wenqing Duan; Huaibing Li; Hansheng Feng; Wu Du; Jiayang Gu (International Journal of Refrigeration, 2024)

Integrated dual-biomarker detection: Transforming proteins and nucleic acids into ssDNA for enhanced disease diagnosis - Jie Liu; Shuang Wu; Chao Zhang; Minli You; Haoqing Zhang; Feng Xu; Won Gu Lee; Hui Guo; Zedong Li (Chemical Engineering Journal, 2024)

Enhancing phosphorus release and recovery from waste activated sludge by citric acid treatment and cyclic extraction - Fangyue Peng; Weihua He; Ruize Gu; Dandan Liang; Dongyi Li; Yujie Feng (Chemical Engineering Journal, 2024)

Seasonal variation and origins of C1–C5 alkyl nitrates: A year-long study at a Hong Kong coastal site - Hao Sun; Dasa Gu; Zijie Xu; Xin Feng; Xiangyunong Cao; Yuchen Mai; Xin Li; Ho Wun Lee; Ka Fung Leung; Tsz Ching Tse; Wai Ming Chan; Sin Ka Mak (Atmospheric Environment, 2024)

Inhibition of the RXRA-PPARα-FABP4 signaling pathway alleviates vascular cellular aging by an SGLT2 inhibitor in an atherosclerotic mice model - Weiwei Zhang; Linghuan Wang; Yujia Wang; Yan Fang; Ruihua Cao; Zhiyi Fang; Dong Han; Xu Huang; Zhenghui Gu; Yingjie Zhang; Yan Zhu; Yan Ma; et al. (Science China Life Sciences, 2024)

Effects of elevated ozone, warming, and their interactions on the stem lodging resistance of rice under fully open-field conditions - Zaisheng Shao; Jiaming Gu; Longxin He; Yansen Xu; Bo Shang; Zhaozhong Feng (Agriculture, Ecosystems & Environment, 2024)

Noise reduction and analysis of leaf electrical signals of strap-leaved plants based on VMD-EWT - Jiaming Gu; Fangming Tian; Jingxiu Shi; Feng Tan (Computers and Electronics in Agriculture, 2024)

Identification of major histocompatibility complex II gene in Pampus argenteus and the expression pattern in Pampus argenteus kidney cell line under the pathogen stress - Youyi Zhang; Jiabao Hu; Yuanbo Li; Weiwei Gu; Zukang Feng; Kaiheng Yan; Man Zhang; Yaya Li; Zi Yuan; Xiaomei Sun; Lu Zhang; Shanliang Xu; et al. (Aquaculture, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Assessing the formation and stability of paddy soil aggregate driven by organic carbon and Fe/Al oxides in rice straw cyclic utilization strategies: Insight from a six-year field trial - Wenqi Gu; Yuning Wang; Yuanyuan Sun; Zifan Liu; Wenjia Wang; Di Wu; Yuxue Zhang; Wen Sun; Xin Wang; Zhibo Feng; Weiming Zhang; Wenfu Chen (Science of The Total Environment, 2024)

MFC-residual sludge coupled treatment for simulated chromium(VI) wastewater: Electricity production performance and microbial communities - Wenwen Gu; Yun Wang; Xiaopeng Hu; Feng Deng (Journal of Water Process Engineering, 2024)

Simultaneous detection of Vibrio parahemolyticus and antimicrobial resistance genes using immonomagnetic separation combined with RPA-microfluidic method in seafood - Han Jiang; Jingwen Wang; Wenjie Jiang; Jing Wang; Xiuying Gu; Xiaorui Feng; Chenze Lu; Jiehong Fang (Food Control, 2024)

Citrus yield estimation for individual trees integrating pruning intensity and image views - Yihang Zhu; Feng Liu; Yiying Zhao; Qing Gu; Xiaobin Zhang (European Journal of Agronomy, 2024)

Durable flame retardant and UV-resistant coating for Poly (ethylene terephthalate) fabric with recyclability and reusability - Yulong Qu; Feng Chen; Xiaowei Su; Jian Liu; Xiaoyu Gu; Hongfei Li; Jun Sun; Peng Qi; Sheng Zhang (Chemical Engineering Journal, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

High-Strength PVA/Cellulosic hydrogels with Acid/Base and thermo dual-responsive fluorescence - Xuezhen Feng; Yabing Tian; Gaoyuan Gu; Chao Wang; Shibin Shang; Xujuan Huang; Jianxin Jiang; Zhanqian Song; Haibo Zhang (Chemical Engineering Journal, 2024)

Association between air pollution, meteorological factors and hand, foot, and mouth disease incidence in Zhejiang Province: A Bayesian spatio-temporal modelling study - Zhixin Zhu; Jian Cai; Yan Feng; Lanfang Gu; Xifei Guan; Nawen Liu; Hua Gu; Xiuyang Li (Atmospheric Environment, 2024)

Numerical study on the neutronics-thermal-mechanics coupling characteristics of the heat pipe nuclear reactor core - Yihu Wang; Kuaiyuan Feng; Yiwei Wu; Limin Liu; Hui Guo; Tenglong Cong; Hanyang Gu (Annals of Nuclear Energy, 2024)

Dynamics between soil fixation of fertilizer phosphorus and biological phosphorus mobilization determine the phosphorus budgets in agroecosystems - Yanlong Li; Zhen Xu; Lin Zhang; Wangzun Chen; Gu Feng (Agriculture, Ecosystems & Environment, 2024)

Research on regional "dual carbon" targets and path planning based on mathematical modeling methods: a case study of southeast coastal China - Haiyang Shen; Kai Guo; Xuan Liao; Qimin Gao; Feng Wu; Fengwei Gu; Zhichao Hu (Environment, Development and Sustainability, 2024)

Single and mixture toxicity of benzophenone-3 and its metabolites on Daphnia magna - Yun-Ru Ju; Chang-Rui Su; Chih-Feng Chen; Cheng-Fu Shih; Li-Siang Gu (Chemosphere, 2024)

Adaptive adjustment of the FM component of calls in CF-FM bats is not involved in avoidance of conspecific jamming - Jianan Ding; Hao Gu; Kangkang Zhang; Aiqing Lin; Jiang Feng; Ying Liu (Animal Behaviour, 2024)

Engineering human midbrain organoid microphysiological systems to model prenatal PFOS exposure - Chunhui Tian; Hongwei Cai; Zheng Ao; Longjun Gu; Xiang Li; Vivian C. Niu; Maria Bondesson; Mingxia Gu; Ken Mackie; Feng Guo (Science of The Total Environment, 2024)

The general patterns of water flow in loess slope system and implications for slope geological security - Li Feng; Maosheng Zhang; Hao Liu; Bin Zhang; Zhen Du; Pingping Sun; Junbo Bi; Liang Wang; Tianfeng Gu (Science of The Total Environment, 2024)

Unveiling the impact of mulching film promotion on the food–water–environment–plastic nexus - Yifan Gu; Zixin Bian; Yufeng Wu; Qianqian Shi; Yanhong Feng; Haibo Meng; He Peng; Jinping Qu; Tieyong Zuo (Resources, Conservation and Recycling, 2024)

Development of a natural iron-based mineral/biochar composite for efficient simultaneous removal of Cr(VI) and methylene blue in the presence of oxalic acid - Chunyao Gu; Miao Cai; Peng He; Xiaowen Zhang; Ran Feng; Shuyang Wang; Tianye Liu; Kejing Zhang; Min Gan; Huaqun Yin; Jianyu Zhu (Journal of Environmental Chemical Engineering, 2024)

Spore germination and lactic acid combined treatment: A new processing strategy for the shelf-life extension of instant wet noodles - Qiaozhen Zhang; Fengying Gu; Tian Li; Xin Guo; Yang Li; Manzhu Liang; Feng Wang; Qin Guo; Qiang Wang (International Journal of Food Microbiology, 2024)

Behavior of surface loaded clay foundation reinforced by GESCs with lateral geosynthetic cushion under freeze-thaw cycles - Zi-Ang Gu; Jian-Feng Chen; Chungsik Yoo (Geotextiles and Geomembranes, 2024)

Potassium-mediated control of adsorbed intermediates on CuCoAl layered nanoplates for ethanol synthesis from syngas - Kai Sun; Shiqi Geng; Jiaqian Yang; Faen Song; Yongqiang Gu; Haozhe Feng; Noritatsu Tsubaki; Qingde Zhang; Yisheng Tan (Fuel, 2024)

Advancements in data center cooling systems: From refrigeration to high performance cooling - Feng Zhou; Wenlong Gu; Guoyuan Ma (Energy and Buildings, 2024)

Hierarchically porous structure based on humic acid endogenous modified carbon electrodes for microbial electrochemical system energy recovery and electroactive biofilm conditioning - Yujie Zhu; Lijuan Zhang; Ruize Gu; Yushi Tian; Dandan Liang; Weihua He; Yujie Feng (Chemical Engineering Journal, 2024)

Holocene transgression and Neolithic human adaptations in the Zhejiang coastal Plain, East China - Yuenan Li; Yansheng Gu; Hongye Liu; Zhongbiao Fu; Xiaoming Tang; Hangjian Feng; Xinghua Xu; Shuo Guan (CATENA, 2024)

Impact of a Three-Dimensional Reference State in a Global Semi-Implicit Semi-Lagrangian Non-Hydrostatic Atmospheric Model on Yin–Yang Grids - Yifan Zhao; Xindong Peng; Dehui Chen; Yerong Feng; Xiaohan Li; Juan Gu (Journal of Meteorological Research, 2024)

What Caused the Differences between the July 2023 and August 1996 Extreme Rainfall Events in North China under Similar Synoptic Background? - Xinghua Bao; Jisong Sun; Jinfang Yin; Xiaoyu Gao; Feng Li; Xudong Liang; Haodong Gu; Rudi Xia; Mingxin Li; Chong Wu; Jianing Feng (Journal of Meteorological Research, 2024)

Rich-silicon rice husk ash increases iron plaque formation and decreases cadmium and arsenic accumulation in rice seedlings - Jiao-Feng Gu; Xuan-Tao Yi; Kun Ouyang; Qian Li; Ping You; Rui Zhou; Peng Zeng; Ye Liao; Hang Zhou (Chemosphere, 2024)

Organophosphate esters (OPEs) pollution characteristics, bioaccumulation and human consumption implication in wild marine organisms from the Yellow River Estuary, China - Jianing Lin; Xinshu Ding; Jinzeng Gu; Lutao Zhang; Jinyu Chao; Heng Zhang; Song Feng; Changsheng Guo; Jian Xu; Zhenhui Gao (Marine Pollution Bulletin, 2024)

Tenascin can inhibit apoptosis induced by copper in silver pomfret (Pampus argenteus) - Jiabao Hu; Youyi Zhang; Yuanbo Li; Weiwei Gu; Zukang Feng; Kaiheng Yan; Man Zhang; Yaya Li; Rongyue Zheng; Shanliang Xu; Yajun Wang; Xiaojun Yan (Aquaculture, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Fenitrothion induces glucose metabolism disorders in rat liver BRL cells by inhibiting AMPKα and IRS1/PI3K/AKT signaling pathway - Yuchao Guo; Dandan Gu; Emmanuel Sunday Okeke; Weiwei Feng; Yao Chen; Guanghua Mao; Liuqing Yang; Xiangyang Wu; Ting Zhao (Pesticide Biochemistry and Physiology, 2024)

SedaDNA reveals mid-to late Holocene aquatic plant and algae changes in Luanhaizi Lake on the Tibetan Plateau - Xu Han; Lianfang Feng; Naimeng Zhang; Shihua Hu; Zhengquan Gu; Xiaozhong Huang; Xiaoyan Yang; Fahu Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Barium isotope variation during fluid–rock interaction at forearc depths: Evidence from high-pressure fluid–metasomatized rocks in the Eastern Alps - Xue-Li Li; Yi-Xiang Chen; Attila Demény; Xiao-Feng Gu; Jia-Wei Xiong; Fang Huang; Hans-Peter Schertl (Lithos, 2024)

First report on liquid crystal monomers in tree barks surrounding a display manufacturer: Insights for atmospheric transport and establishment of priority list - Jiong-Feng Xie; Jia-Yi Gu; Liang-Zhong Li; Ying Guo; Liang-Ying Liu (Journal of Hazardous Materials, 2024)

Emission characteristics of lead and particulate matter from lead and zinc smelters in China - Jiawei Zhang; Xiaohui Sun; Qingru Wu; Jianguo Deng; Zhijian Li; Minneng Wen; Liwen Xu; Yongzheng Gu; Tao Han; Lei Feng; Lei Duan (Journal of Hazardous Materials, 2024)

Straw removal reduces Cd availability and rice Cd accumulation in Cd-contaminated paddy soil: Cd fraction, soil microorganism structure and porewater DOC and Cd - Hang Zhou; Zi-Yu Wang; Chang Li; Hai-Wei Yuan; Lu Hu; Peng Zeng; Wen-Tao Yang; Bo-Han Liao; Jiao-Feng Gu (Journal of Hazardous Materials, 2024)

Influence of Chinese herbal plants on greenhouse gas emissions from pig manure composting and fermentation - Ya-jun Duan; Hong-sheng Wu; Guang-yao Chen; Feng-yi Hu; Yan-hui Li; Zhen-wei Li; Jin-he Chi; Dong-ming Lu; Xiao-ming Gu; Ming-chun Di (International Biodeterioration & Biodegradation, 2024)

A preliminary integrated analysis of regional paleoclimate variations in China over the past ∼ 21 ka - Huayu Lu; Yan Zhao; Xiangdong Yang; Haibing Wu; Cheng Zhao; Jingjing Wang; Xiaoyong Wang; Xueyuan Kuang; Xiaojian Zhang; Chunmei Ma; Fuzhi Lu; Xiayun Xiao; et al. (Global and Planetary Change, 2024)

Constructing direct Z-scheme heterojunction of NiCo-LDH coated with g-C3N4 for boosting photocatalytic H2 evolution - Qinyi Gu; Chujun Feng; Congtian Liu; Jian Rong; Yuzhe Zhang; Xudong Zheng; Zhongyu Li; Song Xu (Fuel, 2024)

CcPTGS2a-like gene-mediated NF-κB/ERK signaling regulation in the common carp (Cyprinus carpio) - Feng Gao; Yanjing Zhao; Yunli Zhang; Yanlong Gu; Chao Pei; Chen Li; Xianghui Kong (Fish & Shellfish Immunology, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

A twin S-scheme CoFe2O4/VCNDA/BiVO4 nanozyme for photo-auto-enzyme-coupled catalytic degradation of carbamazepine - Chujun Feng; Qinyi Gu; Jian Rong; Xudong Zheng; Yuzhe Zhang; Qian Liang; Zhongyu Li; Song Xu (Chemical Engineering Journal, 2024)

Recent progress on the organelle targeted AlEgens for bioimaging and treatment of diseases - Qihang Ding; Yan Luo; Jun Hu; Shuai Zhang; Wenzhe Zhang; Yuanyuan Feng; Kun Qian; Xin Li; Zhen Cheng; Meijia Gu (Chemical Engineering Journal, 2024)

Heat-moisture treatment of freshly harvested high-amylose maize kernels improves its starch thermal stability and enzymatic resistance - Zhonghua Gu; Gaomin Cheng; Xianying Sha; Haochen Wu; Xinwei Wang; Renyong Zhao; Qiang Huang; Yinong Feng; Jihua Tang; Hongxin Jiang (Carbohydrate Polymers, 2024)

Inspection for the desorption effect and mechanism of petroleum from contaminated soil in surfactant solution - Meixia Gu; Xiaoshuang Yin; Xiaoning Feng; Nan Shi; Wei Zhu; Shuhai Guo; Min Li; Bo Wu; Gang Li; Xingshun Cong; Bin Lou; Fushan Wen; et al. (Journal of Soils and Sediments, 2024)

Plasma Deoxycholic Acid Levels are Associated with Hemodynamic and Clinical Outcomes in Acute Pulmonary Embolism Patients - Na Sun; Yi-Qiang Chen; Yan-Sheng Chen; Lei Gao; Run-Wei Deng; Jing Huang; You-Li Fan; Xuan Gao; Bin-Feng Sun; Na-Na Dong; Bo Yu; Xia Gu; et al. (Cardiovascular Toxicology, 2024)

A novel sea-land segmentation network for enhanced coastline extraction using satellite remote sensing images - Jiangfan Feng; Shiyu Wang; Zhujun Gu (Advances in Space Research, 2024)

Design and synthesis of ligustrazine derivatives as potential anti-Alzheimer’s agents - Xu-fei Chen; Shan-shan Li; Yu-jun Bai; Ze-feng Zhao; Ya-jun Bai; Gu Gong; Xi-rui He; Xiao-hui Zheng (Natural Product Research, 2024)

Fate and partition of perfluoroalkyl acids (PFAAs) driven by particles in mangrove ecosystems: Mechanistic insights and environmental implications - Jianwei Dong; Shiya Gu; Meiqi Shang; Yang Cui; Xin Song; Hongbing Wang; Hui Xie; Ranran Feng; Dandan Yan; Yongfen Du; Yang Wang (Journal of Cleaner Production, 2024)

Behavior of geosynthetic-encased stone column reinforced foundation under freeze-thaw cycles - Zi-Ang Gu; Chungsik Yoo; Jian-Feng Chen (Geotextiles and Geomembranes, 2024)

Transcriptome-based network analysis reveals hub immune genes and pathways of hepatopancreas against LPS in Amphioctopus fangsiao - Zan Li; Jingjing Gu; Xiaolan Huang; Zhengcai Lu; Yanwei Feng; Xiaohui Xu; Jianmin Yang (Fish & Shellfish Immunology, 2024)

Mechanically strong, healable, and recyclable supramolecular solid–solid phase change materials with high thermal conductivity for thermal energy storage - Hao Zhu; Meijuan Gu; Xinyi Dai; Siyu Feng; Tao Yang; Yijuan Fan; Jingyi Zhang; Dongli Fan; Yuan Liu; Yaqing Lu; Peng Zhu; Hongbin Lu; et al. (Chemical Engineering Journal, 2024)

Facilities pond aquaculture system construction and the ecological economy analyzed - Hao Zhu; Zhao-Jun Gu; Guo-Feng Cheng; Xing-Guo Liu; Rong Tang (Aquacultural Engineering, 2024)

Assessment of co-benefits from on-road vehicle electrification in Suzhou City, China - Feiyue Qian; Cui Da; Chunchen Lu; Xinyu Gu; Junjian Yang; Chaowei Shi; Zhen Feng; Yuanyuan Cheng (Urban Climate, 2024)

Indirect load measurement method and experimental verification of floating offshore wind turbine - Xiangheng Feng; Yonggang Lin; Yajing Gu; Xingchen Zhao; Hongwei Liu; Yong Sun (Ocean Engineering, 2024)

Fluid-Driven Debonding of Cement Interfaces of an Injector Well: A Coupled Thermo–Hydro–Mechanical Approach - Chenwang Gu; Yongcun Feng; Mojgan Hadi Mosleh; Xiaorong Li; Manouchehr Sanei; Jingen Deng (Rock Mechanics and Rock Engineering, 2024)

Abiotic natural attenuation of 1,2,3-trichloropropane by natural magnetite under O2 perturbation - Chunyun Gu; Jiabin Li; Wei Zhou; Jiayi An; Liting Tian; Feng Xiong; Wenbo Fei; Yangfan Feng; Jie Ma (Chemosphere, 2024)

Settling velocity of atmospheric particles in seawater: Based on hydrostatic sedimentation method using video imaging techniques - Shuo Wang; Huiwang Gao; Shijie Jia; Mingliang Gu; Feng Shi; Xiaohong Yao (Marine Pollution Bulletin, 2024)

Hyposalinity stress reduces mussel byssus secretion but does not cause detachment - Wen-Yi Wang; Ji-Yue Ni; Shi-Hui Huang; Qian-Wen Cui; Yu-Qing Wang; Zhong-Qi Gu; Yi-Feng Li (Science of The Total Environment, 2024)

Phase development in steelmaking slags during a gas quenching granulation process - Wen-Feng Gu; Jiang Diao; Li-Yuan Jiang; Hua-Fang Yu; Wen-Feng Tan; Lian Chen; Hong-Yi Li; Bing Xie; Shigeru Ueda (Journal of Environmental Chemical Engineering, 2024)

Early Triassic high-K granitoids and enclaves of the Daheba pluton, West Qinling (China): Implications for relative contributions of crust and mantle - Feng-Hui Zou; M. Santosh; Chang-Qian Ma; Cai-Lai Wu; Jian-Ping Zheng; Fa-Bin Pan; Han-Ming Gu; Li-Huan Deng (Journal of Asian Earth Sciences, 2024)

Dynamic changes of microbiota and metabolite of traditional Hainan dregs vinegar during fermentation based on metagenomics and metabolomics - Xiaohan Yu; Chunhe Gu; Xiaoxue Guo; Ruijia Guo; Lin Zhu; Xinrong Qiu; Jun Chai; Fei Liu; Zhen Feng (Food Chemistry, 2024)

Classification and quantification of adulterants in Alaska pollock based on fourier transform near-infrared spectroscopy with chemometrics - Shijia Feng; Shou Qi; Chen Chen; Imran Mahmood Khan; Qianhui Gu; Yin Zhang; Zhouping Wang (Food Bioscience, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Maximising cotton phosphorus utilisation for zero surplus and high yields: A review of innovative P management strategies - Yi Peng; Weige Huo; Gu Feng (Field Crops Research, 2024)

Dominance by cyanobacteria in the newly formed biofilms on stone monuments under a protective shade at the Beishiku Temple in China - Yong Zhang; Fasi Wu; Ji-Dong Gu; Kun He; Zhou Fang; Xiaobo Liu; Dongpeng He; Xinghua Ding; Jie Li; Zengyang Han; Qi Zhang; Huyuan Feng (Environmental Research, 2024)

Stabilizing high-Ni cathodes with gradient surface Ti-enrichment - Wenchang Zhu; Xiaotian Zhu; Jizhen Qi; Junyi Yao; Yanbin Shen; Guanjian Cheng; Xue Huang; Shiqi Yang; Hao Zhang; Chao-Lung Chiang; Yan-Gu Lin; Jianming Bai; et al. (Chemical Engineering Journal, 2024)

Revealing sulfur-iron coupling mechanism for enhanced autotrophic denitrification in ecological floating beds - Feng Xu; Yuanyuan Peng; Xushun Gu; Shanshan Sun; Anqi Li; Shengbing He (Bioresource Technology, 2024)

Insight Into the Leakage and Degradation Behavior of Polyacrylamide in Cement-Based Materials - Linan Gu; Jingjing Feng (Water, Air, & Soil Pollution, 2024)

Effective harvesting of the microalga Monoraphidium sp. QLY-1: Comparison of different flocculants - Qingming Long; Xueling Chen; Yongjie Feng; Ximeng He; Hong Gu; Taicong Huang; Peng Zhao (Journal of Applied Phycology, 2024)

Research on the three-dimensional spatio-temporal dynamic evolution and kinematic characteristics of loess landslides induced by strong earthquakes - Huajun Tian; Chaoyu Chang; Jingshan Bo; Xuechen Sun; Fan Feng; Tianyu Dai; Wenjia Zhou; Haoyu Li; Jiapei Gu (Bulletin of Engineering Geology and the Environment, 2024)

Differential evolution of territorial space and effects on ecological environment quality in China’s border regions - Guanhai Gu; Bin Wu; Shengquan Lu; Wenzhu Zhang; Yichao Tian; Rucheng Lu; Xiaoling Feng; Wenhui Liao (Journal of Geographical Sciences, 2024)

Three episodes of Triassic volcanism in the Eastern Kunlun Orogen, NW China: constraints for evolution of the Palaeo-Tethys Ocean - Hao-Ran Li; Jian-Feng Qiao; Feng-Yue Sun; Ye Qian; Yan-Zhang Wang; Shahzad Bakht; Hao-Tian Liu; Yan Gu (International Geology Review, 2024)

The spatiotemporal characteristics and driving mechanisms of subsurface marine heatwaves in the Xisha Region - Feng Gao; Cong Liu; Fangguo Zhai; Jinbao Song; Peiliang Li; Yanzhen Gu (Frontiers in Marine Science, 2024)
Under the background of global climate change, Subsurface Marine Heatwaves (SSMHWs) have become a ‘hot-spot’ research due to their significant impacts on marine ecosystems. Temperature data from the ECCO2 for the years 1992 to 2021 is used to research the spatiotemporal characteristics of SSMHWs in the upper 500 m over the Xisha region (110°E to 113°E, 15°N to 18°N). This study indicates that SSMHWs of high intensity occur in the Xisha area, with the vertical maximum intensity at approximately 100 m. These events exhibit significant seasonal variations, with the highest intensity occurring in May. The intensity of SSMHW in the analysis region varies interannually. SSMHWs have intensified at a rate of 1.53°C·Days/Year and tend to shift to deeper water over the past three decades. A block-based method for SSMHW identification is proposed, in order to take the vertical extent of the event in consideration. By analyzing the eight most intense events based on spatial cumulative intensity, it suggested that warm mesoscale eddies may play an important role on the spatial distribution of the SSMHWs. Statistical analysis shows that the intensity and coverage of the warm mesoscale eddy in the Xisha zone may influence the intensity and evolution of the SSMHWs. Additionally, only 18.27% of SSMHW events occur with apparent surface marine heatwave signals. These findings are vital for uncovering SSMHW dynamics in the Xisha area, and are important for future monitoring, early warnings and marine conservation.

PcLGBP, a pattern recognition receptor from Procambarus clarkii confers broad-spectrum disease resistance by activating ProPO system and AMPs related pathways - Lichao Ren; Mingcong Liao; Ruixue Hu; Guangpeng Feng; Nan Chen; Zemao Gu (Aquaculture, 2024)

Differential susceptibility of BRL cells with/without insulin resistance and the role of endoplasmic reticulum stress signaling pathway in response to acrylamide-exposure toxicity effects in vitro - Yuchao Guo; Houlin Mao; Danni Gong; Nuo Zhang; Dandan Gu; Emmanuel Sunday Okeke; Weiwei Feng; Yao Chen; Guanghua Mao; Ting Zhao; Liuqing Yang (Toxicology, 2024)

Smart Breeding Platform: A web-based tool for high-throughput population genetics, phenomics, and genomic selection - Huihui Li; Xin Li; Peng Zhang; Yingwei Feng; Junri Mi; Shang Gao; Lele Sheng; Mohsin Ali; Zikun Yang; Liang Li; Wei Fang; Wensheng Wang; et al. (Molecular Plant, 2024)

Operando gas- and particle-phase measurements of combustion cigarette smoke aerosols by vacuum ultraviolet photoionization mass spectrometry - Feng Zhao; Zuoying Wen; Xuejun Gu; Weijun Zhang; Xiaofeng Tang (Journal of Aerosol Science, 2024)

NiCoP cocatalyst modified g-C3N4 as ohmic junction photocatalyst for efficient degradation of tetracycline under visible light - Qinyi Gu; Chujun Feng; Jian Rong; Yuzhe Zhang; Xudong Zheng; Jinfeng Mei; Zhongyu Li; Song Xu (Environmental Research, 2024)

Study on non-isothermal reaction and sintering kinetics of Ca(OH)2 particle cluster dehydration with temperature distribution modification - Yishi Gu; Yuxiang Cheng; Zhongjie Shen; Feng Lv; Dayang Wan; Yongchuan Gao; Yuezhang Duan; Jianliang Xu; Qinfeng Liang; Xiaolei Guo; Haifeng Liu (Chemical Engineering Journal, 2024)

Reducing the Effect of Incorrect Lithology Labels on the Training of Deep Neural Networks for Lithology Identification - Xiaoyue Feng; Hongmei Luo; Changjiang Wang; Hanming Gu (Mathematical Geosciences, 2024)

Time-dependent neutron transport method based on three-dimensional method of characteristics - Qufei Song; Chang Zhang; Yiwei Wu; Kuaiyuan Feng; Hui Guo; Hanyang Gu (Annals of Nuclear Energy, 2024)

Identifying the predictors of mycorrhizal response under multiple fertilization regimes - Zefeng Qin; Yinghao Tian; Wenying Hao; Junling Zhang; Gu Feng; Peter Christie; Jingping Gai (Agriculture, Ecosystems & Environment, 2024)

Seasonal Characteristics of Forecasting Uncertainties in Surface PM2.5 Concentration Associated with Forecast Lead Time over the Beijing-Tianjin-Hebei Region - Qiuyan Du; Chun Zhao; Jiawang Feng; Zining Yang; Jiamin Xu; Jun Gu; Mingshuai Zhang; Mingyue Xu; Shengfu Lin (Advances in Atmospheric Sciences, 2024)

Universal patterns and differences in graded aggressive calls of greater horseshoe bats from distant populations - Kangkang Zhang; Yanping Yu; Tong Liu; Jianan Ding; Hao Gu; Jiang Feng; Ying Liu (Animal Behaviour, 2024)

Soil pH and carbon quality index regulate the biogeochemical cycle couplings of carbon, nitrogen and phosphorus in the profiles of Isohumosols - Zhuxiu Liu; Haidong Gu; Qin Yao; Feng Jiao; Xiaojing Hu; Junjie Liu; Jian Jin; Xiaobing Liu; Guanghua Wang (Science of The Total Environment, 2024)

Sequential recovery of protein and ammonium from waste sludge and functional metabolism in a combined process of nutrient recovery electro-fermentation (NREF) - Jiayu Gu; Huihui Zhou; Jing Wang; Kun Feng; Guojun Xie; Bingfeng Liu; Defeng Xing (Resources, Conservation and Recycling, 2024)

Hierarchical driving factors of ammonia emissions from cropland in China - Chen Wang; Yinan Feng; Xiangrui Xu; Xiuming Zhang; Hongbin Liu; Jianming Xu; Baojing Gu (Journal of Cleaner Production, 2024)

Analyzing sustainable development in Chinese cities: A focus on land use efficiency in production-living-ecological aspects - Ao Leng; Kan Wang; Jianjun Bai; Na Gu; Ruitao Feng (Journal of Cleaner Production, 2024)

Thermodynamic design and analysis of air-liquefied energy storage combined with LNG regasification system - Qingfeng Jiang; Shiqing Wan; Chongyao Pan; Guozeng Feng; Huaibing Li; Hansheng Feng; Bo Meng; Jiayang Gu; Yunchu Feng (International Journal of Refrigeration, 2024)

Computer vision-based real-time deflection monitoring of complex and sizeable steel structures - Yongqi Huang; Ruoqiang Feng; Changjun Zhong; Xiaoyu Tong; Xinxing Shao; Liuning Gu; Ze Hui (Engineering Structures, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Cruise observation of ambient volatile organic compounds over Hong Kong coastal water - Hao Sun; Dasa Gu; Xin Feng; Zhe Wang; Xiangyunong Cao; Mingyao Sun; Zhi Ning; Penggang Zheng; Yuchen Mai; Zijie Xu; Wai Ming Chan; Xin Li; et al. (Atmospheric Environment, 2024)

Historical and future health burden attributable to PM2.5 exposure in China - Yang Bai; Lei Chen; Zijia Feng; Jia Zhu; Yixuan Gu; Ke Li; Hong Liao (Atmospheric Environment, 2024)

Adding plant metabolites improve plant phosphorus uptake by altering the rhizosphere bacterial community structure - Siji Wang; Shilong Duan; Timothy S. George; Gu Feng; Lin Zhang (Plant and Soil, 2024)

Sevoflurane Exposure Induces Neuronal Cell Ferroptosis Initiated by Increase of Intracellular Hydrogen Peroxide in the Developing Brain via ER Stress ATF3 Activation - Liheng Kang; Meihua Piao; Nan Liu; Wanping Gu; Chunsheng Feng (Molecular Neurobiology, 2024)
Neuronal cell death is acknowledged as the primary pathological basis underlying developmental neurotoxicity in response to sevoflurane exposure, but the exact mechanism remains unclear. Ferroptosis is a form of programmed cell death characterized by iron-dependent lipid peroxidation that is driven by hydrogen peroxide (H 2 O 2 ) and ferrous iron through the Fenton reaction and participates in the pathogenesis of multiple neurological diseases. As stress response factor, activating transcription factor 3 (ATF3) can be activated by the PERK/ATF4 pathway during endoplasmic reticulum (ER) stress, followed by increased intracellular H 2 O 2 , which is involved in regulation of apoptosis, autophagy, and ferroptosis. Here, we investigated whether ferroptosis and ATF3 activation were implicated in sevoflurane-induced neuronal cell death in the developing brain. The results showed that sevoflurane exposure induced neuronal death as a result of iron-dependent lipid peroxidation damage secondary to H 2 O 2 accumulation and ferrous iron increase, which was consistent with the criteria for ferroptosis. Furthermore, we observed that increases in iron and H 2 O 2 induced by sevoflurane exposure were associated with the upregulation and nuclear translocation of ATF3 in response to ER stress. Knockdown of ATF3 expression alleviated iron-dependent lipid peroxidation, which prevented sevoflurane-induced neuronal ferroptosis. Mechanistically, ATF3 promoted sevoflurane-induced H 2 O 2 accumulation by activating NOX4 and suppressing catalase, GPX4, and SLC7A11 expression. Additionally, an increase in H 2 O 2 was accompanied by the upregulation of TFR and TF and downregulation of FPN, which linked iron overload to ferroptosis induced by sevoflurane. Taken together, our results demonstrated that ER stress-mediated ATF3 activation contributed to sevoflurane-induced neuronal ferroptosis via H 2 O 2 accumulation and the resultant iron overload.

CO2 utilization for methanol production: a review on the safety concerns and countermeasures - Lele Feng; Yifan Gu; Maifan Dong; Jie Liu; Liangliang Jiang; Yuxin Wu (Environmental Science and Pollution Research, 2024)

Effect of plasma exosome lncRNA on isoproterenol hydrochloride-induced cardiotoxicity in rats - Liyuan Zhao; Lei Shi; Zixuan Yang; Minhui Zheng; Zhimin Sun; Luyao Sun; Mengyun Gu; Xin Song; Gang Liu; Feng Miao; Ming Wang; Shaoqiu Zheng; et al. (Toxicology and Applied Pharmacology, 2024)

The pig intestinal phageome is an important reservoir and transfer vector for virulence genes - Yalu Ji; Hengyu Xi; Chong Chen; Changjiang Sun; Xin Feng; Liancheng Lei; Wenyu Han; Jingmin Gu (Science of The Total Environment, 2024)

Significance of phosphate adsorbed on the cellular surface as a storage pool and its regulation in marine microalgae - Xian-Yang Zhang; Zhuo-Fan Li; Hai-Feng Gu; Ai-Qin Han; Feng-Xian Han; Lin-Jian Ou (Marine Environmental Research, 2024)

Non-targeted metabolomics identifies biomarkers in milk with high and low milk fat percentage - Xiaofang Feng; Ruoshuang Ma; Ying Wang; Lijia Tong; Wan Wen; Tong Mu; Jia Tian; Baojun Yu; Yaling Gu; Juan Zhang (Food Research International, 2024)

A rigid-flexible integrated polyester with bis-phosphaphenanthrene pendants towards simultaneously flame-retarded and toughened epoxy resins with multifunctionalities - Yan-Fang Xiao; Xiao-Feng Liu; Feng-Ming He; Song Gu; Yu-Zhong Wang; Li Chen (Chemical Engineering Journal, 2024)

Mechanical interlocking induced emission in two-dimensional covalent organic frameworks - Ruo-Meng Zhu; Wang-Kang Han; Yong Liu; Jia-Xing Fu; Jing-Dong Feng; Jinfang Zhang; Huan Pang; Zhi-Guo Gu (Chemical Engineering Journal, 2024)

Identification and molecular mapping of a major gene conferring resistance to Phytophthora sansomeana in soybean ‘Colfax’ - Feng Lin; Muhammad Salman; Zhanguo Zhang; Austin G. McCoy; Wenlong Li; Raju Thada Magar; Drew Mitchell; Meixia Zhao; Cuihua Gu; Martin I. Chilvers; Dechun Wang (Theoretical and Applied Genetics, 2024)

Carotenoid fates in plant foods: Chemical changes from farm to table and nutrition - Yanqi Wang; Feilong Yang; Ting Liu; Chengying Zhao; Fengying Gu; Hengjun Du; Feng Wang; Jinkai Zheng; Hang Xiao (Critical Reviews in Food Science and Nutrition, 2024)

Ascorbic acid reduction pretreatment enhancing metal regulation to improve methane production from anaerobic digestion of waste activated sludge - Siqi Li; Yu Zhang; Miao Liu; Zexuan Du; Jinze Li; Li Gu; Linji Xu; Feng Liu (Science of The Total Environment, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Evaluation of the fate of wastewater effluent organic matter in receiving water: Effect of sequential photochemical and biological processes - Lei Zheng; Feng Xiao; Xinyi Zhang; Yang Deng; Shansheng Mo; Zhongli Liu; Xin Gu; Norbert Hertkorn; Gregory V. Korshin; Mingquan Yan (Journal of Hazardous Materials, 2024)

Quasi-closed-loop approach for facile and environmentally friendly red mud reutilization as advanced Li-ion anode material - Dawei Lan; Yixun Gu; Xianglong Chen; Man Mo; Zhijie Fang; Panyu Xiong; Weichi Ye; Gangli Zhao; Tianshi Xiong; Minfeng Huang; Weijian Li; Haiqing Zhan; et al. (Journal of Cleaner Production, 2024)

Centrifuge investigation on behavior of geosynthetic-encased stone column supported embankment under freeze-thaw cycles - Zi-Ang Gu; Fu-Jun Niu; Jian-Feng Chen; Chungsik Yoo (Geotextiles and Geomembranes, 2024)

Selecting autochthonous lactic acid bacteria for co-inoculation in Chinese bayberry wine production: Stress response, starter cultures application and volatilomic study - Qing Gu; Yixian Li; Ying Lou; Yan Zhao; Xujie Feng; Ping Li; Oskar Laaksonen; Baoru Yang; Vittorio Capozzi; Shuxun Liu (Food Research International, 2024)

Integrating shotgun metagenomics and metabolomics to elucidate the dynamics of microbial communities and metabolites in fine flavor cocoa fermentation in Hainan - Haode Chang; Chunhe Gu; Mengrui Wang; Ziqing Chang; Junping Zhou; Mingzhe Yue; Junxia Chen; Xiaowei Qin; Zhen Feng (Food Research International, 2024)

Insight into the effects of different ripeness levels on the quality and flavor chemistry of Noni fruit (Morinda citrifolia L.) - Xiaoai Chen; Chunhe Gu; Kexue Zhu; Fei Xu; Zhen Feng; Yanjun Zhang (Food Chemistry, 2024)

Sustainable recycling of spent ternary lithium-ion batteries via an environmentally friendly process: Selective recovery of lithium and non-hazardous upcycling of residue - Jianxing Liang; Rongcan Chen; Jia-nan Gu; Jingdong Li; Yixin Xue; Feng Shi; Bingji Huang; Mingming Guo; Jinping Jia; Kan Li; Tonghua Sun (Chemical Engineering Journal, 2024)

Mechanism of sulfur-guided CO2 selective hydrogenation through modulation of surface intermediate over Ni/ZrO2 catalysts - Yunhao Zang; Ziyi Zhang; Yan Wang; Jiangying Qu; Feng Gao; Jianfeng Gu; Xuetan Lin; Taipeng Wei (Chemical Engineering Journal, 2024)

An analysis of lncRNAs related to fiber quality and the discovery of their target genes in a Gossypium hirsutum line with Gossypium mustelinum introgression - Baohua Wang; Meijun Ji; Hui Fang; Haijing Gu; Teame Gereziher Mehari; Jinlei Han; Wenxiang Feng; Xuehan Huo; Jingxia Zhang; Yu Chen; Jun Zhang; Allah Ditta; et al. (Theoretical and Applied Genetics, 2024)

Spatial and temporal variability and risk assessment of organophosphate esters in seawater and sediments of the Yangtze River estuary - Jianing Lin; Lingzhi Liao; Ting Sun; Jinzeng Gu; Xiaoxian Yang; Lutao Zhang; Zhenhui Gao; Song Feng (Marine Pollution Bulletin, 2024)

Tartaric acid coupled with gibberellin improves remediation efficiency and ensures safe production of crops: A new strategy for phytoremediation - Teng-yue Yuan; Da-juan Wan; Wen-jun Yang; Jiao-feng Gu; Hang Zhou; Peng Zeng; Bo-han Liao (Science of The Total Environment, 2024)

Critical influence of vegetation response to rising CO2 on runoff changes - Cuiyan Liu; Shuyun Feng; Qiang Zhang; Jiaxin Hu; Ning Ma; Hui Ci; Dongdong Kong; Xihui Gu (Science of The Total Environment, 2024)

Photochemical behavior of dissolved organic matter derived from Alternanthera philoxeroides hydrochar: Insights from molecular transformation and photochemically reactive intermediates - Xincai Gu; Bingfa Chen; Hong Liu; Yanfang Feng; Bingyu Wang; Shiying He; Muhua Feng; Guojun Pan; Shiqun Han (Journal of Hazardous Materials, 2024)

Characterization of a Bacillus velezensis strain as a potential biocontrol agent against soft rot of eggplant fruits - Xiaoyun Zhang; Yu Xin; Junyi Wang; Solairaj Dhanasekaran; Qingrong Yue; Faping Feng; Xiangyu Gu; Bo Li; Lina Zhao; Hongyin Zhang (International Journal of Food Microbiology, 2024)

Creating a monetization-SolVES model to visualize the cultural ecosystem services for promoting landscape conservation - Xiaoqian Shi; Xiaoqing Zhao; Junwei Pu; Zexian Gu; Qiaoqiao Zhao; Yan Feng; Shijie Zhou (Journal for Nature Conservation, 2024)

Roles of alcohol group in functionalized carbon nitride for photocatalytic oxidation - Shuting Feng; Xincheng Li; Xianmo Gu; Ruiyi Wang; Yunwei Wang; Zhanfeng Zheng (Fuel, 2024)

Isolation and characterization of Bacillus cereus bacteriophage DZ1 and its application in foods - Zhichao Huang; Xiaoming Yuan; Zhenjun Zhu; Ying Feng; Na Li; Shubo Yu; Chun Li; Bo Chen; Shi Wu; Qihui Gu; Jumei Zhang; Juan Wang; et al. (Food Chemistry, 2024)

Advances of designing effective and functional electrolyte system for high-stability aqueous Zn ion battery - Lanlan Fan; Xiyun Hu; Yimei Jiao; Lei Cao; Shixian Xiong; Feng Gu; Shufen Wang (Chemical Engineering Journal, 2024)

Understanding changes in heat waves, droughts, and compound events in Yangtze River Valley and the corresponding atmospheric circulation patterns - Zhonghua Qian; Yingxiao Sun; Qianrong Ma; Yu Gu; Taichen Feng; Guolin Feng (Climate Dynamics, 2024)
Heat waves, droughts, and compound drought and heat waves (CDHWs) have received extensive attention because of their disastrous impacts on agriculture, ecosystems, human health, and society. Here, we computed the heat wave magnitude index (HWMI), drought magnitude index (DMI), and compound drought and heat wave magnitude index (CDHMI) for Yangtze River Valley (YRV) from July to August during 1961–2022. We compared the large-scale atmospheric circulation characteristics of different extreme events based on these indexes. The results show that the positive center with sink motion in East Asia provides a favorable circulation background for heat wave events. Drought events are mainly affected by the zonal wave train dominated by a significant negative anomaly in Siberia and a high-pressure anomaly upstream, and a anticyclonic water vapor with strong divergence over the Yangtze River basin. During CDHW events, both anomalous systems that affect heat waves and droughts appear and strengthen simultaneously. Specifically, in the middle and upper troposphere, the positive height anomaly center in YRV expands abnormally, and the “+–+” wave train over the northern 50° N region of East Asia becomes more obvious. Therefore, the positive anomaly and water vapor anomaly brought by the two circulation patterns at different latitudes are superimposed over the YRV, leading to severe CDHWs. At the same time, the warm positive eddy center and cold negative eddy center in high latitudes exhibit more stable positive pressure features, which are conducive to the persistent development and strengthening of CDHWs. In addition, the anomalous warm sea surface temperature in western Pacific moderating the favorable circulation patterns may also promote the occurrence of CDHWs in the YRV during the same period.

Physiological tolerance of black locust (Robinia pseudoacacia L.) and changes of rhizospheric bacterial communities in response to Cd and Pb in the contaminated soil - Xu-Feng Luo; Meng-Yu Liu; Zi-Xi Tian; Yue Xiao; Peng Zeng; Zi-Yu Han; Hang Zhou; Jiao-Feng Gu; Bo-Han Liao (Environmental Science and Pollution Research, 2023)

Long-term fertilisation management changes bacterial phoD and gcd gene communities and abundances in the rhizosphere of cotton (Gossypium hirsutum L.) grown in a grey desert soil - Fei Wang; Xin Wei; Linqi Zhang; Gu Feng (Rhizosphere, 2023)

Effects of different diets on the growth and development of young silkworms - Yuanfei Wang; Qilong Shu; Haoyi Gu; Piao Feng; Minli Dai; Qingyu Zhu; Wei Liu; Yan Dai; Fanchi Li; Bing Li (Journal of Asia-Pacific Entomology, 2023)

Comparison of anthocyanin and volatile organic compounds in juices and fruit wines made from blood oranges (Citrus sinensis L. Osbeck) at different maturity stages - Shuxun Liu; Ying Lou; Yixian Li; Yan Zhao; Xujie Feng; Vittorio Capozzi; Oskar Laaksonen; Baoru Yang; Ping Li; Qing Gu (Food Bioscience, 2023)

Transcriptomic analysis revealed the dynamic response mechanism to acute ammonia exposure in the ivory shell, Babylonia areolata - Xin Hong; Jie Qin; Deng Fu; Yi Yang; Aimin Wang; Zhifeng Gu; Feng Yu; Chunsheng Liu (Fish & Shellfish Immunology, 2023)

Manure application enhanced cotton yield by facilitating microbially mediated P bioavailability - Shaomin Zhang; Weige Huo; Baidengsha Maimaitiaili; Yi Peng; Gu Feng (Field Crops Research, 2023)

Insight into personal exposure characteristics and health effects of PM2.5 and PM0.25-bound PAHs and their derivatives with different heating ways in the Fenwei Plain, China - Yunxuan Gu; Hongmei Xu; Rong Feng; Bin Zhang; Min Gao; Jian Sun; Zhenxing Shen; Linli Qu; Steven Sai Hang Ho; Junji Cao (Environmental Pollution, 2023)

Degradation of norfloxacin by sulfur-doped iron-cobalt oxides activated perodisulfate: Synergism between free radicals and singlet oxygen - Luwei Zhai; Fengchun Li; Yuhai He; Xia Chen; Xuan Zhang; Yawei Gu; Chongqing Xu; Guihuan Yan; Xiaojing Feng; Wenqiang Jiang (Chemical Engineering Journal, 2023)

Ti3C2Tx quantum dot-modified Ti3C2Tx nanosheets freestanding films for flexible solid-state pseudocapacitors - Ping Liu; Handan Liu; Tengfei Zhang; Long Chen; Wen Guo; Tiantian Gu; Feng Yu; Yanyan Liu; Gang Wang (Chemical Engineering Journal, 2023)

Investigation of the multi-year trend of surface ozone and ozone-precursor relationship in Hong Kong - Xin Feng; Jia Guo; Zhe Wang; Dasa Gu; Kin-Fai Ho; Yi Chen; Kezheng Liao; Vincent T.F. Cheung; Peter K.K. Louie; Kenneth K.M. Leung; Jian Zhen Yu; Jimmy C.H. Fung; et al. (Atmospheric Environment, 2023)

Effects of PM2.5 emissions from household fuel combustion on biomarkers and pulmonary function in rural areas of Fenwei Plain, China - Rong Feng; Hongmei Xu; Hongwei Lu; Bei Han; Yue Cheng; Yunxuan Gu; Jian Sun; Liu Yang; Zhenxing Shen; Junji Cao (Atmospheric Pollution Research, 2023)

Pathological observation and transcriptomic analysis of thymus injury in PRRSV-infected piglets - Naying Su; Zhengdan Lin; Xi Liu; Xiuxiu Sun; Xinxin Jin; Helong Feng; Cunlin Zhan; Xueying Hu; Changqin Gu; Wanpo Zhang; Guofu Cheng (Veterinary Research Communications, 2023)
The thymus, the central immune organ in mammals, plays an important role in immune defense. Porcine reproductive and respiratory syndrome virus (PRRSV) infection in piglets can cause thymus injury and immunosuppression. However, the mechanisms of thymus injury remain unknown. This study was aimed at investigating the specific manifestations of thymus injury through the construction of a PRRSV-infected piglet model and histopathological observation. In this study, fourteen 40-day-old PRRSV-free piglets were randomly divided into two groups, eleven of which were intramuscularly injected with 3 mL of PRRSV WUH3 virus suspension (10 6 PFU /mL) in the infection group, and three of which were sham-inoculated with 3 mL of RPMI-1640 medium in the control group. Clinical necropsy and samples collection were performed on day 8 after artificial infection. With the Illumina platform, the transcriptomes of piglet thymus tissues from infected and control piglets were sequenced to explore the relationships of differentially expressed genes (DEGs) and signaling pathways with thymus injury. The immune organs of PRRSV-infected piglets were severely damaged. The histopathological findings in the thymus indicated that PRRSV infection was associated with a large decrease in lymphocytes, cell necrosis and cell apoptosis; an increase in blood vessels and macrophages; thymic corpuscle hyperplasia; and interstitial widening of the thymic lobules. The transcriptomic analysis results revealed that the Gene Ontology functions of DEGs were enriched primarily in biological processes such as angiogenesis, regulation of angiogenesis and positive regulation of cell migration. Moreover, greater numbers of blood vessels and macrophages were observed in the thymus in PRRSV-infected than control piglets. KEGG pathway enrichment analysis revealed that the DEGs were significantly enriched in the Toll-like receptor signaling pathway, chemokine signaling pathway, IL-17 signaling pathway and TNF signaling pathway. The expression of TLR8, IRF5, the chemokines CCL2, CCL3L1 and CCL5; and their receptors CCR1, CCR2 and CCR5 was significantly up-regulated in PRRSV infection, thus suggesting that these cytokines were associated with the pathological processes of thymus injury.

Vav2 promotes ductus arteriosus anatomic closure via the remodeling of smooth muscle cells by Rac1 activation - Yinghui Chen; Yizhuo Wu; Weiqi Feng; Xueyang Luo; Bing Xiao; Xiaowei Ding; Yongjia Gu; Yanan Lu; Yu Yu (Journal of Molecular Medicine, 2023)

Telluribacter roseus sp. nov., Isolated from the Kumtag Desert Soil - Chu-Ying Feng; Jia-Rui Han; Chun-Yan Lu; Li Gu; Shuai Li; Wen-Hui Lian; Lei Dong; Wen-Jun Li (Current Microbiology, 2023)

Multi-objective optimization of method of characteristics parameters based on genetic algorithm - Qufei Song; Chang Zhang; Yiwei Wu; Kuaiyuan Feng; Hui Guo; Hanyang Gu (Annals of Nuclear Energy, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

A position-aware attention network with progressive detailing for land use semantic segmentation of Remote Sensing images - Jiangfan Feng; Wei Zheng; Zhujun Gu; Dongen Guo; Rui Qin (International Journal of Remote Sensing, 2023)

Insight into the mechanisms of neuroendocrine toxicity induced by 6:2FTCA via thyroid hormone disruption - Linlin Wu; Jie Gu; Xinjie Duan; Feng Ge; Heyong Ye; Lingcan Kong; Wenwei Liu; Rong Gao; Jiandong Jiao; Huanhuan Chen; Guixiang Ji (Chemosphere, 2023)

Effects of xylanase on starch isolation and functional properties of waxy wheat flour - Zhonghua Gu; Renyong Zhao; Junwei Feng; Hongxin Jiang (Journal of Cereal Science, 2023)

Mechanisms of lead-containing pigment discoloration caused by Naumannella cuiyingiana AFT2T isolated from 1500 years tomb wall painting of China - Shuwei Pei; Fasi Wu; Yuxin Chen; Wenxia Ma; Dongpeng He; Qi Zhang; Ji-Dong Gu; Wanfu Wang; Tian Tian; Huyuan Feng (International Biodeterioration & Biodegradation, 2023)

First-principles calculations of equilibrium barium isotope fractionation among silicate minerals - Xiao Zi-Cong; Wang Wen-Zhong; Gu Xiao-Feng; Deng Geng-Xin; Wu Zhong-Qing; Nan Xiao-Yun; Huang Fang (Geochimica et Cosmochimica Acta, 2023)

Experimental studies on improving progressive collapse resistance of RC beam–column assemblies using kinked steel plates - Xing-Ju Yang; Feng Lin; Xiang-Lin Gu (Engineering Structures, 2023)

Corrosion-induced moment redistributions of RC frame structures under service loads - Chao Jiang; Deng-Feng Shang; Xiang-Lin Gu; Hong-Fei Zhang; Wei-Ping Zhang (Engineering Structures, 2023)

Dynamic shakedown limits of the pavement on saturated subgrade subjected to traffic rolling-sliding loading - Hao Lei; Jia-Feng Zhang; Jian-Gu Qian; Yu-Chen Dai; Jun Shen (Computers and Geotechnics, 2023)

Bio-based phytic acid-induced polypyrrole/silver nanowires coating towards multifunctional nylon/cotton blend fabrics - Jian Liu; Peng Qi; Jingfan Zhang; Xiaodong Liu; Feng Chen; Hongfei Li; Xiaoyu Gu; Jun Sun; Sheng Zhang (Chemical Engineering Journal, 2023)

Rational construction of edge-grafted g-C3N4 via cross-linking aromatic compounds with C F bonds for efficient photocatalytic H2 evolution - Yongpan Gu; Haoqiang Feng; Jindi Zhao; Mengling Cui; Yike Li; Zhongjun Li (Chemical Engineering Journal, 2023)

Soil potassium regulation by initial K level and acidification degree when subjected to liming: A meta-analysis and long-term field experiment - Tianfu Han; Dongchu Li; Kailou Liu; Jing Huang; Lu Zhang; Shujun Liu; Asad Shah; Lisheng Liu; Gu Feng; Huimin Zhang (CATENA, 2023)

Source apportionment of heavy metals in PM2.5 samples and effects of heavy metals on hypertension among schoolchildren in Tianjin - Jingwei Zhang; Lihong Feng; Zhonghui Liu; Lu Chen; Qing Gu (Environmental Geochemistry and Health, 2023)

Microbial and chemical fertilizers for restoring degraded alpine grassland - Songsong Gu; Xueli Zhou; Hao Yu; Huilin Yan; Yingcheng Wang; Yue Liu; Zhihui Wang; Kai Feng; Xiongfeng Du; Guangxin Lu; Ye Deng (Biology and Fertility of Soils, 2023)

Placing seeds with the embryo pointed down improves deep root growth in winter wheat under soil compaction stress - Baoru Li; Weishuang Feng; Shiming Duan; Huijie Gu; Jun Ji; Xiuwei Liu (Plant and Soil, 2023)

Could continuous rice cropping increase soil fertility and rice productivity by rice straw carbonized utilization in cold areas? — A 6-year field-located trial - Di Wu; Zhibo Feng; Wenqi Gu; Yuning Wang; Zifan Liu; Wenjia Wang; Yuxue Zhang; Weiming Zhang; Wenfu Chen (Environmental Science and Pollution Research, 2023)

Semantic segmentation of remote sensing images combined with attention mechanism and feature enhancement U-Net - Jionghui Jiang; Xi’an Feng; QiLei Ye; Zhongyi Hu; Zhiyang Gu; Hui Huang (International Journal of Remote Sensing, 2023)

Kinetics and mechanism of triclocarban degradation by the chlorination process: Theoretical calculation and experimental verification - Tao Peng; Chao Xu; Bin Yang; Feng-Long Gu; Guang-Guo Ying (Chemosphere, 2023)

Electrochemical oxidation technique to pharmaceutical pollutants removal - Chunying Wu; Ji Ge; Feng Gu; Lu Bai (Chemosphere, 2023)

Metagenomic and metaproteomic insights into the microbiome and the key geobiochemical potentials on the sandstone of rock-hewn Beishiku Temple in Northwest China - Fasi Wu; Xinghua Ding; Yong Zhang; Ji-Dong Gu; Xiaobo Liu; Qinglin Guo; Jie Li; Huyuan Feng (Science of The Total Environment, 2023)

Preliminary stability design method and hybrid experimental validation of a floating platform for 10 MW wind turbine - Xiangheng Feng; Yonggang Lin; Yajing Gu; Danyang Li; Bowen Chen; Hongwei Liu; Yong Sun (Ocean Engineering, 2023)

Source apportionment of consumed volatile organic compounds in the atmosphere - Yao Gu; Baoshuang Liu; He Meng; Shaojie Song; Qili Dai; Laiyuan Shi; Yinchang Feng; Philip K. Hopke (Journal of Hazardous Materials, 2023)

Testing of a novel multi-branch horizontal well remediation technology for in situ remediation of contaminated soil and groundwater - Chao Feng; Lingrong Kong; Yu Wang; Ailiang Gu; Xuan Huang (Journal of Environmental Management, 2023)

Extended construction strategies of Ag3PO4-based heterojunction photocatalysts for robust environmental applications - Cheng Zhang; Chuchu Feng; Junwei Yuan; Zhiyun Wang; Yanan Wang; Shiyuan Zhou; Peiyang Gu; Yang Li (Journal of Environmental Chemical Engineering, 2023)

Quaternary evolution of the Dunhuang paleolake and its controlling factors in the northeastern Tibetan Plateau - Jianlei Zheng; Jinjiang Zhang; Bo Zhang; Yang Wang; Daxiang Gu; Lin Feng; Haibin Wang (Geomorphology, 2023)

Dual-mode immunochromatographic assay based on dendritic gold nanoparticles with superior fluorescence quenching for ultrasensitive detection of E. coli O157:H7 - Yanna Shao; Zhengzheng Wang; Jihang Xie; Zhenjun Zhu; Ying Feng; Shubo Yu; Liang Xue; Shi Wu; Qihui Gu; Jumei Zhang; Qingping Wu; Juan Wang; et al. (Food Chemistry, 2023)

Cheese-like Ti3C2 for enhanced hydrogen storage - Chen Gu; Hai-Guang Gao; Peng Tan; Ya-Na Liu; Xiao-Qin Liu; Xiao-Hui Hu; Yun-Feng Zhu; Lin-Bing Sun (Chemical Engineering Journal, 2023)

The mechanisms of exosomes in diabetic foot ulcers healing: a detailed review - Lei Yu; Jianxin Qin; Jiajun Xing; Zihao Dai; Tingting Zhang; Feng Wang; Jin Zhou; Xiaobai Zhang; Xia Chen; Yunjuan Gu (Journal of Molecular Medicine, 2023)

OAMSFNet: Orientation-Aware and Multi-Scale Feature Fusion Network for shadow detection in remote sensing images via pseudo shadow - Jiangfan Feng; Juntao Liu; Zhujun Gu; Wei Zheng (International Journal of Remote Sensing, 2023)

Improving the hygroscopicity and flame retardancy of polyamide 6 fabrics by surface coating with β-FeOOH and sulfamic acid - Jian Liu; Peng Qi; Feng Chen; Xiaobei Li; Jingfan Zhang; Lijun Qian; Xiaoyu Gu; Jun Sun; Sheng Zhang (Chemosphere, 2023)

PbrWRKY70 increases pear (Pyrus bretschneideri Rehd) black spot disease tolerance by negatively regulating ethylene synthesis via PbrERF1B-2 - Caihua Xing; Qiming Chen; Qinghai Qiao; Shenao Gu; Xiangyu Cheng; Huizhen Dong; Likun Lin; Feng Zhang; Chenyang Han; Zan Zhang; Hao Yin; Kaijie Qi; et al. (Plant Science, 2023)

Distributed optimization of networked marine surface vehicles: A fixed-time estimator-based approach - Qian Chen; Ming-Feng Ge; Chang-Duo Liang; Zhi-Wei Gu; Jie Liu (Ocean Engineering, 2023)

Plastispheres as hotspots of microbially-driven methylmercury production in paddy soils - Yun-Yun Hao; Hui-Wen Liu; Jiating Zhao; Jiao Feng; Xiuli Hao; Qiaoyun Huang; Baohua Gu; Yu-Rong Liu (Journal of Hazardous Materials, 2023)

Precooking treatments affect the sensory and tensile properties of autoclaved recooked noodles via moisture distribution and protein structure - Xin Guo; Fengying Gu; Yang Li; Qiaozhen Zhang; Runrun Hu; Bo Jiao; Feng Wang; Qiang Wang (Food Chemistry, 2023)

Effects of soil solarization combined with manure-amended on soil ARGs and microbial communities during summer fallow - Xiaojuan Wang; Li Zhang; Jie Gu; Yucheng Feng; Kai He; Haihong Jiang (Environmental Pollution, 2023)

Microenvironmental corrosion and hydrolysis induced two-dimensional heterojunction of copper oxide@ferriferrous oxide for efficient electrochemical nitrate reduction to ammonia - Jingsha Li; Hui Liu; Feng Du; Lvfei Liu; Yunjie Gu; Changming Li; Chunxian Guo; Haiyan Wang (Chemical Engineering Journal, 2023)

Identification and prevalence investigation of cyathocotylid trematode (Trematoda: Digenea: Cyathocotylidae) in Carassius auratus in Wuhu, China - Feng Jiang; Wanyu Zhang; Yang Pan; Xudong Yu; Jiacheng Cao; Ningning Du; Mengyi Zhu; Shengli Gu; Xiaodong Zhan (Veterinary Research Communications, 2023)

Expression and functional analysis of ace1 and ace2 reveal their differential roles in larval growth and insecticide sensitivity in Spodoptera frugiperda (J. E. Smith, 1797) - Jie Gao; Li-Feng Gong; Huan-Huan Wang; Rui Zhao; Xing Xiao; Xin-Yao Tian; Bo Li; Pei Liang; Xi-Wu Gao; Shao-Hua Gu (Journal of Pest Science, 2023)

CLASRP oncogene as a novel target for colorectal cancer - Quan Gu; Jianzhong Wu; Heng Xu; Haixia Cao; Junying Zhang; Changwen Jing; Zhuo Wang; Mengjie Du; Rong Ma; Jifeng Feng (Functional & Integrative Genomics, 2023)
Clk4-associated serine/arginine-rich protein ( CLASRP ), an alternative splicing regulator, may be involved in the development and progression of cancer by regulating the activity of the CDC-like kinase (Clk) family. This study explored the biological function of CLASRP in colorectal cancer (CRC). The expression of CLASRP , which is associated with clinicopathological features, was analysed in CRC tissues and paired noncancer tissues by RT–PCR. The roles of CLASRP were investigated in CRC cells transfected with plasmids or shRNA through proliferation, migration and invasion assays in vitro and a xenograft model in vivo . Apoptosis was analysed using CLASRP -overexpressing CRC cells by western blotting. Clk inhibitors were used to perform functional research on CLASRP in CLASRP -overexpressing CRC cells. CLASRP was significantly upregulated in CRC cell lines, while high CLASRP expression was correlated with metastasis in CRC patients. Functionally, overexpression of CLASRP significantly promoted the proliferation, migration and invasion of CRC cells in vitro and tumour growth in vivo. Mechanistically, the proliferation, migration and invasion of CLASRP -overexpressing CRC cells were inhibited by Clk inhibitors, accompanied by low expression of CLASRP at the gene and protein levels. Clk inhibitors induced apoptosis of CLASRP -overexpressing CRC cells, resulting in direct blockade of cell growth. The expression levels of cleaved caspase 3 and cleaved caspase 8 were increased in CLASRP -overexpressing CRC cells treated with Clk inhibitors. CLASRP might serve as a promotional oncogene in CRC cells and be suppressed by Clk inhibitors through activation of caspase pathways.

Analysis of Endophytic Bacterial Diversity in Rice Seeds with Regional Characteristics in Yunnan Province, China, Based on High-Throughput Sequencing Technology - Xilong Feng; Zhishan Wang; Xiaolin Li; Wei Wang; Anyu Gu; Yang Liu (Current Microbiology, 2023)

A review of controlled release from cyclodextrins: release methods, release systems and application - Yan Feng; Shuangdi Chen; Zhaofeng Li; Zhengbiao Gu; Shude Xu; Xiaofeng Ban; Yan Hong; Li Cheng; Caiming Li (Critical Reviews in Food Science and Nutrition, 2023)

Enhancing wheat Fusarium head blight detection using rotation Yolo wheat detection network and simple spatial attention network - Dong-Yan Zhang; Han-Sen Luo; Tao Cheng; Wei-Feng Li; Xin-Gen Zhou; Wei-Guo; Chun-Yan Gu; Zhihua Diao (Computers and Electronics in Agriculture, 2023)

Ciliated parasites as the primary agents for early epizootic ulcerative syndrome (EUS) in yellow catfish, Tachysurus fulvifraco - Hao Yang; Xiaoting Feng; Xiao Tu; Fangyuan Liu; Ruixue Hu; Zemao Gu (Aquaculture, 2023)

Anammox bacteria adapt to long-term light irradiation in photogranules - Lingrui Kong; Ru Zheng; Yiming Feng; Wenran Du; Chen Xie; Yuanqi Gu; Sitong Liu (Water Research, 2023)

New insights into the protection of dietary components on anxiety, depression, and other mental disorders caused by contaminants and food additives - Ruo-Gu Xiong; Jiahui Li; Jin Cheng; Si-Xia Wu; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Ao Shang; Guo-Yi Tang; Hua-Bin Li; Ren-You Gan; Yibin Feng (Trends in Food Science & Technology, 2023)

Environmental and health impacts of household energy conversion on PAHs and their derivatives in PM2.5 in typical areas of northern China - Yunlong Bai; Hongmei Xu; Rong Feng; Yunxuan Gu; Meixuan Liu; Jian Sun; Linli Qu; Steven Sai Hang Ho; Zhenxing Shen; Junji Cao (Science of The Total Environment, 2023)

Chemical composition and potential health risks of tire and road wear microplastics from light-duty vehicles in an urban tunnel in China - Meixuan Liu; Hongmei Xu; Rong Feng; Yunxuan Gu; Yunlong Bai; Ningning Zhang; Qiyuan Wang; Steven Sai Hang Ho; Linli Qu; Zhenxing Shen; Junji Cao (Environmental Pollution, 2023)

Delamination of multilayer Ti3C2T MXene alters its adsorpiton and reduction of heavy metals in water - Yuxuan Zhang; Jun Luo; Biao Feng; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Xin Hu; Mu Naushad; Bin Gao; Hongqiang Ren (Environmental Pollution, 2023)

Design of amphiphilic-function-aiding biopolymer adhesives for strong and durable underwater adhesion via a simple solvent-exchange approach - Feng Li; Weidong Gu; Shanshan Gong; Wenrui Zhou; Sheldon.Q. Shi; Qiang Gao; Zhen Fang; Jianzhang Li (Chemical Engineering Journal, 2023)

Suppression of Microglial ERO1a Alleviates Inflammation and Enhances the Efficacy of Rehabilitative Training After Ischemic Stroke - Jing Ren; Yuan Lv; Qiuyan Tian; Li Sun; Po Miao; Xiaofeng Yang; Li-Xiao Xu; Chen-Xi Feng; Mei Li; Qin Gu; Xing Feng; Xin Ding (Molecular Neurobiology, 2023)

Using radium isotopes to evaluate the uncertainty of submarine groundwater discharge in the northeast and entirety of Daya Bay - Hequan Gu; Feng Zhao; Zhixin Ni; Meigui Wu; Li Zhao; Aicui Dang; Dongmei Li; Minxia Zhang; Qin Hu (Acta Oceanologica Sinica, 2023)

Elucidating performance failure in the use of an Anaerobic-Oxic-Anoxic (AOA) plug-flow system for biological nutrient removal - Lingna Xu; Ji Zhao; Jimiao Wang; Ruihuan Gu; Yong Qu; Jianhui Yin; Deshuang Yu; Zhengda Yu; Juan Feng; Xiaoxia Wang (Science of The Total Environment, 2023)

Gene-specific silencing of SlPL16, a pectate lyase coding gene, extends the shelf life of tomato fruit - Haozhan Ren; Qing Zhao; Youwei Feng; Peipei Tang; Yong Wang; Jun Jiang; Chunhua Hu; Yunxing Wang; Baolu Cui; Xiaodong Xie; Yan Li; Xuejie Zhao; et al. (Postharvest Biology and Technology, 2023)

Ambient temperature exposure causes lung function impairment: The evidence from Controlled Temperature Study in Healthy Subjects (CTSHS) - Weihong Qiu; Heng He; Lieyang Fan; Xiaobing Feng; Minjing Li; Chaoqian Dong; Zhenzhen Li; Wei Liu; Ruyi Liang; Yingdie Zhang; Yongfang Zhang; Pei Gu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Composition and transcriptional activity of oil reservoir microorganisms under different gas/liquid ratios - Li-Bin Shou; Zhao-Wei Hou; Yi-Fan Liu; Ying Wang; Lei Zhou; Jin-Feng Liu; Shi-Zhong Yang; Ji-Dong Gu; Xiao-Lin Wu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2023)

Evaluation of the digestibility and antioxidant activity of protein and lipid after mixing nuts based on in vitro and in vivo models - Fangfang Jian; Zhongyuan Zhang; Dajing Li; Fangjian Luo; Qihui Wu; Fengqin Lu; Zhuqing Dai; Meimei Nie; Yayuan Xu; Lei Feng; Qianhui Gu (Food Chemistry, 2023)

The impact of semi-open street roofs on urban pollutant exposure and pedestrian-level thermal comfort in 2-D street canyons - Huiru Zhong; Jiaxi Feng; Cho Kwong Charlie Lam; Jian Hang; Jiajia Hua; Zhongli Gu (Building and Environment, 2023)

Identification of quantitative trait loci and candidate genes for seed folate content in soybean - Kwadwo Gyapong Agyenim-Boateng; Shengrui Zhang; Rongzhe Gu; Shibi Zhang; Jie Qi; Muhammad Azam; Caiyou Ma; Yecheng Li; Yue Feng; Yitian Liu; Jing Li; Bin Li; et al. (Theoretical and Applied Genetics, 2023)

Experimental study on multiple propagation characteristics of stress wave and surface displacement behavior in coal based on SHPB and DIC - Xiaoliang Li; Enlai Zhao; Zhentang Liu; Yubing Liu; Xiaojun Feng; Zhoujie Gu (Bulletin of Engineering Geology and the Environment, 2023)

3D-imaging and quantitative assessment for size-related penetration of HfO2 nanoparticles in breast cancer tumor by synchrotron radiation microcomputed tomography - Jiali Wang; Tingfeng Zhang; You Liao; Wei Chen; Shanshan Liang; Si Xu; Hao Fang; Meng Wang; Lingna Zheng; Zhanjun Gu; Zhiyong Zhang; Bing Wang; et al. (Analytica Chimica Acta, 2023)

Dual-mode colorimetric and homogeneous electrochemical detection of intracellular/extracellular H2O2 based on FeSx/SiO2 nanoparticles with high peroxidase-like activity - Chengcheng Gu; Lipeng Bai; Ting Hou; Lei Zhang; Panpan Gai; Feng Li (Analytica Chimica Acta, 2023)

Characteristics of PM2.5 and Its Reactive Oxygen Species in Heating Energy Transition and Estimation of Its Impact on the Environment and Health in China—A Case Study in the Fenwei Plain - Zexuan Wang; Hongmei Xu; Rong Feng; Yunxuan Gu; Jian Sun; Suixin Liu; Ningning Zhang; Dan Li; Tao Wang; Linli Qu; Steven Sai Hang Ho; Zhenxing Shen; et al. (Advances in Atmospheric Sciences, 2023)

Mold growth under near-saturated preservation environment of unearthed relics within archaeological museums - Bin Chang; Xiao Liu; Xilian Luo; Zhuangbo Feng; Zhaolin Gu (Sustainable Cities and Society, 2023)

Co-incidence of BA.1 and BA.2 at the start of Singapore's Omicron wave revealed by Community and University Campus wastewater surveillance - Feng Jun Desmond Chua; Se Yeon Kim; Eric Hill; Jia Wei Cai; Wei Lin Lee; Xiaoqiong Gu; Siti Aisyah Afri Affandi; Wee Chiew Germaine Kwok; Weijie Ng; Mats Leifels; Federica Armas; Franciscus Chandra; et al. (Science of The Total Environment, 2023)

The tanshinones from the plant of Salvia miltiorrhiza - Jian-Shuang Jiang; Quan-chang Gu; Zi-Ming Feng; Xiang Yuan; Xu Zhang; Pei-Cheng Zhang; Ya-Nan Yang (Phytochemistry, 2023)

New insight into desorption behavior and mechanism of oil from aged oil-contaminated soil in microemulsion - Xiaoning Feng; Shuhai Guo; Fushan Wen; Wei Zhu; Xiujie Yang; Meixia Gu; Nan Shi; Zhiheng Li; Bin Lou; Dong Liu (Journal of Hazardous Materials, 2023)

Cytoplasmic Hsp70s promote EcR transport into the nucleus by responding to various stimuli - Jun Gu; Yan Ye; Zi-Wen Zheng; Wei Luo; Yan-Jun Gong; Qi-Li Feng; Sheng Li; Li-Hua Huang (Insect Biochemistry and Molecular Biology, 2023)

Effect of ammonia on the soot surface characteristics in ammonia/ethylene co-flow diffusion flames - Feng Zhang; Shuanglong Li; Qianqian Liu; Jingyun Sun; Xin Wei; Mingyan Gu; Yang Wang; Xiangyong Huang (Fuel, 2023)

Effects of drying methods on bioactive components of Ganoderma lucidum fermented whole wheat in products & in vitro digestive model - Yang Li; Fengying Gu; Xin Guo; Qiaozhen Zhang; Runrun Hu; Ling Qin; Qiang Wang; Feng Wang (Food Research International, 2023)

Bioactive compounds and health benefits of pomegranate: An updated narrative review - Jin Cheng; Jiahui Li; Ruo-Gu Xiong; Si-Xia Wu; Si-Yu Huang; Dan-Dan Zhou; Adila Saimaiti; Ao Shang; Yibin Feng; Ren-You Gan; Hua-Bin Li (Food Bioscience, 2023)

Conductive materials enhance microbial salt-tolerance in anaerobic digestion of food waste: Microbial response and metagenomics analysis - Jianhao Li; Xiaofeng Xu; Cong Chen; Linji Xu; Zexuan Du; Li Gu; Ping Xiang; Dezhi Shi; Xiaoliu Huangfu; Feng Liu (Environmental Research, 2023)

Structural flexibility in cationic metal–organic framework for boosting ReO4− capture - Shufen Gu; Zhiwu Yu; Ning Li; Qingyun Zhang; Huiping Zhang; Lipeng Zhang; Lele Gong; Rajamani Krishna; Feng Luo (Chemical Engineering Journal, 2023)

Intelligent diagnostic system for Cryptococcus: Switch-controllable nanocatcher and CNN-based artificial intelligence - Feng Gu; Shan Hu; Benshun Tian; Tianyi Ma; Yu Xu; Ying Yang; Bing Gu (Chemical Engineering Journal, 2023)

A trade-off between space exploration and mobilization of organic phosphorus through associated microbiomes enables niche differentiation of arbuscular mycorrhizal fungi on the same root - Jiachao Zhou; Thomas W. Kuyper; Gu Feng (Science China Life Sciences, 2023)

Experimental Study on the Damage Evolution Behavior of Coal Under Dynamic Brazilian Splitting Tests Based on the Split Hopkinson Pressure Bar and the Digital Image Correlation - Xiaoliang Li; Zhentang Liu; Enlai Zhao; Yubing Liu; Xiaojun Feng; Zhoujie Gu (Natural Resources Research, 2023)

Association between urinary cadmium level and subclinical myocardial injury in the general population without cardiovascular disease aged ≥ 50 years - Yu-Jie Wu; Si-Bo Wang; Jia-Teng Sun; Ling-Feng Gu; Ze-Mu Wang; Bo Deng; Hao Wang; Lian-Sheng Wang (Environmental Science and Pollution Research, 2023)

Automatic detection and classification of land subsidence in deltaic metropolitan areas using distributed scatterer InSAR and Oriented R-CNN - Zherong Wu; Peifeng Ma; Yi Zheng; Feng Gu; Lin Liu; Hui Lin (Remote Sensing of Environment, 2023)

Study on fatty acid binding protein in lipid metabolism of livestock and poultry - Chuanchuan Wang; Tong Mu; Xiaofang Feng; Juan Zhang; Yaling Gu (Research in Veterinary Science, 2023)

Regulation of chlorophyll biosynthesis by light-dependent acetylation of NADPH:protochlorophyll oxidoreductase A in Arabidopsis - Minting Liang; Dachuan Gu; Zhiyang Lie; Yongyi Yang; Longxin Lu; Guangyi Dai; Tao Peng; Ling Deng; Feng Zheng; Xuncheng Liu (Plant Science, 2023)

Site-specific isotope fractionation during Zn adsorption onto birnessite: Insights from X-ray absorption spectroscopy, density functional theory and surface complexation modeling - Zhao Wang; Caroline Peacock; Kideok D. Kwon; Xueyuan Gu; Xionghan Feng; Wei Li (Geochimica et Cosmochimica Acta, 2023)

Autochthonous bioaugmentation accelerates phenanthrene degradation in acclimated soil - Haiping Gu; Jie Yan; Yuhao Liu; Xuewei Yu; Yan Feng; Xuanyi Yang; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Environmental Research, 2023)

Europium doped RuO2@TP enhanced chlorine evolution reaction performance by charge redistribution - Lingshu Qiu; Fan Zhang; Yang Qian; Weiwei Han; Yi He; Xiangdong Feng; Jianxin Jin; Yongping Gu; Shaoyun Hao; Xingwang Zhang (Chemical Engineering Journal, 2023)

Galectin-3-centered paracrine network mediates cardiac inflammation and fibrosis upon β-adrenergic insult - Guomin Hu; Jimin Wu; Huijun Gu; Xiangning Deng; Wenli Xu; Shan Feng; Shuaixing Wang; Yao Song; Zhengda Pang; Xiuling Deng; Aleksandr E. Vendrov; Nageswara R. Madamanchi; et al. (Science China Life Sciences, 2023)

Ecotoxicological risk of antibiotics and their mixtures to aquatic biota with the DGT technique in sediments - Yang-Guang Gu; Yan-Peng Gao; Shi-Jun Jiang; Richard W. Jordan; Yu-Feng Yang (Ecotoxicology, 2023)

Triassic igneous activities in the east flank of the East Kunlun orogenic belt: the Daheba complex example - Nan Tian; Feng-Yue Sun; Zhong-Cui Pan; Liang Li; Yan Gu; Dong-Qian Wu; Jia-Fang Deng; Zhe-Dong Liu; Li Wang; Ya-Jing Zhang (International Geology Review, 2023)

Selective and efficient removal of emerging contaminants by sponge-like manganese ferrite synthesized using a solvent-free method: Crucial role of the three-dimensional porous structure - Jianxing Liang; Rongcan Chen; Jia-nan Gu; Jingdong Li; Feng Shi; Yixin Xue; Bingji Huang; Mingming Guo; Jinping Jia; Kan Li; Tonghua Sun (Water Research, 2023)

Nonmetric multidimensional scaling and probabilistic ecological risk assessment of trace metals in surface sediments of Daya Bay (China) using diffusive gradients in thin films - Yang-Guang Gu; Shi-Jun Jiang; Richard W. Jordan; Hong-Hui Huang; Feng-Xia Wu (Science of The Total Environment, 2023)

Insight into the desorption behavior of oily soil with different particle sizes based on accumulation effect and binding interaction - Xiaoning Feng; Zhiheng Li; Xiujie Yang; Bin Lou; Fushan Wen; Nan Shi; Wei Zhu; Shuhai Guo; Meixia Gu; Dong Liu (Journal of Environmental Chemical Engineering, 2023)

Effect of principal stress direction interchange on the failure characteristics of hard rock - Liangjie Gu; Xia-Ting Feng; Rui Kong; Chengxiang Yang (International Journal of Rock Mechanics and Mining Sciences, 2023)

Oral vaccination with recombinant Lactobacillus casei with surface displayed OmpK fused to CTB as an adjuvant against Vibrio mimicus infection in Carassius auratus - Hong-Jin Li; Bin-Tong Yang; Yu-Feng Sun; Tong Zhao; Zhi-Peng Hao; Wei Gu; Meng-Xia Sun; Wei Cong; Yuan-Huan Kang (Fish & Shellfish Immunology, 2023)

Replacing polar aprotic solvents with water in organic synthesis - Feng Gao; Honggang Chang; Jinjin Li; Ruifeng Wang; Yanlong Gu (Current Opinion in Green and Sustainable Chemistry, 2023)

Injectable engineered micro/nano-complexes trigger the reprogramming of bone immune epigenetics - Xindie Zhou; Kun Xi; Jiang Bian; Ziang Li; Liang Wu; Jincheng Tang; Chenwei Xiong; Zhentang Yu; Junjie Zhang; Yong Gu; Yong Huang; Feng Cai; et al. (Chemical Engineering Journal, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

PTSA-catalyzed selective synthesis and antibacterial evaluation of 1,2-disubstituted benzimidazoles - Jiaxu Fu; Yuandong Yue; Kejun Liu; Shuang Wang; Yiliang Zhang; Qing Su; Qiang Gu; Feng Lin; Yumin Zhang (Molecular Diversity, 2023)

Hyphosphere interactions between Rhizophagus irregularis and Rahnella aquatilis promote carbon–phosphorus exchange at the peri‐arbuscular space in Medicago truncatula - Shilong Duan; Stéphane Declerck; Gu Feng; Lin Zhang (Environmental Microbiology, 2023)
Arbuscular mycorrhizal (AM) fungi form a continuum between roots and soil. One end of this continuum is comprised of the highly intimate plant–fungus interface with intracellular organelles for nutrient exchange, while on the other end the fungus interacts with bacteria to compensate for the AM fungus' inability to take up organic nutrients from soil. How both interfaces communicate in this highly complex tripartite mutualism is widely unknown. Here, the effects of phosphate‐solubilizing bacteria (PSB) Rahnella aquatilis dwelling at the surface of the extraradical hyphae of Rhizophagus irregularis was analysed based on the expression of genes involved in C‐P exchange at the peri‐arbuscular space (PAS) in Medicago truncatula . The interaction between AM fungus and PSB resulted in an increase in uptake and transport of Pi along the extraradical hyphae and its transfer from AM fungus to plant. In return, this was remunerated by a transfer of C from plant to AM fungus, improving the C‐P exchange at the PAS. These results demonstrated that a microorganism (i.e., a PSB) developing at the hyphosphere interface can affect the C‐P exchange at the PAS between plant and AM fungus, suggesting a fine‐tuned communication operated between three organisms via two distantly connected interfaces.

Research on the seasonal variation of zooplankton community in Daya Bay, South China Sea - Feng-Xia Wu; Yang-Guang Gu; Qing-Xia Liu; Shu-Fei Zhang; Yi-Yong Rao; Hua-Xue Liu; Ming Dai; Yan-Guo Wang; Hong-Hui Huang (Frontiers in Marine Science, 2023)
Changes in zooplankton composition, abundance, and some species in response to environmental variation were investigated over four seasons (2020) in Daya Bay. In total, 129 taxa of zooplankton (16 groups of planktonic larvae and 20 indeterminate species) were identified. Zooplankton communities exhibited a significant seasonal shift in abundance and taxonomic composition. The maximum number of zooplankton species was recorded in winter (72 species) and the lowest in spring (42 species). However, the abundance was highest in spring (1,372.01 ± 1,071.14 individuals/m³) and lowest in autumn (50.93 ± 34.05 individuals/m³). Pearson correlation analyses demonstrated that the zooplankton abundance and the variations of indicator species were obviously correlated with environmental parameters ( e . g ., salinity, temperature, pH, and chlorophyll- a ). Based on specificity and occupancy analysis, a total of eight species were selected as indicator species. It is noteworthy that some kollaplankton (such as Dolioletta gegenbauri and Doliolum denticulatum ) could potentially cause disaster to the nuclear power plant cooling system because of their relatively large body size and huge blooms in spring. In addition, Centropages tenuiremis blooms in spring and Penilia avirostris blooms in summer could attract assemblages of larval or adult pelagic fish, which would also threaten the cooling system security in Daya Bay. In conclusion, our results suggest that zooplankton communities and some species may be considered as favorable indicators of the marine environment.

Cu(II) removal from water by trimercapto-s-triazine trisodium salt modified alkaline lignin - Qiaorui Wang; Fei He; Jinxing Gu; Xuqin Song; Feng Xu (Environmental Science and Pollution Research, 2023)

Environmental benign foam finishing with a hyperbranched polyphosphonate flame retardant for polyethylene terephthalate fabric - Peng Qi; Feng Chen; Yuchun Li; Yichong Jiang; Tao Zhu; Jun Sun; Hongfei Li; Xiaoyu Gu; Sheng Zhang (Chemosphere, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

Variations in oolong tea key characteristic floral aroma compound contents among tea (Camellia sinensis) germplasms exposed to postharvest stress - Shuhua Wu; Dachuan Gu; Yuzhen Chen; Feng Wang; Jiajia Qian; Lanting Zeng; Jinchi Tang; Ying Yan; Changsong Chen; Jianlong Li (Postharvest Biology and Technology, 2023)

Experimental study on the redistribution law of heavy metals in sludge disintegration - Juanjuan Zhao; Feng Deng; Han Zhang; Wenwen Gu; Huidan Chen; Siqi Huang (Journal of Environmental Management, 2023)

The biodeterioration outbreak in Dunhuang Mogao Grottoes analyzed for the microbial communities and the occurrence time by C-14 dating - Wenxia Ma; Fasi Wu; Dongpeng He; Jie Li; Qi Zhang; Xiaoju Yang; Ji-Dong Gu; Wanfu Wang; Huyuan Feng (International Biodeterioration & Biodegradation, 2023)

Recycling and reuse performance of cobalt catalyst for coal hydrogasification - Jun Feng; Shuai Yan; Rong Zhang; Sumin Gu; Xuan Qu; Jicheng Bi (Fuel, 2023)

Biodegradable Ecoflex encapsulated bacterial cellulose/polypyrrole strain sensor detects motion with high sensitivity, flexibility and scalability - Chong Gao; Yingcun Liu; Feng Gu; Ze Chen; Ziyi Su; Heng Du; Duo Xu; Keshuai Liu; Weilin Xu (Chemical Engineering Journal, 2023)

Elucidating the role of Mo doping in enhancing the meta-Xylene ammoxidation performance over the CeVO4 catalyst - Longqin Gu; Bing Feng; Pengbo Xi; Jun Xu; Bingxu Chen; Siqing Zhong; Weimin Yang (Chemical Engineering Journal, 2023)

Towards low carbon demand and highly efficient nutrient removal: Establishing denitrifying phosphorus removal in a biofilm-based system - Kaiyue Dong; Yanling Qiu; Xiaoxia Wang; Deshuang Yu; Zhengda Yu; Juan Feng; Jimiao Wang; Ruihuan Gu; Ji Zhao (Bioresource Technology, 2023)

Excavation Stress Path Induced Fracturing Mechanism of Hard Rock in Deep Tunnel - Liangjie Gu; Xia-Ting Feng; Rui Kong; Chengxiang Yang; Qiang Han; Yuelin Xia (Rock Mechanics and Rock Engineering, 2023)

Seasonal variation of population and individual dietary niche in the avivorous bat, Ia io - Lixin Gong; Hao Gu; Yang Chang; Zhiqiang Wang; Biye Shi; Aiqing Lin; Hui Wu; Jiang Feng; Tinglei Jiang (Oecologia, 2023)

Combined Application of Calcium-Magnesium Phosphate Fertilizer with Soluble Phosphorus Improves Maize Growth in a Calcareous Soil - Zihang Yang; Wenli Zhou; Baoru Sun; Zed Rengel; Gu Feng; Lin Zhang (Journal of Soil Science and Plant Nutrition, 2023)

Experimental and numerical investigation on seismic performance of corroded RC columns of low-strength concrete - Weiping Zhang; Yang Liu; Feng Hu; Xianglin Gu (Bulletin of Earthquake Engineering, 2023)

Effects of fertilizer and weed species richness on soil nematode community in a microcosm field experiment - Xinli Niu; Yongfan Cheng; Xiaopei Feng; Feng Sun; Yanfang Gu (Soil Ecology Letters, 2023)

DGT method for the in situ measurement of triazines and the desorption kinetics of atrazine in soil - Siheng Zheng; Feng Sheng; Cheng Gu; Yanying Li; Zhou Fang; Jun Luo (Environmental Science and Pollution Research, 2023)

Using transcriptomics, proteomics and phosphoproteomics as new approach methodology (NAM) to define biological responses for chemical safety assessment - Yuan Li; Zhenpeng Zhang; Songhao Jiang; Feng Xu; Liz Tulum; Kaixuan Li; Shu Liu; Suzhen Li; Lei Chang; Mark Liddell; Fengjuan Tu; Xuelan Gu; et al. (Chemosphere, 2023)

Chronic exposure to IQOS results in impaired pulmonary function and lung tissue damage in mice - Jianjun Gu; Daohui Gong; Yuxiu Wang; Tingting Feng; Jun Zhang; Suwei Hu; Lingfeng Min (Toxicology Letters, 2023)

Metagenomics analysis reveals potential pathways and drivers of piglet gut phage-mediated transfer of ARGs - Yalu Ji; Hengyu Xi; Zhen Zhao; Qiujie Jiang; Chong Chen; Xinwu Wang; Fengyang Li; Na Li; Changjiang Sun; Xin Feng; Liancheng Lei; Wenyu Han; et al. (Science of The Total Environment, 2023)

Simultaneous alleviation of Cd availability in contaminated soil and accumulation in rice (Oryza sativa L.) by Fe-Mn oxide-modified biochar - Wen-Tao Tan; Hang Zhou; Shang-Feng Tang; Qiong Chen; Xia Zhou; Xin-Hui Liu; Peng Zeng; Jiao-Feng Gu; Bo-Han Liao (Science of The Total Environment, 2023)

Damming has changed the migration process of microplastics and increased the pollution risk in the reservoirs in the Shaying River Basin - Jiachen Shen; Xu Gu; Run Liu; Hongyu Feng; Dianpeng Li; Yan Liu; Xufei Jiang; Ge Qin; Shuqing An; Ning Li; Xin Leng (Journal of Hazardous Materials, 2023)

Barium isotope fractionation during slab dehydration: Records from an eclogite-quartz vein system in Dabie orogen - Juan Xu; Wang-Ye Li; Xiao-Feng Gu; Hui-Min Yu; Xiao-Yun Nan; Yi-Xiang Chen; Fang Huang (Geochimica et Cosmochimica Acta, 2023)

Phosphorus fertilizer recommendation based on minimum soil surplus for cotton growing in salt-affected soils - Weige Huo; Yi Peng; Baidengsha Maimaitiaili; William David Batchelor; Gu Feng (Field Crops Research, 2023)

Magnetically-oriented porous hydrogel advances wearable electrochemical solidoid sensing heavy metallic ions - Wanxin Tang; Zhen Gu; Yao Chu; Jian Lv; Li Fan; Xinling liu; Feng Wang; Ye Ying; Jian Zhang; Yuning Jiang; Jiaying Cao; Anni Zhu; et al. (Chemical Engineering Journal, 2023)

Deposition effect of inhaled particles in the human: Accurate health risks of personal exposure to PAHs and their derivatives from residential solid fuel combustion - Rong Feng; Hongmei Xu; Yunxuan Gu; Min Gao; Yunlong Bai; Meixuan Liu; Zhenxing Shen; Jian Sun; Linli Qu; Steven Sai Hang Ho; Junji Cao (Atmospheric Environment, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

A recombinant baculovirus vector vaccine ( BacMCP ) against the infectious spleen and kidney necrosis virus ( ISKNV ) - Min Zhu; Zeen Shen; Yuchao Gu; Xinyu Tong; Yaxin Zhang; Jun Pan; Yongjie Feng; Xiaolong Hu; Yujun Wang; Guangli Cao; Renyu Xue; Chengliang Gong (Journal of Fish Diseases, 2023)
The infectious spleen and kidney necrosis virus (ISKNV) is a highly lethal virus, which has brought significant losses to aquaculture. Therefore, a new vaccine against ISKNV with high efficiency, safety and convenience must be developed. While baculoviruses are more commonly used as protein expression systems for vaccine antigen production, this paper used baculovirus technology to develop a live‐vector vaccine, BacMCP, which contains the coding sequence of the major capsid protein (MCP) (GenBank accession no. AF371960) of ISKNV and is driven by a CMV promoter. Real‐time PCR and immunofluorescence showed that the MCP gene was successfully delivered to and expressed in fish cells and tissues inoculated with BacMCP. Immune‐related gene (IgM, TGF‐β, IL‐1, IL‐8, TNF‐α) expression was induced in BacMCP‐treated groups of largemouth bass compared with control groups. Specific antibodies could be detected in the serum of BacMCP injection‐vaccinated largemouth bass by ELISA. After injection or immersion vaccination with BacMCP for 21 days, largemouth bass were infected with ISKNV. The immune effect of the injected immunization on fish in different sizes was evaluated. The vaccine efficacy of injection‐vaccinated bass was 100% in small bass and 85.7% in large bass. The vaccine efficacy of immersion‐vaccinated small bass was 77.3%. This study suggested that BacMCP can be used as a vector‐based vaccine candidate to prevent the diseases caused by ISKNV infection.

Targeted isolation of antitubercular cycloheptapeptides and an unusual pyrroloindoline-containing new analog, asperpyrroindotide A, using LC–MS/MS-based molecular networking - Yi-Qian Han; Qun Zhang; Wei-Feng Xu; Yang Hai; Rong Chao; Cui-Fang Wang; Xue-Mei Hou; Mei-Yan Wei; Yu-Cheng Gu; Chang-Yun Wang; Chang-Lun Shao (Marine Life Science & Technology, 2023)
Further insights on the secondary metabolites of a soft coral-derived fungus Aspergillus versicolor under the guidance of MS/MS-based molecular networking led to the isolation of seven known cycloheptapeptides, namely, asperversiamides A–C ( 1 – 3 ) and asperheptatides A–D ( 4 – 7 ) and an unusual pyrroloindoline-containing new cycloheptapeptide, asperpyrroindotide A ( 8 ). The structure of 8 was elucidated by comprehensive spectroscopic data analysis, and its absolute configuration was determined by advanced Marfey’s method. The semisynthetic transformation of 1 into 8 was successfully achieved and the reaction conditions were optimized. Additionally, a series of new derivatives ( 10 − 19 ) of asperversiamide A ( 1 ) was semi-synthesized and their anti-tubercular activities were evaluated against Mycobacterium tuberculosis H37Ra. The preliminary structure−activity relationships revealed that the serine hydroxy groups and the tryptophan residue are important to the activity.

First report of Ambiphrya species (Ciliophora, Peritrichia) infestation in farmed Micropterus salmoides and Ictalurus punctatus in China - Xiaoting Feng; Hao Yang; Xiao Tu; Zhe Wang; Zemao Gu (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Associations of personal exposure to domestic heating and cooking fuel emissions and epidemiological effects on rural residents in the Fenwei Plain, China - Yunxuan Gu; Hongmei Xu; Rong Feng; Yue Cheng; Bei Han; Kin Fai Ho; Zexuan Wang; Yansu He; Linli Qu; Steven Sai Hang Ho; Jian Sun; Zhenxing Shen; et al. (Science of The Total Environment, 2023)

Phosphorus supply chain for sustainable food production will have mitigated environmental pressure with region-specific phosphorus management - Haiqing Gong; Jiechen Wu; Gu Feng; Xiaoqiang Jiao (Resources, Conservation and Recycling, 2023)

Undescribed isoquinolines from Zanthoxylum nitidum and their antiproliferative effects against human cancer cell lines - Feng Qin; Cai Yi Wang; Chun-Gu Wang; Yao Chen; Jin-Jun Li; Mei-Shan Li; Yan-Kui Zhu; Sang Kook Lee; Heng-Shan Wang (Phytochemistry, 2023)

Suggestion on further strengthening ultra-low emission standards for PM emission from coal-fired power plants in China - Jianguo Deng; Shumin Wang; Jiawei Zhang; Yi Zhang; Jingkun Jiang; Yongzheng Gu; Tao Han; Lei Feng; Jian Gao; Lei Duan (Journal of Environmental Sciences, 2023)

Quantitative conversion of free, acid-hydrolyzable, and bound ellagic acid in walnut kernels during baking - Xin Guo; Fengying Gu; Tingting Yang; Zhixiao Shao; Qiaozhen Zhang; Jinjin Zhu; Feng Wang (Food Chemistry, 2023)

High polarity catalyst of CoFe alloy/fluoride interconnected by bamboo-like nitrogen-doped carbon nanotubes for efficient oxygen evolution reaction - Yubin Kuang; Runze He; Xiaocong Gu; Fulin Yang; Xinlong Tian; Ligang Feng (Chemical Engineering Journal, 2023)

Distinguish the toxic differentiations between acute exposure of micro- and nano-plastics on bivalves: An integrated study based on transcriptomic sequencing - Pengzhi Qi; Longmei Qiu; Dan Feng; Zhongqi Gu; Baoying Guo; Xiaojun Yan (Aquatic Toxicology, 2023)

Deep submerged speleothems in the Sansha Yongle Blue Hole (South China Sea) as determination of low sea levels during the Last Glacial Maximum - Xiaoxiao Yu; Baichuan Duan; Jingyao Zhao; Dongqi Gu; Aiping Feng; Yanxiong Liu; Tiegang Li (Frontiers in Marine Science, 2022)
Although Last Glacial Maximum (LGM) sea levels have been the focus of much attention in climate and marine sciences, the timing, duration, and magnitude need further research. Here we present observations and analyses of the deepest speleothems (-116 m) collected from the deepest known blue hole on a global scale, the Sansha Yongle Blue Hole, Xisha Islands, South China Sea. The field investigations illustrate that submerged speleothems are irregular cauliflower-like coatings on the downward cave ceiling from water depths of ~90 to 120 m. The downward growth direction and negative stable carbon and oxygen stable isotopes of submerged speleothems suggest that they may deposit in an air-filled condition through gravity drip, indicating the maximum LGM sea level. The deep submerged speleothems were dated, indicating two U–Th ages of 29.16 ± 0.17 and 26.04 ± 0.18 ka BP and one radiocarbon age of 18.64 ± 0.12 ka BP, respectively. The investigated deep submerged speleothems therefore clearly determine the minimum onset and maximum termination times for LGM terms of sea level. The results show that LGM began at ~29 ka BP and ended at ~18.5 ka BP. This study therefore provides initial evidence for the use of deep speleothems to determine LGM sea levels and emphasizes the importance of deep submerged speleothems in the reconstruction of Pleistocene low sea levels.

Evaluation of the Effectiveness of Marking Juvenile Takifugu obscurus Otoliths with Strontium - Lingling Gu; Hui Zhang; Guangpeng Feng; Yong Liu; Zhiqiang Han; Feng Zhao; Qing Ye; Wangjiao Hu; Chao Song (Fishes, 2022)
Strontium marking technology is commonly used for extensive marking in stock enhancement and releasing activities. In order to explore the feasibility of this technology for juvenile Takifugu obscurus, five different concentrations of strontium (0, 12, 18, 36, and 72 mg/L) were set up by strontium chloride hexahydrate (SrCl2·6H2O) and T. obscurus were immersed for 7 days. Then, T. obscurus were reared in non-additive water for 25 days. The results showed that the survival rate of all groups was 100%, except the 72 mg/L group, after 7 days of immersion. Moreover, the growths of all the marked groups were better than that of the control group. There was no significant difference between the control and marked groups, except for the 18 mg/L group, indicating that the appropriate concentration of strontium might have positive effect for T. obscurus. The strontium to calcium (Sr/Ca) ratios of otoliths in the marked groups increased with increasing concentration and time, which were higher than the baseline, respectively. Then, the Sr/Ca ratios returned to the original level, but the peak value was still retained, suggesting that the success rate of the strontium marking reached 100%. Notably, the residual strontium content of 18 mg/L group was insufficient for causing negative effects for T. obscurus after 25 days. Therefore, in consideration of the growth, survival, and effect of strontium marking on otolith, 18 mg/L is an appropriate concentration for strontium marking of juvenile T. obscurus. This study confirmed the feasibility of strontium marking for T. obscurus and provided a new approach to rationally and scientifically evaluate the stock enhancement and releasing efficiency of T. obscurus.

First report of cucumber mosaic virus satRNA in Salvia miltiorrhiza in China - Kun Zhang; Yanhong Hua; Chenwei Feng; TianXiao Gu; Xiao Guo; Xinjian Zhuang; Kai Xu (Journal of Plant Pathology, 2022)

Alternate wetting and moderate soil drying irrigation counteracts the negative effects of lower nitrogen levels on rice yield - Siyu Li; Yun Chen; Tingting Li; Feng Yu; Yajun Zhang; Kun Liu; Hao Zhang; Junfei Gu; Jianchang Yang; Lijun Liu (Plant and Soil, 2022)

Exploring the secrets of hyphosphere of arbuscular mycorrhizal fungi: processes and ecological functions - Fei Wang; Lin Zhang; Jiachao Zhou; Zed Rengel; Timothy S. George; Gu Feng (Plant and Soil, 2022)

Inhibition of Spinal 5-HT3 Receptor and Spinal Dorsal Horn Neuronal Excitability Alleviates Hyperalgesia in a Rat Model of Parkinson’s Disease - Cheng-Jie Li; Li-Ge Zhang; Lu-Bing Liu; Meng-Qi An; Li-guo Dong; Han-Ying Gu; Yong-Ping Dai; Fen Wang; Cheng-Jie Mao; Chun-Feng Liu (Molecular Neurobiology, 2022)

Experimental Study on Pyrolysis of Rice Straw Catalyzed by CaO/Al2O3-Phosphate Mixture - Lianlian Xu; Zhongwen Xu; Feng Zhang; Yinmei Yuan; Bin Cheng; Chuang Zhang; Ping Chen; Xiangyong Huang; Yuyu Lin; Mingyan Gu (BioEnergy Research, 2022)

New considerations on the phylogeny of Sessilida (Protista: Ciliophora: Peritrichia) based on multiple-gene information, with emphasis on colonial taxa - Zhe Wang; Xiaoting Feng; Lifang Li; Khaled A. S. Al-Rasheid; Alan Warren; Chundi Wang; Zemao Gu (Marine Life Science & Technology, 2022)

Effect of Different Colored LED Lighting on the Growth and Pigment Content of Isochrysis zhanjiangensis under Laboratory Conditions - Bu Lv; Ziling Liu; Yu Chen; Shuaiqin Lan; Jing Mao; Zhifeng Gu; Aimin Wang; Feng Yu; Xing Zheng; Hebert Ely Vasquez (Journal of Marine Science and Engineering, 2022)
Light is one of the most important environmental factors affecting the growth and reproduction of algae. In this study, the effect of various LED colors on the productivity, chlorophyll (Chl-a, Chl-b, and total Chl), protein, and carbohydrate content of Isochrysis zhanjiangensis in indoor culture was investigated. Microalgae monocultures were cultivated under five different colors (red, green, blue, yellow, and white) for twenty-one days. The microalgae cultured under red light exhibited a higher specific growth rate (0.4431 ± 0.0055 µ day−1), and under white light a higher productivity (0.0728 ± 0.0013 g L−1 day−1). The poorest performance was observed under yellow and green lights. Interestingly, green light exhibited the highest levels of chlorophylls (Chl-a, 1.473 ± 0.037 mg L−1; Chl-b, 1.504 ± 0.001 mg L−1; total Chl, 2.827 ± 0.083 mg L−1). The highest protein content was observed under the white light (524.1935 ± 6.5846 mg L−1), whereas the carbohydrate content was remarkably high under the blue light (24.4697 ± 0.0206 mg L−1). This study is important in terms of the selection of light at the appropriate color (wavelength) to increase the content of organic compounds desired to be obtained indoors with the potential for commercially produced cultures.

Differential study of the Parabramis pekinensis intestinal microbiota according to different gonad development stages - Hailong Gu; Yaming Feng; Zhijing Yang (Fisheries Science, 2022)

Identification and characterization of pleiotropic and epistatic QDRL conferring partial resistance to Pythium irregulare and P. sylvaticum in soybean - Feng Lin; Wenlong Li; Austin G. McCoy; Kelly Wang; Janette Jacobs; Na Zhang; Xiaobo Huo; Shabir H. Wani; Cuihua Gu; Martin I. Chilvers; Dechun Wang (Theoretical and Applied Genetics, 2022)

Recognizing Multivariate Geochemical Anomalies Related to Mineralization by Using Deep Unsupervised Graph Learning - Qingfeng Guan; Shuliang Ren; Lirong Chen; Yao Yao; Ying Hu; Ruifan Wang; Bin Feng; Landing Gu; Wenhui Chen (Natural Resources Research, 2022)

Both AMP-activated and cAMP-dependent protein kinase regulate the expression of heat shock protein 70-2 gene in Neopyropia yezoensis - Zhenjie Sun; Wenhui Gu; Zezhong Feng; Yaqin Fan; Jianfeng Niu; Guangce Wang (Frontiers in Marine Science, 2022)
The upregulation of heat shock protein 70 ( hsp70 ) gene under high temperature stress is a common phenomenon. Although heat shock protein-mediated stress responses play an important role in intertidal Neopyropia yezoensis , the detailed regulatory mechanism of the hsp70 gene expression is still unclear. Here, a full-length sequence of the hsp70-2 gene was cloned and its’ expression regulation was analyzed. There was an activating transcription factors element (ATFE) of cAMP-dependent protein kinase (PKA) was found at the gene promoter region and a highly conserved deduced amino acid sequence with calmodulin-binding activity was detected. Reagents implicated in the induction of the hsp70 gene were then selected to treat the algal samples at 24°C, and the photosynthetic parameters, transcription and translation of this gene were determined. Results showed that quercetin inhibited the transcription of the hsp70-2 gene, significantly decreased the synthesis of the HSP70-2 protein, and lowered the photosynthetic activity of N. yezoensis under high temperature stress conditions. Although the addition of trifluoperazine (TFP), an inhibitor of calmodulin (CAM), downregulated the photosynthetic parameters, the transcription of the hsp70-2 gene was not influenced at high temperature treatment, implying that CAM was not involved in the transcription of the hsp70-2 gene but involved in the heat stress reponding pathways. 5′-aminoimidasole-4-carboxamide-1-β-d-ribofuranoside (AICAR) promoted the synthesis of hsp70-2 transcripts significantly and HSP70-2 protein slightly, which indicated that AMPK regulated the induction of the hsp70-2 gene in N. yezoensis . Forskolin also promoted the upregulation of the hsp70-2 gene. Thus, both AMPK and cAMP-dependent protein kinase (PKA) could phosphorylate HSF and activate the expression of the hsp70-2 gene in N. yezoensis . However, there was no strict correlation between transcripts of the hsp70-2 gene and HSP70-2 protein contents. It was proposed that the posttranscriptional mechanisms were involved in regulating the synthesis of the HSP70-2 protein. Which allowed it to adapt to the extremely variable intertidal environments with an instant responding manner, since the accumulated transcripts could be translated rapidly when needed.

Effects of polycyclic aromatic hydrocarbons fluoranthene on the soil aggregate stability and the possible underlying mechanism - Jixian Mo; Jingyi Feng; Wanying He; Yuze Liu; Ning Cao; Yu Tang; Siyu Gu (Environmental Science and Pollution Research, 2022)

Can mycorrhizal fungi alleviate plant community instability caused by increased precipitation in arid ecosystems? - Yangyang Jia; Tao Zhang; Florian Walder; Yu Sun; Zhaoyong Shi; Cameron Wagg; Changyan Tian; Gu Feng (Plant and Soil, 2022)

Health risks of PM2.5-bound polycyclic aromatic hydrocarbon (PAH) and heavy metals (PPAH&HM) during the replacement of central heating with urban natural gas in Tianjin, China - Jingwei Zhang; Lihong Feng; Yan Zhao; Changchun Hou; Qing Gu (Environmental Geochemistry and Health, 2022)

Variation of soil organic carbon and bulk density during afforestation regulates soil hydraulic properties - Feng Gu; Xue-jiao Chen; Zheng-an Su; Xin-bao Zhang; Ming-hua Zhou (Journal of Mountain Science, 2022)

Discovery of the non‐cosmopolitan lineages in Candidatus Thermoprofundales - Yi‐Fan Liu; Liu Yang; Zhong‐Lin Liu; Jing Chen; Bo Fang; Lei Zhou; Jin‐Feng Liu; Shi‐Zhong Yang; Ji‐Dong Gu; Bo‐Zhong Mu (Environmental Microbiology, 2022)
Summary The recently proposed order Candidatus Thermoprofundales, currently containing only one family‐level lineage Marine Benthic Group‐D (MBG‐D), is distributed in global subsurface ecosystems and ecologically important, but its diversity, evolution and metabolism remain largely unknown. Here we described two novel family‐level specialized lineages in Ca . Thermoprofundales, JdFR‐43 and HyVt, which are restricted to specific biotopes (primarily in marine hydrothermal vents and occasionally in oil reservoirs and hot springs) in contrast to the cosmopolitan lineage MBG‐D. The comparative genomics revealed that the specialized lineages have streamlined genomes, higher GC contents, enriched genes associated with nucleotide biosynthesis, ribosome biogenesis and DNA repair and additional thermostable aminopeptidases, enabling them to adapt to high‐temperature habitats such as marine hydrothermal vents, deep subsurface oil reservoirs and hot springs. On the contrary, the unique metabolic traits of the cosmopolitan MBG‐D, motility, glycolysis, butanoate metabolism, secondary metabolites production and additional genes for specific peptides and carbohydrates degradation potentially enhance its response to environmental change. Substrate preference is found for most MAGs across all lineages with the ability to utilize both polysaccharides (chitin and starch) and proteinaceous substances, whereas JdFR‐43 members from oil reservoirs can only utilize proteins. These results expand the diversity of C a . Thermoprofundales significantly and further improve our understandings of the adaptations of C a . Thermoprofundales to various environments.

Heavy metal-induced lipogenic gene aberration, lipid dysregulation and obesogenic effect: a review - Yang Zhou; Frank Peprah Addai; Xinshuang Zhang; Yuelin Liu; Yinfeng Wang; Feng Lin; Alex Tuffour; Jie Gu; Guangxiang Liu; Haifeng Shi (Environmental Chemistry Letters, 2022)

Metabolism, absorption, and anti-cancer effects of sulforaphane: an update - Hao-feng Gu; Xue-ying Mao; Min Du (Critical Reviews in Food Science and Nutrition, 2022)

Reducing methane emission by promoting its oxidation in rhizosphere through nitrogen-induced root growth in paddy fields - Siyu Li; Yun Chen; Feng Yu; Yajun Zhang; Kun Liu; Xinxin Zhuo; Yuanyuan Qiu; Hao Zhang; Junfei Gu; Weilu Wang; Jianchang Yang; Lijun Liu (Plant and Soil, 2022)

Integrative studies on the taxonomy and molecular phylogeny of four new Pleuronema species (Protozoa, Ciliophora, Scuticociliatia) - Mingjian Liu; Yujie Liu; Tengteng Zhang; Borong Lu; Feng Gao; Jing Gu; Saleh A. Al-Farraj; Xiaozhong Hu; Weibo Song (Marine Life Science & Technology, 2022)
The ciliate genus Pleuronema comprises approximately 30 nominal species and has been reported in freshwater, brackish water, and marine habitats. Nevertheless, recent studies have indicated that there might be a large undiscovered species diversity. In the present work, four new Pleuronema species, namely P. foissneri sp. nov., P. parasmalli sp. nov., P. parasalmastra sp. nov., and P. paraorientale sp. nov., collected from Shenzhen, southern China, was investigated using taxonomic methods. The diagnosis, description, comparisons with morphologically related species and detailed morphometric data are supplied for each. The small subunit ribosomal RNA (SSU rRNA) gene of the four new species is sequenced and their molecular phylogeny is analyzed. The SSU rRNA gene tree shows that Pleuronema is polyphyletic comprising several separate clades. All four new species cluster consistently with P. orientale KF206429, P. puytoraci KF840520 and P. setigerum FJ848874 within the core Pleuronematidae + Peniculistomatidae clade. Phylogenies of Pleuronematidae-related taxa are also discussed.

Can SpRY recognize any PAM in human cells? - Jinbin Ye; Haitao Xi; Yilu Chen; Qishu Chen; Xiaosheng Lu; Jineng Lv; Yamin Chen; Feng Gu; Junzhao Zhao (Journal of Zhejiang University-SCIENCE B, 2022)

C:P stoichiometric imbalance between soil and microorganisms drives microbial phosphorus turnover in the rhizosphere - Yi Peng; Yisheng Duan; Weige Huo; Zuojian Zhang; Da Huang; Minggang Xu; Xihe Wang; Xueyun Yang; Boren Wang; Yakov Kuzyakov; Gu Feng (Biology and Fertility of Soils, 2022)

Phenolic glycosides from Sanguisorba officinalis and their anti-inflammatory effects - Jin-feng Chen; Lu Tan; Feng Ju; Qi-xuan Kuang; Tian-long Yang; Fang Deng; Yu-cheng Gu; Li-shi Jiang; Yun Deng; Da-le Guo (Natural Product Research, 2022)

Dissection of the practical soybean breeding pipeline by developing ZDX1, a high-throughput functional array - Rujian Sun; Bincheng Sun; Yu Tian; Shanshan Su; Yong Zhang; Wanhai Zhang; Jingshun Wang; Ping Yu; Bingfu Guo; Huihui Li; Yanfei Li; Huawei Gao; et al. (Theoretical and Applied Genetics, 2022)
Key message We developed the ZDX1 high-throughput functional soybean array for high accuracy evaluation and selection of both parents and progeny, which can greatly accelerate soybean breeding. Abstract Microarray technology facilitates rapid, accurate, and economical genotyping. Here, using resequencing data from 2214 representative soybean accessions, we developed the high-throughput functional array ZDX1, containing 158,959 SNPs, covering 90.92% of soybean genes and sites related to important traits. By application of the array, a total of 817 accessions were genotyped, including three subpopulations of candidate parental lines, parental lines and their progeny from practical breeding. The fixed SNPs were identified in progeny, indicating artificial selection during the breeding process. By identifying functional sites of target traits, novel soybean cyst nematode-resistant progeny and maturity-related novel sources were identified by allele combinations, demonstrating that functional sites provide an efficient method for the rapid screening of desirable traits or gene sources. Notably, we found that the breeding index (BI) was a good indicator for progeny selection. Superior progeny were derived from the combination of distantly related parents, with at least one parent having a higher BI. Furthermore, new combinations based on good performance were proposed for further breeding after excluding redundant and closely related parents. Genomic best linear unbiased prediction (GBLUP) analysis was the best analysis method and achieved the highest accuracy in predicting four traits when comparing SNPs in genic regions rather than whole genomic or intergenic SNPs. The prediction accuracy was improved by 32.1% by using progeny to expand the training population. Collectively, a versatile assay demonstrated that the functional ZDX1 array provided efficient information for the design and optimization of a breeding pipeline for accelerated soybean breeding.

An fMRI investigation of the intention-outcome interactions in second- and third-party punishment - Chunliang Feng; Qun Yang; Lydia Azem; Konstantina M. Atanasova; Ruolei Gu; Wenbo Luo; Morris Hoffman; Stefanie Lis; Frank Krueger (Brain Imaging and Behavior, 2022)

Vegetation-related dry deposition of global PM2.5 from satellite observations - Huihui Feng; Ying Ding; Bin Zou; Jason Blake Cohen; Shuchao Ye; Zhuolin Yang; Kai Qin; Lei Liu; Xiaodong Gu (Journal of Geographical Sciences, 2022)

Metabolomics changes in brain-gut axis after unpredictable chronic mild stress - Qiuyue Xu; Mingchen Jiang; Simeng Gu; Xunle Zhang; Guangkui Feng; Xianjun Ma; Shijun Xu; Erxi Wu; Jason H Huang; Fushun Wang (Psychopharmacology, 2022)
Background Major depressive disorder is a leading cause of disability worldwide, affecting up to 17 % of the general population. The neural mechanisms of depression, however, are yet to be uncovered. Recently, attention has been drawn to the effects of dysfunctional brain-gut axis on depression, and many substances have been suggested to be involved in the communication between the gut and brain, such as ghrelin. Methods We herein systematically examined the changes of metabolomics after unpredictable chronic mild stress (UCMS)–induced depression-like behaviors in rats and compared the altered metabolites in the hippocampus and jejunum samples. Results Our results show that many metabolites significantly changed with UCMS both in the hippocampus and jejunum, such as L-glutamine, L-tyrosine, hydroxylamine, and 3-phosphoglyceric acid. Further studies suggested that these changes are the reasons for anxiety-like behaviors and depression-like behaviors in UCMS rats and also are the reasons for hippocampal neural plasticity. Conclusions Coexistence of brain and gut metabolic changes in UCMS-induced depressive behavior in rats suggests a possible role of brain-gut axis in depression. This study provides insights into the neurobiology of depression.

Circular RNA circ_0008934 promotes hepatocellular carcinoma growth and metastasis through modulating miR-1305/TMTC3 axis - Jia-Xi Li; Jin-Jiang Wang; Zhou-Feng Deng; Hao Zheng; Chun-Mei Yang; Ying Yuan; Cheng Yang; Fang-Fang Gu; Wei-Qi Wu; Guang-Lei Qiao; Li-Jun Ma (Human Cell, 2022)

Same total normal forms sperm counts of males from Lhasa and Shanghai, China - Benhong Gu; Shangren Wang; Feng Liu; Yuxuan Song; Jun Li; Yongtao Ni; Min Chen; Jianlin Hu; Luobu Ouzhu; Zheng Li; Li Liu; Xia Li; et al. (Environmental Science and Pollution Research, 2022)

Research progress on inosine monophosphate deposition mechanism in chicken muscle - Zengwen Huang; Juan Zhang; Yaling Gu; Zhengyun Cai; Xiaofang Feng; Chaoyun Yang; Guosheng Xin (Critical Reviews in Food Science and Nutrition, 2022)

Neutrophil Extracellular Traps may be a Potential Target for Treating Early Brain Injury in Subarachnoid Hemorrhage - Hanhai Zeng; Xiongjie Fu; Jing Cai; Chenjun Sun; Mengyan Yu; Yucong Peng; Jianfeng Zhuang; Jingyin Chen; Huaijun Chen; Qian Yu; Chaoran Xu; Hang Zhou; et al. (Translational Stroke Research, 2022)

Structure modification, antialgal, antiplasmodial, and toxic evaluations of a series of new marine-derived 14-membered resorcylic acid lactone derivatives - Wei-Feng Xu; Na-Na Wu; Yan-Wei Wu; Yue-Xuan Qi; Mei-Yan Wei; Laura M. Pineda; Michelle G. Ng; Carmenza Spadafora; Ji-Yong Zheng; Ling Lu; Chang-Yun Wang; Yu-Cheng Gu; et al. (Marine Life Science & Technology, 2022)
Marine natural products play critical roles in the chemical defense of many marine organisms and are essential, reputable sources of successful drug leads. Sixty-seven 14-membered resorcylic acid lactone derivatives 3 – 27 and 30 – 71 of the natural product zeaenol ( 1 ) isolated from the marine-derived fungus Cochliobolus lunatus were semisynthesized by chlorination, acylation, esterification, and acetalization in one to three steps. The structures of these new derivatives were established by HRESIMS and NMR techniques. All the compounds ( 1 – 71 ) were evaluated for their antialgal and antiplasmodial activities. Among them, 14 compounds displayed antifouling activities against adhesion of the fouling diatoms. In particular, 9 and 34 exhibited strong and selective inhibitory effects against the diatoms Navicula laevissima and Navicula exigua (EC 50 = 6.67 and 8.55 μmol/L), respectively, which were similar in efficacy to those of the positive control SeaNine 211 (EC 50 = 2.90 and 9.74 μmol/L). More importantly, 38 , 39 , and 69 – 71 showed potent antiplasmodial activities against Plasmodium falciparum with IC 50 values ranging from 3.54 to 9.72 μmol/L. Very interestingly, the five antiplasmodial derivatives displayed non-toxicity in the cytotoxicity assays and the zebrafish embryos model, thus, representing potential promising antiplasmodial drug agents. The preliminary structure–activity relationships indicated that biphenyl substituent at C-2, acetonide at positions C-5′ and C-6′, and tri- or tetra-substituted of acyl groups increased the antiplasmodial activity. Therefore, combining evaluation of chemical ecology with pharmacological models will be implemented as a systematic strategy, not only for environmentally friendly antifoulants but also for structurally novel drugs.

Effects of air pollution and green spaces on impaired lung function in children: a case-control study - Jingwei Zhang; Yuming Wang; Lihong Feng; Changchun Hou; Qing Gu (Environmental Science and Pollution Research, 2022)

The risk characteristics of heavy metals in urban soil of typical developed cities in China - Yan Li; Dike Feng; Meiying Ji; Zhanpeng Li; Ruocheng Zhang; Chenwei Gu (Environmental Monitoring and Assessment, 2022)

A Possible Dynamic Mechanism for Rapid Production of the Extreme Hourly Rainfall in Zhengzhou City on 20 July 2021 - Jinfang Yin; Haodong Gu; Xudong Liang; Miao Yu; Jisong Sun; Yanxin Xie; Feng Li; Chong Wu (Journal of Meteorological Research, 2022)

Organic fertilizer amendment promotes wheat resistance to herbivory and biocontrol services via bottom-up effects in agroecosystems - Shimin Gu; Myron P. Zalucki; Xingyuan Men; Jing Li; Ruixing Hou; Qingqing Zhang; Feng Ge; Fang Ouyang (Journal of Pest Science, 2022)

Comprehensive evaluation and analysis of the salinity stress response mechanisms based on transcriptome and metabolome of Staphylococcus aureus - Ying Feng; Dizhou Gu; Ziyan Wang; Chenyang Lu; Jingfeng Fan; Jun Zhou; Rixin Wang; Xiurong Su (Archives of Microbiology, 2022)

Longitudinal virological changes and underlying pathogenesis in hospitalized COVID-19 patients in Guangzhou, China - Zhengtu Li; Yinhu Li; Ruilin Sun; Shaoqiang Li; Lingdan Chen; Yangqing Zhan; Mingzhou Xie; Jiasheng Yang; Yanqun Wang; Airu Zhu; Guoping Gu; Le Yu; et al. (Science China Life Sciences, 2021)

Gene expression profiles in the brain of phenylketonuria mouse model reversed by the low phenylalanine diet therapy - Sha Hong; Tianwen Zhu; Simin Zheng; Xia Zhan; Feng Xu; Xuefan Gu; Lili Liang (Metabolic Brain Disease, 2021)

Genome editing of Corynebacterium glutamicum mediated with Cpf1 plus Ku/LigD - Fa-Yu Yang; Nan Wei; Zhi-Hao Zhang; Mi Wang; Ying-Chun Liu; Li-Fang Zhang; Feng Gu (Biotechnology Letters, 2021)

Diversity and spatial–temporal distribution of airborne fungi at the world culture heritage site Maijishan Grottoes in China - Yulong Duan; Fasi Wu; Dongpeng He; Ji-Dong Gu; Huyuan Feng; Tuo Chen; Guangxiu Liu; Wanfu Wang (Aerobiologia, 2021)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Characteristics of warm cores of tropical cyclones in a 25-km-mesh regional climate simulation over CORDEX East Asia domain - Dazhi Xi; Kekuan Chu; Zhe-Min Tan; Jian-Feng Gu; Wenqiang Shen; Yi Zhang; Jianping Tang (Climate Dynamics, 2021)

Defective Autophagy and Mitophagy in Alzheimer’s Disease: Mechanisms and Translational Implications - Jie Chen; Hai-Jun He; Qianqian Ye; Feifei Feng; Wen-Wen Wang; Yingying Gu; Ruiyu Han; Chenglong Xie (Molecular Neurobiology, 2021)

A landslide in Heifangtai, northwest of the Chinese Loess Plateau: triggered factors, movement characteristics, and failure mechanism - Jia-xu Kong; Jian-qi Zhuang; Jie-wei Zhan; Zheng-wei Bai; Yan-qiu Leng; Peng-hui Ma; Jian-bing Peng; Zuo-peng Wang; Tian-feng Gu; Jia-xing Sun; Fan-chen Zhang; Yuan-jun Xu; et al. (Landslides, 2021)

Vascular endothelial growth factor ameliorated palmitate-induced cardiomyocyte injury via JNK pathway - Shi-ya Wang; Cao Zou; Xiao-feng Liu; Yon-jin Yan; Shun-zhon Gu; Xun Li (In Vitro Cellular & Developmental Biology - Animal, 2021)
Enhanced apoptosis of cardiomyocytes in suffering overloaded saturated fatty acids (SFAs) can result in myocardial infarction and cardiac dysfunction. The function of vascular endothelial growth factor (VEGF) in cardiomyocyte protection was not clearly described. To investigate the preservative effects of VEGF sensitization on ceramide-mediated programmed cell death of cardiomyocytes, palmitate-induced injury in H9c2 cells was established as an in vitro model. Results revealed that 0.5 mM palmitate application effectively led to debased viability and activated apoptotic factors. A significant time-dependent relation between PAL and cardiomyocyte injury was observed. The apoptosis rate was increased greatly after 16 h of treatment with 0.5 mM PAL. In addition, cell viability was restored by VEGF overexpression during treatment with 0.5 mM PAL. Reduced apoptosis rate and expression of caspase 3, Bax, and NF-κB p65 were observed in this process, while boosted Bcl-2, p-JNK/JNK expression and activity of caspase 3 were checked. However, p-ERK/ERK levels did not exhibit a significant change. These findings indicated the protective effects of VEGF in confronting the ceramide-induced cardiomyocyte apoptosis, and would devote therapeutic targets for cardiovascular safeguard in dealing with fatty acid stress.

Distribution of ammonia-oxidizing archaea and bacteria along an engineered coastal ecosystem in subtropical China - Yong-Feng Wang; Ji-Dong Gu; Richard P. Dick; Wei Han; Hui-Xiao Yang; Huan-Qin Liao; Yi Zhou; Han Meng (Ecotoxicology, 2021)

Let-7a-5p regulated by lncRNA-MEG3 promotes functional differentiation to Schwann cells from adipose derived stem cells via directly inhibiting RBPJ-mediating Notch pathway - Wei Wang; Mei-Feng Gu; Zhi-Fei Wang; Xiang-Min Shen; Jie Zhang; Liang Yang (Apoptosis, 2021)

CRISPR/Cas9-mediated mutagenesis at microhomologous regions of human mitochondrial genome - Bang Wang; Xiujuan Lv; Yufei Wang; Zhibo Wang; Qi Liu; Bin Lu; Yong Liu; Feng Gu (Science China Life Sciences, 2021)

Wogonin Accelerates Hematoma Clearance and Improves Neurological Outcome via the PPAR-γ Pathway After Intracerebral Hemorrhage - Jianfeng Zhuang; Yucong Peng; Chi Gu; Huihui Chen; Zheng Lin; Hang Zhou; Xiao Wu; Jianru Li; Xiaobo Yu; Yang Cao; Hanhai Zeng; Xiongjie Fu; et al. (Translational Stroke Research, 2021)

Molecular mapping of quantitative disease resistance loci for soybean partial resistance to Phytophthora sansomeana - Feng Lin; Wenlong Li; Austin G. McCoy; Xuan Gao; Paul J. Collins; Na Zhang; Zixiang Wen; Sizhe Cao; Shabir H. Wani; Cuihua Gu; Martin I. Chilvers; Dechun Wang (Theoretical and Applied Genetics, 2021)

Profiling of Serum Exosome MiRNA Reveals the Potential of a MiRNA Panel as Diagnostic Biomarker for Alzheimer’s Disease - Zhiwu Dong; Hongjun Gu; Qiang Guo; Shuang Liang; Jian Xue; Feng Yao; Xianglu Liu; Feifei Li; Huiling Liu; Li Sun; Kewen Zhao (Molecular Neurobiology, 2021)

Assessments of heavy metal pollution of a farmland in an urban area based on the Environmental Geochemical Baselines - Xinzhe Lu; Anqing Gu; Chunlei Huang; Yingchun Wei; Mingxing Xu; Hanqin Yin; Xue-Feng Hu (Journal of Soils and Sediments, 2021)

Correction to: Soil microbial biomass phosphorus can serve as an index to reflect soil phosphorus fertility - Yi Peng; Yisheng Duan; Weige Huo; Minggang Xu; Xueyun Yang; Xihe Wang; Boren Wang; Martin S. A. Blackwell; Gu Feng (Biology and Fertility of Soils, 2021)

Soil microbial biomass phosphorus can serve as an index to reflect soil phosphorus fertility - Yi Peng; Yisheng Duan; Weige Huo; Minggang Xu; Xueyun Yang; Xihe Wang; Boren Wang; Martin S. A. Blackwell; Gu Feng (Biology and Fertility of Soils, 2021)

Design and Implementation for the High Voltage DC-DC Converter of the Subsea Observation Network - Feng Zhang; Zhifeng Zhang; Sa Xiao; Kai Xie; Jiawei Ni; Haolun Gu; Yong Wu; Yang Ning; Qingchao Xia (Journal of Marine Science and Engineering, 2021)
The subsea observation network has become an indispensable means of ocean exploration worldwide. However, the scale of the subsea observation network is limited by the power supply voltage and power level. Hence, to promote the development of a subsea observation network, this paper investigates the underwater high voltage DC-DC converter (HVC), which greatly improves the voltage and power level of the subsea observation network. The traditional series-parallel converter based on multi-module is faced with many technical problems, such as difficult transformer isolation, many fault points, low power density under higher input voltage level, and higher output power. The subsea HVC of this paper adopts a modular multilevel resonant DC-DC converter. The main circuit of HVC is designed in detail, including a module circuit, a resonant circuit, and a control scheme. Through the combination of the sub-module removal voltage regulation and closed-loop control, the converter can still output a stable voltage of 375 V when the input voltage changes. The modular sub-module and centralized transformer structure enables the converter to isolate high voltage easily, small volume, and high power density. The simulation and experiment results show the proposed HVC meets the design requirements and has good application prospects. It can be applied to submarine power transmission and distribution needs because of its wide range, large transformation ratio, and high efficiency.

Occurrence, Profiles and Ecological Risk of Bisphenol Analogues in a Municipal Sewage Treatment Plant - Deming Gu; Zhongxian Song; Haiyan Kang; Yanli Mao; Qiyan Feng (Bulletin of Environmental Contamination and Toxicology, 2021)

Influence of Considering the Sorption Effect in the Betti-Maxwell Reciprocal Theorem on Gas Transport Capacity in Unconventional Reservoirs - Qin Ying; Hongbin Zhang; Jing Zhao; Wenbo Wu; Bin Gu; Xi-Qiao Feng (Transport in Porous Media, 2021)

Arbuscular mycorrhizal fungi alleviate the negative effects of increases in phosphorus (P) resource diversity on plant community structure by improving P resource utilization - Tao Zhang; Gu Feng (Plant and Soil, 2021)

The Fe3O4-modified biochar reduces arsenic availability in soil and arsenic accumulation in indica rice (Oryza sativa L.) - Yao Yao; Hang Zhou; Xiu-Lan Yan; Xiao Yang; Kang-Wen Huang; Juan Liu; Li-Juan Li; Jing-Yi Zhang; Jiao-Feng Gu; Yaoyu Zhou; Bo-Han Liao (Environmental Science and Pollution Research, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Stoichiometric analysis of an arable crop–soil–microbe system after repeated fertilizer and compost application for 10 years - Yi Yang; Rongbo Ji; Hongyan Zhang; Peter Christie; Gu Feng; Xiaolin Li; Jingping Gai (Journal of Soils and Sediments, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Spatial distribution and determinants of PM2.5 in China’s cities: fresh evidence from IDW and GWR - Kuiying Gu; Yi Zhou; Hui Sun; Feng Dong; Lianming Zhao (Environmental Monitoring and Assessment, 2021)

A Re-evaluation of the Taxonomy and Classification of the Type III Secretion System in a Pathogenic Bacterium Causing Soft Rot Disease of Pleurotus eryngii - Feng Xu; Hui Yan; Yu Liu; Shuang Zhao; Shuang Song; Tongtong Gu; Zhongjuan Song; Jianbo Xie; Chengbo Rong (Current Microbiology, 2021)

Characterization of a recombinant sucrose isomerase and its application to enzymatic production of isomaltulose - Feng Zhang; Feng Cheng; Dong-Xu Jia; Yue-Hao Gu; Zhi-Qiang Liu; Yu-Guo Zheng (Biotechnology Letters, 2021)

Production of functional human nerve growth factor from the submandibular glands of mice using a CRISPR/Cas9 genome editing system - Yi Gu; Hui Cao; Fei Li; Jianli Yu; Rui Nian; Dongxiao Feng; Jingtao Lin; Haipeng Song; Wenshuai Liu (World Journal of Microbiology and Biotechnology, 2020)

Factors associated with a SARS-CoV-2 recurrence after hospital discharge among patients with COVID-19: systematic review and meta-analysis - Meng-qi Yao; Qiu-xian Zheng; Jia Xu; Jing-wen Deng; Tian-tian Ge; Hai-bo Zhou; Feng-tian Wu; Xin-yu Gu; Qin Yang; Yan-li Ren; Gang Wang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Creep damage properties of sandstone under dry-wet cycles - Xin-gang Wang; Bao-qin Lian; Jia-ding Wang; Wen-kai Feng; Tian-Feng Gu (Journal of Mountain Science, 2020)

Intelligent identification method for near-surface ground fissures based on seismic data - Su-Zhen Shi; Jian-Ying Gu; Jian Feng; Pei-fei Duan; You-chao Qi; Qi Han (Applied Geophysics, 2020)

Micro-Topography Manipulations Facilitate Suaeda Salsa Marsh Restoration along the Lateral Gradient of a Tidal Creek - Dawei Wang; Junhong Bai; Wei Wang; Xu Ma; Yanan Guan; Chuanhui Gu; Shuyan Zhang; Feng Lu (Wetlands, 2020)

How the constituents of fine particulate matter and ozone affect the lung function of children in Tianjin, China - Jingwei Zhang; Lihong Feng; Changchun Hou; Qing Gu (Environmental Geochemistry and Health, 2020)

Molecular characterization of an emerging reassortant mammalian orthoreovirus in China - Dandan Ye; Zhaoyang Ji; Hongyan Shi; Jianfei Chen; Da Shi; Liyan Cao; Jianbo Liu; Mingwei Li; Hui Dong; Zhaoyang Jing; Xiaobo Wang; Qiuge Liu; et al. (Archives of Virology, 2020)

Pentamidine sensitizes FDA-approved non-antibiotics for the inhibition of multidrug-resistant Gram-negative pathogens - Chenxuan Wu; Ling Xia; Wei Huang; Yangfan Xu; Yuanxin Gu; Chang Liu; Luting Ji; Wenyao Li; Yandong Wu; Kai Zhou; Xinxin Feng (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Microseismic monitoring and stability analysis for the large-scale underground caverns at the Wudongde hydropower station - Biao Li; Nuwen Xu; Feng Dai; Gongkai Gu; Wei Ke (Bulletin of Engineering Geology and the Environment, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Analysis of main pathogenic bacteria and drug sensitivity in patients with chronic suppurative otitis media and middle ear cholesteatoma in China - Feng Xu; Weili Kong; Jiaojiao Peng; Hailing Gu; Hong Zheng (Biotechnology Letters, 2020)

Effects of Bacillus cereus PAS38 on Immune-Related Differentially Expressed Genes of Spleen in Broilers - Xiaoxiao Gu; Jiao Zhang; Jiajun Li; Zhenhua Wang; Jie Feng; Jianzhen Li; Kangcheng Pan; Xueqin Ni; Dong Zeng; Bo Jing; Dongmei Zhang (Probiotics and Antimicrobial Proteins, 2020)

Directed functional connectivity of the hippocampus in patients with presbycusis - Yu-Chen Chen; Wei Yong; Chunhua Xing; Yuan Feng; Nasir Ahmad Haidari; Jin-Jing Xu; Jian-Ping Gu; Xindao Yin; Yuanqing Wu (Brain Imaging and Behavior, 2020)

Field performance of different maize varieties in growth cores at natural and reduced mycorrhizal colonization: yield gains and possible fertilizer savings in relation to phosphorus application - Xin-Xin Wang; Wopke van der Werf; Yang Yu; Ellis Hoffland; Gu Feng; Thomas W. Kuyper (Plant and Soil, 2020)

Microwave-assisted efficient synthesis of 3-substituted bis-isoxazole ether bearing 2-chloro-3-pyridyl via 1,3-dipolar cycloaddition - Ran Zheng; Fan Feng; Zhihui Zhang; Jiaxu Fu; Qing Su; Yumin Zhang; Qiang Gu (Molecular Diversity, 2020)

Anticancer activity evaluation of indazolyl-substituted piperidin-4-yl-aminopyrimidines - Chao Wang; Xiao-Wen Liu; Ting Xiao; Zhi-Qiang Xu; Shuang Cao; Hai-Feng Wang; Qiong-Jiao Yan; Shuang-Xi Gu; Yuan-Yuan Zhu (Medicinal Chemistry Research, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Effect of three Napier grass varieties on phytoextraction of Cd- and Zn-contaminated cultivated soil under mowing and their safe utilization - Wen-Jun Yang; Jiao-Feng Gu; Hang Zhou; Fang Huang; Teng-Yue Yuan; Jing-Yi Zhang; Shi-Long Wang; Zhi-Guang Sun; Hong-Wei Yi; Bo-Han Liao (Environmental Science and Pollution Research, 2020)

Three new ɑ-pyrone derivatives induced by chemical epigenetic manipulation of Penicillium herquei , an endophytic fungus isolated from Cordyceps sinensis - Da-Le Guo; Ling Qiu; Dan Feng; Xin He; Xiao-Hua Li; Zhi-Xing Cao; Yu-Cheng Gu; Ling Mei; Fang Deng; Yun Deng (Natural Product Research, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Soil plant-available phosphorus levels and maize genotypes determine the phosphorus acquisition efficiency and contribution of mycorrhizal pathway - Qun Chu; Lin Zhang; Jianwei Zhou; Lixing Yuan; Fanjun Chen; Fusuo Zhang; Gu Feng; Zed Rengel (Plant and Soil, 2020)

Health benefits on cardiocerebrovascular disease of reducing exposure to ambient fine particulate matter in Tianjin, China - Jingwei Zhang; Lihong Feng; Changchun Hou; Qing Gu (Environmental Science and Pollution Research, 2020)

Reservoir characteristics, pore structure, and main controlling factors of oolitic shoal reservoir in Feixianguan Formation: a case study from eastern Kaijiang-Liangping Trough - Yifan Gu; Yuqiang Jiang; Hairuo Qing; Liang Feng; Linjie Feng; Yonghong Fu; Chan Jiang (Arabian Journal of Geosciences, 2020)

Prevention of breast cancer by dietary polyphenols—role of cancer stem cells - Hao-Feng Gu; Xue-Ying Mao; Min Du (Critical Reviews in Food Science and Nutrition, 2020)

Mycorrhizal impacts on root trait plasticity of six maize varieties along a phosphorus supply gradient - Xin-Xin Wang; Hongbo Li; Qun Chu; Gu Feng; Thomas W. Kuyper; Zed Rengel (Plant and Soil, 2020)

Accumulation of PAHs of the soils and assessment of their health risks at a village with plastic manufacturing in Taizhou, Zhejiang Province, Southeast China - Xinzhe Lu; Anqing Gu; Yanwu Zhang; Xianyao Chu; Xue-Feng Hu (Journal of Soils and Sediments, 2020)

Distributions of 224, 223Ra and 137Cs in the Luzon Strait and its adjacent waters and their response to Typhoon Rainbow - Hequan Gu; Feng Zhao; Wei Yu; Ruihuan Li; Li Zhao; Dongmei Li (Acta Oceanologica Sinica, 2019)

Radiolarian fauna from the Chiungchussuan Shuijingtuo Formation (Cambrian Series 2) in Western Hubei Province, South China - Qiangfen Ma; Qinglai Feng; Wenchao Cao; Lei Zhang; Yan Ye; Songzhu Gu (Science China Earth Sciences, 2019)

Comparison of immunomodulatory properties of exosomes derived from bone marrow mesenchymal stem cells and dental pulp stem cells - Lujun Ji; Liuliu Bao; Zhifeng Gu; Qiao Zhou; Yi Liang; Ya Zheng; Yang Xu; Xiang Zhang; Xingmei Feng (Immunologic Research, 2019)

Occurrence and Risk Assessment of Antibiotics in Manure, Soil, Wastewater, Groundwater from Livestock and Poultry Farms in Xuzhou, China - Deming Gu; Qiyan Feng; Changsheng Guo; Song Hou; Jiapei Lv; Yan Zhang; Sheng Yuan; Xin Zhao (Bulletin of Environmental Contamination and Toxicology, 2019)

Molecular cloning, expression and characterization of secreted ferritin in the silkworm, Bombyx mori - Yang Zhou; Xiao-Dong Yuan; Jing-Chi Wang; Hai-Tao Liu; Frank Addai Peprah; Ting-Ya Jiang; Jie Gu; Hai-Feng Shi (BioMetals, 2019)

Biological properties and genomics analysis of vB_KpnS_GH-K3, a Klebsiella phage with a putative depolymerase-like protein - Ruopeng Cai; Zijing Wang; Gang Wang; Hao Zhang; Mengjun Cheng; Zhimin Guo; Yalu Ji; Hengyu Xi; Xinwu Wang; Yibing Xue; Sadeeq ur Rahman; Changjiang Sun; et al. (Virus Genes, 2019)

Analysis of a Complex Flexural Toppling Failure of Large Underground Caverns in Layered Rock Masses - Ang Li; Feng Dai; Nuwen Xu; Gongkai Gu; Zhonghua Hu (Rock Mechanics and Rock Engineering, 2019)

Evaluation of Ultimate Pullout Capacity of Anchor Cables Embedded in Rock Using a Unified Rupture Shape Model - Qian-qing Zhang; Ruo-feng Feng; Zhen-hao Xu; Shan-wei Liu; Jian-gu Qian (Geotechnical and Geological Engineering, 2019)

Phosphorus forms affect the hyphosphere bacterial community involved in soil organic phosphorus turnover - Fei Wang; Michael A. Kertesz; Gu Feng (Mycorrhiza, 2019)

The neural signatures of egocentric bias in normative decision-making - Chunliang Feng; Xue Feng; Li Wang; Lili Wang; Ruolei Gu; Aiping Ni; Gopikrishna Deshpande; Zhihao Li; Yue-Jia Luo (Brain Imaging and Behavior, 2019)

Geomagnetic jerk extraction based on the covariance matrix - Yan Feng; Yun-Shan Jiang; Jia-Lin Gu; Fan Xu; Yi Jiang; Shuang Liu (Applied Geophysics, 2019)

Genome-wide identification of Ziziphus jujuba TCP transcription factors and their expression in response to infection with jujube witches’ broom phytoplasma - Peng Chen; Jidong Li; Xia Ye; Bin Tan; Xianbo Zheng; Jun Cheng; Wei Wang; Huiyu Wang; Liyuan Gu; Jiancan Feng (Acta Physiologiae Plantarum, 2019)

Sediment transport in the Luanhe River delta: grain size trend analysis - Xiaoxiao Yu; Tiegang Li; Dongqi Gu; Aiping Feng; Shihao Liu; Ping Li; Guoqiang Xu; Wenwen Yan; Zhiwei Zhang; Zhengtao Zhu (Journal of Oceanology and Limnology, 2019)

Maize varieties can strengthen positive plant-soil feedback through beneficial arbuscular mycorrhizal fungal mutualists - Xin-Xin Wang; Ellis Hoffland; Liesje Mommer; Gu Feng; Thomas W. Kuyper (Mycorrhiza, 2019)

Genome-wide identification and characterization of sweet orange (Citrus sinensis) aquaporin genes and their expression in two citrus cultivars differing in drought tolerance - Qingjiang Wei; Qiaoli Ma; Zhangzheng Ma; Gaofeng Zhou; Fangfang Feng; Si Le; Changyu Lei; Qingqing Gu (Tree Genetics & Genomes, 2019)

Self-assessment strategy during contest decisions between male Great Himalayan leaf-nosed bats - Congnan Sun; Chunmian Zhang; Hao Gu; Tinglei Jiang; Jiang Feng (Behavioral Ecology and Sociobiology, 2019)

MiR-1180 from bone marrow-derived mesenchymal stem cells induces glycolysis and chemoresistance in ovarian cancer cells by upregulating the Wnt signaling pathway - Zhuo-Wei Gu; Yi-Feng He; Wen-Jing Wang; Qi Tian; Wen Di (Journal of Zhejiang University-SCIENCE B, 2019)

The links between potassium availability and soil exchangeable calcium, magnesium, and aluminum are mediated by lime in acidic soil - Tianfu Han; Andong Cai; Kailou Liu; Jing Huang; Boren Wang; Dongchu Li; Muhammad Qaswar; Gu Feng; Huimin Zhang (Journal of Soils and Sediments, 2019)

Secondary metabolites from Antarctic marine-derived fungus Penicillium crustosum HDN153086 - Cong-Cong Liu; Zhen-Zhen Zhang; Yan-Yan Feng; Qian-Qun Gu; De-Hai Li; Tian-Jiao Zhu (Natural Product Research, 2019)

Novel anti-cancer agents: design, synthesis, biological activity, molecular docking, and MD simulations of 2, 3, 4, 5-tetrahydro-1H-pyrido-[4,3-b]indole derivatives - Yu Feng; Xingxing Teng; Jinhua Gu; Bangwei Yu; Yan Luo; Lianbao Ye (Medicinal Chemistry Research, 2019)

Nitrapyrin affects the abundance of ammonia oxidizers rather than community structure in a yellow clay paddy soil - Yan Gu; Wenhai Mi; Yinan Xie; Qingxu Ma; Lianghuan Wu; Zhaoping Hu; Feng Dai (Journal of Soils and Sediments, 2019)

Concentration of morpholine residues in major fruits and juices and its dietary exposure in China - Pei Cao; Da-Wei Chen; Jiang Liang; Ping-Gu Wu; Sheng Wen; Jing Wei; Si-Jie Liu; Xi-Mei Wu; Yun-Feng Zhao; Hai-Bin Xu (Food Additives & Contaminants: Part A, 2019)

The arbuscular mycorrhizal fungus Rhizophagus irregularis MUCL 43194 induces the gene expression of citrate synthase in the tricarboxylic acid cycle of the phosphate-solubilizing bacterium Rahnella aquatilis HX2 - Lin Zhang; Jiequn Fan; Gu Feng; Stéphane Declerck (Mycorrhiza, 2019)

Comparative study on mitogenomes of green tide algae - Chuner Cai; Feng Liu; Ting Jiang; Lingke Wang; Rui Jia; Lingjie Zhou; Kai Gu; Jianfeng Ren; Peimin He (Genetica, 2018)

Transcriptomic analysis of porcine PBMCs in response to Actinobacillus pleuropneumoniae reveals the dynamic changes of differentially expressed genes related to immuno-inflammatory responses - Hexiang Jiang; Rining Zhu; Hongtao Liu; Chuntong Bao; Jianfang Liu; Abdalla Eltahir; Paul R. Langford; Diangang Sun; Zhonghua Liu; Changjiang Sun; Jingmin Gu; Wenyu Han; et al. (Antonie van Leeuwenhoek, 2018)

Ultra-stable super-resolution fluorescence cryo-microscopy for correlative light and electron cryo-microscopy - Xiaojun Xu; Yanhong Xue; Buyun Tian; Fengping Feng; Lusheng Gu; Weixing Li; Wei Ji; Tao Xu (Science China Life Sciences, 2018)

Spatial association between landslides and environmental factors over Guizhou Karst Plateau, China - Xi-liu Yue; Shao-hong Wu; Mei Huang; Jiang-bo Gao; Yun-he Yin; Ai-qing Feng; Xiao-ping Gu (Journal of Mountain Science, 2018)

Time is nothing: emotional consistency of autobiographical memory and its neural basis - Rui Xu; Juan Yang; Chunliang Feng; Haiyan Wu; Ruiwang Huang; Qiuli Yang; Zhihao Li; Pengfei Xu; Ruolei Gu; Yue-jia Luo (Brain Imaging and Behavior, 2018)

Circadian clock pathway genes associated with colorectal cancer risk and prognosis - Dongying Gu; Shuwei Li; Shuai Ben; Mulong Du; Haiyan Chu; Zhengdong Zhang; Meilin Wang; Zuo-Feng Zhang; Jinfei Chen (Archives of Toxicology, 2018)

Calpain inhibition attenuates bleomycin-induced pulmonary fibrosis via switching the development of epithelial-mesenchymal transition - Yuan Liu; Bing Liu; Gu-qin Zhang; Jing-feng Zou; Meng-lin Zou; Zhen-shun Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Arbuscular mycorrhizal fungi stimulate organic phosphate mobilization associated with changing bacterial community structure under field conditions - Lin Zhang; Ning Shi; Jiequn Fan; Fei Wang; Timothy S. George; Gu Feng (Environmental Microbiology, 2018)
Summary The extraradical hyphae of arbuscular mycorrhizal fungi (AMF) harbour and interact with a microbial community performing multiple functions. However, how the AMF‐microbiome interaction influences the phosphorus (P) acquisition efficiency of the mycorrhizal pathway is unclear. Here we investigated whether AMF and their hyphal microbiome play a role in promoting organic phosphorus (P) mineralizing under field conditions. We developed an AMF hyphae in‐growth core system for the field using PVC tubes sealed with membrane with different size of pores (30 or 0.45 μm) to allow or deny AMF hyphae access to a patch of organic P in root‐free soil. AMF and their hyphae associated microbiome played a role in enhancing soil organic P mineralization in situ in the field, which was shown to be a function of the change in bacteria community on the hyphae surface. The bacterial communities attached to the AMF hyphae surface were significantly different from those in the bulk soil. Importantly, AMF hyphae recruited bacteria that produced alkaline phosphatase and provided a function that was absent from the hyphae. These results demonstrate the importance of understanding trophic interactions to be able to gain insight into the functional controls of nutrient cycles in the rhizosphere.

Whole-Brain Mapping of Direct Inputs to and Axonal Projections from GABAergic Neurons in the Parafacial Zone - Yun-Ting Su; Meng-Yang Gu; Xi Chu; Xiang Feng; Yan-Qin Yu (Neuroscience Bulletin, 2018)

Isolation and identification of Salmonella pullorum bacteriophage YSP2 and its use as a therapy for chicken diarrhea - Kunyuan Tie; Yuyu Yuan; Shiqing Yan; Xi Yu; Qiuyang Zhang; Huihui Xu; Yang Zhang; Jingmin Gu; Changjiang Sun; Liancheng Lei; Wenyu Han; Xin Feng (Virus Genes, 2018)

Anaerobic biodegradation of partially hydrolyzed polyacrylamide in long-term methanogenic enrichment cultures from production water of oil reservoirs - Hao Hu; Jin-Feng Liu; Cai-Yun Li; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Biodegradation, 2018)

Are aggressive vocalizations the honest signals of body size and quality in female Asian particoloured bats? - Xin Zhao; Tinglei Jiang; Hao Gu; Heng Liu; Congnan Sun; Ying Liu; Jiang Feng (Behavioral Ecology and Sociobiology, 2018)

Identification of Rehmannia glutinosa L. NB-ARC family proteins and their typical changes under consecutive monoculture stress - Aiguo Chen; Li Gu; Mingjie Li; Na Xu; Fajie Feng; Guangliang Liu; Bao Zhang; Daping Gong; Junyi Zhang; Hongyan Liu; Zhongyi Zhang (Acta Physiologiae Plantarum, 2018)

In Vitro-In Vivo Predictive Dissolution-Permeation-Absorption Dynamics of Highly Permeable Drug Extended-Release Tablets via Drug Dissolution/Absorption Simulating System and pH Alteration - Zi-qiang Li; Shuang Tian; Hui Gu; Zeng-guang Wu; Makafui Nyagblordzro; Guo Feng; Xin He (AAPS PharmSciTech, 2018)

Design, synthesis and biological evaluation of novel furoxan-based coumarin derivatives as antitumor agents - Zhuo Zhang; Zhi-Wei Bai; Yong Ling; Li-Qin He; Peng Huang; Hong-Xia Gu; Rong-Feng Hu (Medicinal Chemistry Research, 2018)

Seismic behavior of breakwaters on complex ground by numerical tests: Liquefaction and post liquefaction ground settlements - Linlin Gu; Feng Zhang; Xiaohua Bao; Zhenming Shi; Guanlin Ye; Xianzhang Ling (Earthquake Engineering and Engineering Vibration, 2018)

Effects of an additive (hydroxyapatite–biochar–zeolite) on the chemical speciation of Cd and As in paddy soils and their accumulation and translocation in rice plants - Jiao-Feng Gu; Hang Zhou; Wen-Tao Yang; Pei-Qin Peng; Ping Zhang; Min Zeng; Bo-Han Liao (Environmental Science and Pollution Research, 2018)

Characterization of bacterial composition and diversity in a long-term petroleum contaminated soil and isolation of high-efficiency alkane-degrading strains using an improved medium - Jun Zheng; Jun-Qiao Feng; Lei Zhou; Serge Maurice Mbadinga; Ji-Dong Gu; Bo-Zhong Mu (World Journal of Microbiology and Biotechnology, 2018)

Heavy metal pollution in immobile and mobile components of lentic ecosystems—a review - Ramakrishnan Anu Alias Meena; Palanivel Sathishkumar; Fuad Ameen; Abdull Rahim Mohd Yusoff; Feng Long Gu (Environmental Science and Pollution Research, 2018)

Complete plastid genomes of the genus Ammopiptanthus and identification of a novel 23-kb rearrangement - Lei Feng; Li-Fei Gu; Juan Luo; Ai-Si Fu; Qiong Ding; Siu-Ming Yiu; Jun-Xian He (Conservation Genetics Resources, 2017)

Two new stilbene trimers from Cynodon dactylon - Bi-Jun Li; Yao Liu; Ai-Tong Gu; Qing Zhang; Lei Chen; Shu-Mei Wang; Feng Wang (Natural Product Research, 2017)

Influence of Rapeseed Cake on Iron Plaque Formation and Cd Uptake by Rice (Oryza sativa L.) Seedlings Exposed to Excess Cd - Wen-Tao Yang; Hang Zhou; Jiao-Feng Gu; Qing-ru Zeng; Bo-Han Liao (Bulletin of Environmental Contamination and Toxicology, 2017)

Bioorganic fertilizer maintains a more stable soil microbiome than chemical fertilizer for monocropping - Feng Cai; Guan Pang; Rui-Xia Li; Rong Li; Xiao-Long Gu; Qi-Rong Shen; Wei Chen (Biology and Fertility of Soils, 2017)

Propionate metabolism and diversity of relevant functional genes by in silico analysis and detection in subsurface petroleum reservoirs - Tao Yang; Serge Maurice Mbadinga; Lei Zhou; Shi-Zhong Yang; Jing-Feng Liu; Ji-Dong Gu; Bo-Zhong Mu (World Journal of Microbiology and Biotechnology, 2017)

Glucocorticoid-Potentiated Spinal Microglia Activation Contributes to Preoperative Anxiety-Induced Postoperative Hyperalgesia - Rao Sun; Zhibin Zhao; Jiying Feng; Jinhua Bo; Hui Rong; Yishan Lei; Cui’e Lu; Xiaobao Zhang; Bailing Hou; Yu’e Sun; Yue Liu; Zhengliang Ma; et al. (Molecular Neurobiology, 2017)

Rapid and sensitive detection of Meloidogyne mali by loop-mediated isothermal amplification combined with a lateral flow dipstick - Qian-jin Zhou; Yi Cai; Jian-feng Gu; Xuan Wang; Jiong Chen (European Journal of Plant Pathology, 2017)

Isolation and characterisation of the epothilone gene cluster with flanks from high alkalotolerant strain Sorangium cellulosum (So0157-2) - Zhi-Feng Li; Li-Ping Zhu; Jing-yan Gu; Raghvendra Pratap Singh; Yue-Zhong Li (World Journal of Microbiology and Biotechnology, 2017)

Trichoderma-enriched organic fertilizer can mitigate microbiome degeneration of monocropped soil to maintain better plant growth - Guan Pang; Feng Cai; Ruixia Li; Zheng Zhao; Rong Li; Xiaolong Gu; Qirong Shen; Wei Chen (Plant and Soil, 2017)

Settlement mechanism of piled-raft foundation due to cyclic train loads and its countermeasure - Linlin Gu; Guanlin Ye; Zhen Wang; Xianzhang Ling; Feng Zhang (Earthquake Engineering and Engineering Vibration, 2017)

Preparation and In Vitro Evaluation of a MRI Contrast Agent Based on Aptamer-Modified Gadolinium-Loaded Liposomes for Tumor Targeting - Lan-Xin Zhang; Kun-Feng Li; Huan Wang; Meng-Jie Gu; Li-Si Liu; Zhuo-Zhao Zheng; Nan-Yin Han; Zhen-Jun Yang; Tian-Yuan Fan (AAPS PharmSciTech, 2017)

Transcriptome analysis reveals metabolic alteration due to consecutive monoculture and abiotic stress stimuli in Rehamannia glutinosa Libosch - Yunhe Tian; Fajie Feng; Bao Zhang; Mingjie Li; Fengqing Wang; Li Gu; Aiguo Chen; Zhanjie Li; Wenbo Shan; Xiaoran Wang; Xinjian Chen; Zhongyi Zhang (Plant Cell Reports, 2017)

Distribution of heavy metals in maize and mudflat saline soil amended by sewage sludge - Yan-Chao Bai; Wen-Gang Zuo; Hai-Tao Zhao; Li-Juan Mei; Chuan-Hui Gu; Yong-Xiang Guan; Xu-Kui Wang; Min-Jing Gu; Cai-Yun Zang; Yu-Hua Shan; Ke Feng (Journal of Soils and Sediments, 2017)

Immune recovery after fluid resuscitation in rats with severe hemorrhagic shock - Feng Yao; Yuan-qiang Lu; Jiu-kun Jiang; Lin-hui Gu; Han-zhou Mou (Journal of Zhejiang University-SCIENCE B, 2017)

Pharmacological Inhibition of PERK Attenuates Early Brain Injury After Subarachnoid Hemorrhage in Rats Through the Activation of Akt - Feng Yan; Shenglong Cao; Jianru Li; Brandon Dixon; Xiaobo Yu; Jingyin Chen; Chi Gu; Wang Lin; Gao Chen (Molecular Neurobiology, 2017)

Expression and functional activity of bitter taste receptors in primary renal tubular epithelial cells and M-1 cells - Jie Liang; Fuxue Chen; Fu Gu; Xin Liu; Feng Li; Dongshu Du (Molecular and Cellular Biochemistry, 2017)

A modified Hoek-Brown failure criterion considering the damage to reservoir bank slope rocks under water saturation-dehydration circulation - Xin-gang Wang; Jia-ding Wang; Tian-Feng Gu; Bao-qin Lian (Journal of Mountain Science, 2017)

Interdecadal transition in the relationship between the western Pacific subtropical high and sea surface temperature - Bohui Gu; Zhihai Zheng; Guolin Feng; Xujia Wang (International Journal of Climatology, 2017)
The western Pacific subtropical high ( WPSH ) and sea surface temperatures have experienced marked interdecadal changes. However, whether the relationships between the WPSH and sea surface temperature forcings ( SSTFs ) have also experienced an interdecadal transition remains unclear. This study analyses the interdecadal shift in the relationship between the WPSH and SSTFs . The results clearly reveal the occurrence of two interdecadal transitions in the relationship between the leading empirical orthogonal function modes, which represent the intensity of the WPSH and the SSTFs : one in approximately 1976–1977 and the other in 1993–1994. The positive first principal component is closely related to the equatorial eastern and central Pacific ( EECP ) warming and the western North Pacific ( WNP ) cooling in spring and summer of the three periods. The discharging process of the ‘Indian Ocean Capacitor Effect’ in summer was suppressed by the downdraft during the periods 1978–1992 and 1995–2013, which caused the tropical Indian Ocean ( TIO ) warming to have little influence on the WNP anomalous anticyclone ( WNPAC ) in summer. The positive second principal component corresponds to significantly positive sea surface temperature anomalies in the TIO , the maritime continent, the WNP , the North Pacific cooling in spring and summer, and the EECP cooling in the summer, while it is significantly related to only the positive‐phase North Atlantic tripole ( NAT ) in the spring in the years 1954–1975. The enhancement of the WNPAC by the NAT was partly offset by the tropical North Atlantic warming with a positive tropospheric temperature anomaly. Additionally, an anticyclone over the North Pacific Ocean accelerated the phase shift of El Niño/Southern Oscillation from El Niño to La Niña in the spring in the years 1995–2013.

The mobile monitoring of black carbon and its association with roadside data in the Chinese megacity of Shanghai - Xiao-ning Lei; Ji-wei Bian; Guang-li Xiu; Xiao-feng Hu; Xin-sheng Gu; Qing-gen Bian (Environmental Science and Pollution Research, 2017)

Substrate color preference and feeding by juvenile Chinese sturgeon Acipenser sinensis: exploration of a behavioral adaptation - Xiaolian Gu; Ping Zhuang; Feng Zhao; Xiaotao Shi; Xiaorong Huang; Guangpeng Feng; Tao Zhang; Jianyi Liu; Longzhen Zhang; Boyd Kynard (Environmental Biology of Fishes, 2017)

Assessment of code bias variations of BDS triple-frequency signals and their impacts on ambiguity resolution for long baselines - Yidong Lou; Xiaopeng Gong; Shengfeng Gu; Fu Zheng; Yanming Feng (GPS Solutions, 2017)

Towards a semi-empirical model of the sea ice thickness based on hyperspectral remote sensing in the Bohai Sea - Shuai Yuan; Wei Gu; Chengyu Liu; Feng Xie (Acta Oceanologica Sinica, 2017)

Transcriptome analysis reveals that constant heat stress modifies the metabolism and structure of the porcine longissimus dorsi skeletal muscle - Yue Hao; Yuejin Feng; Peige Yang; Yanjun Cui; Jiru Liu; Chunhe Yang; Xianhong Gu (Molecular Genetics and Genomics, 2016)

Brain functional network abnormality extends beyond the sensorimotor network in brachial plexus injury patients - Jun-Tao Feng; Han-Qiu Liu; Xu-Yun Hua; Yu-Dong Gu; Jian-Guang Xu; Wen-Dong Xu (Brain Imaging and Behavior, 2016)

Increasing phosphorus concentration in the extraradical hyphae of Rhizophagus irregularis DAOM 197198 leads to a concomitant increase in metal minerals - Lin Zhang; Caiyun Jiang; Jiachao Zhou; Stéphane Declerck; Changyan Tian; Gu Feng (Mycorrhiza, 2016)

Impacts of rapeseed dregs on Cd availability in contaminated acid soil and Cd translocation and accumulation in rice plants - Wen-Tao Yang; Jiao-Feng Gu; Jia-Ling Zou; Hang Zhou; Qing-Ru Zeng; Bo-Han Liao (Environmental Science and Pollution Research, 2016)

Multi-GNSS precise point positioning with raw single-frequency and dual-frequency measurement models - Yidong Lou; Fu Zheng; Shengfeng Gu; Charles Wang; Hailin Guo; Yanming Feng (GPS Solutions, 2016)

Chitosan scaffolds induce human dental pulp stem cells to neural differentiation: potential roles for spinal cord injury therapy - Jinlong Zhang; Xiaohui Lu; Guijuan Feng; Zhifeng Gu; Yuyu Sun; Guofeng Bao; Guanhua Xu; Yuanzhou Lu; Jiajia Chen; Lingfeng Xu; Xingmei Feng; Zhiming Cui (Cell and Tissue Research, 2016)

Rab27b is Involved in Lysosomal Exocytosis and Proteolipid Protein Trafficking in Oligodendrocytes - Yun-Tian Shen; Yun Gu; Wen-Feng Su; Jing-fei Zhong; Zi-Han Jin; Xiao-Song Gu; Gang Chen (Neuroscience Bulletin, 2016)

Comparative genomic analysis of Lactobacillus plantarum ZJ316 reveals its genetic adaptation and potential probiotic profiles - Ping Li; Xuan Li; Qing Gu; Xiu-yu Lou; Xiao-mei Zhang; Da-feng Song; Chen Zhang (Journal of Zhejiang University-SCIENCE B, 2016)

Production of porcine TNFα by ADAM17-mediated cleavage negatively regulates porcine reproductive and respiratory syndrome virus infection - Ren Li; Longjun Guo; Weihong Gu; Xiaolei Luo; Jian Zhang; Yunfei Xu; Zhijun Tian; Li Feng; Yue Wang (Immunologic Research, 2016)

On the relationship between the winter Eurasian teleconnection pattern and the following summer precipitation over China - Junhu Zhao; Liu Yang; Bohui Gu; Jie Yang; Guolin Feng (Advances in Atmospheric Sciences, 2016)

A residue substitution in the plastid ribosomal protein L12/AL1 produces defective plastid ribosome and causes early seedling lethality in rice - Dong-sheng Zhao; Chang-quan Zhang; Qian-feng Li; Qing-qing Yang; Ming-hong Gu; Qiao-quan Liu (Plant Molecular Biology, 2016)

Minocycline Protects Against NLRP3 Inflammasome-Induced Inflammation and P53-Associated Apoptosis in Early Brain Injury After Subarachnoid Hemorrhage - Jianru Li; Jingsen Chen; Hangbo Mo; Jingyin Chen; Cong Qian; Feng Yan; Chi Gu; Qiang Hu; Lin Wang; Gao Chen (Molecular Neurobiology, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Regulation of carbon metabolic fluxes in response to CO2 supplementation in phototrophic Chlorella vulgaris: a cytomic and biochemical study - Huifeng Peng; Dong Wei; Feng Chen; Gu Chen (Journal of Applied Phycology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Differential distribution patterns of ammonia-oxidizing archaea and bacteria in acidic soils of Nanling National Nature Reserve forests in subtropical China - Xian-Hua Gan; Fang-Qiu Zhang; Ji-Dong Gu; Yue-Dong Guo; Zhao-Qing Li; Wei-Qiang Zhang; Xiu-Yu Xu; Yi Zhou; Xiao-Ying Wen; Guo-Guang Xie; Yong-Feng Wang (Antonie van Leeuwenhoek, 2016)

Indigenous arbuscular mycorrhizal fungi can alleviate salt stress and promote growth of cotton and maize in saline fields - Shenglin Liu; Xiuli Guo; Gu Feng; Baidengsha Maimaitiaili; Jialin Fan; Xinhua He (Plant and Soil, 2016)

Trimeric autotransporter adhesins contribute to Actinobacillus pleuropneumoniae pathogenicity in mice and regulate bacterial gene expression during interactions between bacteria and porcine primary alveolar macrophages - Wanhai Qin; Lei Wang; Ruidong Zhai; Qiuyue Ma; Jianfang Liu; Chuntong Bao; Hu Zhang; Changjiang Sun; Xin Feng; Jingmin Gu; Chongtao Du; Wenyu Han; et al. (Antonie van Leeuwenhoek, 2016)

Characterisation of aroma profiles of commercial sufus by odour activity value, gas chromatography-olfactometry, aroma recombination and omission studies - Zuobing Xiao; Yi Shang; Feng Chen; Yunwei Niu; Yongbo Gu; Shengjiang Liu; Jiancai Zhu (Natural Product Research, 2015)

The Diagnosis Pattern of Mid-Trimester Fetal Chromosomal Aneuploidy in Xuzhou and the Clinical Applications - Yuan Fang; Guangming Wang; Chuanxia Wang; Feng Suo; Maosheng Gu; Yujuan Xia (Cell Biochemistry and Biophysics, 2015)

Comparison of microhabitats and foraging strategies between the captive-born Zhangxiang and wild giant pandas: implications for future reintroduction - Miaowen Lei; Shibin Yuan; Zisong Yang; Mingsheng Hong; Xuyu Yang; Xiaodong Gu; Feng Huang; Zejun Zhang (Environmental Science and Pollution Research, 2015)

GJB2 as Well as SLC26A4 Gene Mutations are Prominent Causes for Congenital Deafness - Yuan Fang; Maosheng Gu; Chuanxia Wang; Feng Suo; Guangming Wang; Yujuan Xia (Cell Biochemistry and Biophysics, 2015)

Generation and characterization of Brassica rapa ssp. pekinensis – B. oleracea var. capitata monosomic and disomic alien addition lines - AI XIA GU; SHU XING SHEN; YAN HUA WANG; JIAN JUN ZHAO; SHU XIN XUAN; XUE PING CHEN; XIAO FENG LI; SHUANG XIA LUO; YU JING ZHAO (Journal of Genetics, 2015)

Crop yield and soil organic matter after long-term straw return to soil in China - Jinzhou Wang; Xiujun Wang; Minggang Xu; Gu Feng; Wenju Zhang; Chang’ai Lu (Nutrient Cycling in Agroecosystems, 2015)

Genome sequencing and analysis of an Escherichia coli phage vB_EcoM-ep3 with a novel lysin, Lysep3 - Meng Lv; Shuang Wang; Guangmou Yan; Changjiang Sun; Xin Feng; Jingmin Gu; Wenyu Han; Liancheng Lei (Virus Genes, 2015)

The biological effects of hsa-miR-1908 in human adipocytes - Lei Yang; Chun-mei Shi; Ling Chen; Ling-xia Pang; Guang-feng Xu; Nan Gu; Li-jun Zhu; Xi-rong Guo; Yu-hui Ni; Chen-bo Ji (Molecular Biology Reports, 2015)

Infectivity and community composition of arbuscular mycorrhizal fungi from different soil depths in intensively managed agricultural ecosystems - Jingping Gai; Wenjun Gao; Lei Liu; Qing Chen; Gu Feng; Junling Zhang; Peter Christie; Xiaolin Li (Journal of Soils and Sediments, 2015)

Detection of spotted fever group Rickettsiae in ticks from Zhejiang Province, China - Jimin Sun; Junfen Lin; Zhenyu Gong; Yue Chang; Xiaodong Ye; Shiping Gu; Weilong Pang; Chengwei Wang; Xiaohua Zheng; Juan Hou; Feng Ling; Xuguang Shi; et al. (Experimental and Applied Acarology, 2015)

Bacillus vanillea sp. nov., Isolated from the Cured Vanilla Bean - Yong-gan Chen; Feng-lin Gu; Ji-hua Li; Fei Xu; Shu-zhen He; Yi-ming Fang (Current Microbiology, 2015)

Niche specificity of ammonia-oxidizing archaeal and bacterial communities in a freshwater wetland receiving municipal wastewater in Daqing, Northeast China - Kwok-Ho Lee; Yong-Feng Wang; Hui Li; Ji-Dong Gu (Ecotoxicology, 2014)

Distribution patterns of ammonia-oxidizing bacteria and anammox bacteria in the freshwater marsh of Honghe wetland in Northeast China - Kwok-Ho Lee; Yong-Feng Wang; Guo-Xia Zhang; Ji-Dong Gu (Ecotoxicology, 2014)

Multi-time scale analysis of runoff at the Yangtze estuary based on the Morlet Wavelet Transform method - Cui-ping Kuang; Ping Su; Jie Gu; Wu-jun Chen; Jian-le Zhang; Wan-lei Zhang; Yong-feng Zhang (Journal of Mountain Science, 2014)

Birth intervention and non-maternal infant-handling during parturition in a nonhuman primate - Wenshi Pan; Tieliu Gu; Yue Pan; Chunguang Feng; Yu Long; Yi Zhao; Hao Meng; Zuhong Liang; Meng Yao (Primates, 2014)

Bio-beads with immobilized anaerobic bacteria, zero-valent iron, and active carbon for the removal of trichloroethane from groundwater - Ya-Zhen Zhou; Jie Yang; Xiao-Li Wang; Yue-Qing Pan; Hui Li; Dong Zhou; Yong-Di Liu; Ping Wang; Ji-Dong Gu; Qiang Lu; Yue-Feng Qiu; Kuang-Fei Lin (Environmental Science and Pollution Research, 2014)

Heterochronic bilateral ectopic pregnancy after ovulation induction - Bo Zhu; Gu-feng Xu; Yi-feng Liu; Fan Qu; Wei-miao Yao; Yi-min Zhu; Hui-juan Gao; Dan Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Autumn living coccolithophores in the Yellow Sea and the East China Sea - Jie Bai; Xiaoyao Gu; Yuanyuan Feng; Wensheng Jiang; Haiyan Jin; Jianfang Chen; Jun Sun (Acta Oceanologica Sinica, 2014)

Paleo-productivity evolution across the Permian-Triassic boundary and quantitative calculation of primary productivity of black rock series from the Dalong Formation, South China - Jun Shen; Lian Zhou; QingLai Feng; MuHui Zhang; Yong Lei; Ning Zhang; JianXin Yu; SongZhu Gu (Science China Earth Sciences, 2014)

Influence of casein phosphopeptide-amorphous calcium phosphate application, smear layer removal, and storage time on resin-dentin bonding - Jun Lin; Wei-ying Zheng; Peng-ruo-feng Liu; Ning Zhang; Hui-ping Lin; Yi-jing Fan; Xin-hua Gu; Oliver Vollrath; Christian Mehl (Journal of Zhejiang University-SCIENCE B, 2014)

Role of cosubstrate and bioaccessibility played in the enhanced anaerobic biodegradation of organochlorine pesticides (OCPs) in a paddy soil by nitrate and methyl-β-cyclodextrin amendments - Mao Ye; Mingming Sun; Ni Ni; Yinwen Chen; Zongtang Liu; Chengang Gu; Yongrong Bian; Feng Hu; Huixin Li; Fredrick Orori Kengara; Xin Jiang (Environmental Science and Pollution Research, 2014)

Is right ventricular mid-septal pacing superior to apical pacing in patients with high degree atrio-ventricular block and moderately depressed left ventricular function? - Kang Chen; Ye Mao; Shao-hua Liu; Qiong Wu; Qing-zhi Luo; Wen-qi Pan; Qi Jin; Ning Zhang; Tian-you Ling; Ying Chen; Gang Gu; Wei-feng Shen; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Repeated lipopolysaccharide stimulation promotes cellular senescence in human dental pulp stem cells (DPSCs) - Xingmei Feng; Guijuan Feng; Jing Xing; Biyu Shen; Wei Tan; Dan Huang; Xiaohui Lu; Tao Tao; Jinlong Zhang; Liren Li; Zhifeng Gu (Cell and Tissue Research, 2014)

17β-Estradiol protects against apoptosis induced by levofloxacin in rat nucleus pulposus cells by upregulating integrin α2β1 - Si-Dong Yang; Lei Ma; Ti-Xin Gu; Wen-Yuan Ding; Feng Zhang; Yong Shen; Ying-Ze Zhang; Da-Long Yang; Di Zhang; Ya-Peng Sun; Yan-Li Song (Apoptosis, 2014)

Isolation of a WD40-repeat gene regulating anthocyanin biosynthesis in storage roots of purple-fleshed sweet potato - Wei Dong; Liangliang Niu; Jintao Gu; Feng Gao (Acta Physiologiae Plantarum, 2014)

Effects of Dryout and Inflow Water Quality on Mercury Methylation in a Constructed Wetland - Shulu Feng; Zhijiu Ai; Shimei Zheng; Binhe Gu; Yuncong Li (Water, Air, & Soil Pollution, 2014)

Endogenous Subventricular Zone Neural Progenitors Contribute to the Formation and Hyperexcitability of Experimental Model of Focal Microgyria - Hai-Feng Shu; Yong-Qin Kuang; Shi-Yong Liu; Si-Xun Yu; Chun-Qing Zhang; Da-Hai Zheng; Jian-Wen Gu; Hui Yang (Journal of Molecular Neuroscience, 2014)

Investigating soil moisture sensitivity to precipitation and evapotranspiration errors using SiB2 model and ensemble Kalman filter - Xiaolei Fu; Zhongbo Yu; Lifeng Luo; Haishen Lü; Di Liu; Qin Ju; Tao Yang; Feng Xu; Huanghe Gu; Chuanguo Yang; Jingwen Chen; Ting Wang (Stochastic Environmental Research and Risk Assessment, 2014)

Cloning of Catechol 2,3-Dioxygenase Gene and Construction of a Stable Genetically Engineered Strain for Degrading Crude Oil - Yun Xie; Feng Yu; Qi Wang; Xin Gu; Wuling Chen (Indian Journal of Microbiology, 2014)

Preparation of transgenic Dunaliella salina for immunization against white spot syndrome virus in crayfish - Shuying Feng; Wenpo Feng; Ling Zhao; Huihui Gu; Qinghua Li; Ke Shi; Sanxing Guo; Nannan Zhang (Archives of Virology, 2014)

Wnt/β-catenin signaling mediates the senescence of bone marrow-mesenchymal stem cells from systemic lupus erythematosus patients through the p53/p21 pathway - Zhifeng Gu; Wei Tan; Guijuan Feng; Yan Meng; Biyu Shen; Hong Liu; Chun Cheng (Molecular and Cellular Biochemistry, 2014)

Cell cycle perturbations induced by human herpesvirus 6 infection and their effect on virus replication - Lingyun Li; Bin Gu; Feng Zhou; Jing Chi; Dongju Feng; Fangyi Xie; Fang Wang; Changyan Ma; Meng Li; Jinfeng Wang; Kun Yao (Archives of Virology, 2014)

Point-line-area-volume index system of land subsidence and application in Ningbo, China - Jianxiu Wang; Xueying Gu; Yukun Jiang; Tianrong Huang; Bo Feng (Natural Hazards, 2013)

Association between the −1438G/A and T102C polymorphisms of 5-HT2A receptor gene and obstructive sleep apnea: a meta-analysis - Ying Wu; Hong-Bing Liu; Ming Ding; Jian-Nan Liu; Xuan-Feng Zhu; Jian-Hua Gu; Gan Lu (Molecular Biology Reports, 2013)

A reference station-based GNSS computing mode to support unified precise point positioning and real-time kinematic services - Yanming Feng; Shengfeng Gu; Chuang Shi; Chris Rizos (Journal of Geodesy, 2013)

Curcumin Ameliorates the Permeability of the Blood–Brain Barrier During Hypoxia by Upregulating Heme Oxygenase-1 Expression in Brain Microvascular Endothelial Cells - Yan-feng Wang; Yan-ting Gu; Guang-hua Qin; Lei Zhong; Ying-nan Meng (Journal of Molecular Neuroscience, 2013)

Prediction of protein amidation sites by feature selection and analysis - Weiren Cui; Shen Niu; Lulu Zheng; Lele Hu; Tao Huang; Lei Gu; Kaiyan Feng; Ning Zhang; Yudong Cai; Yixue Li (Molecular Genetics and Genomics, 2013)

Mycorrhizal responsiveness of maize (Zea mays L.) genotypes as related to releasing date and available P content in soil - Qun Chu; Xinxin Wang; Yang Yang; Fanjun Chen; Fusuo Zhang; Gu Feng (Mycorrhiza, 2013)

Rotavirus infection and its genetic characterization in non-hospitalized adults with acute gastroenteritis in Shanghai, China - Zhen Shen; Gang Wang; Wanju Zhang; Fangxing Qian; Yang Li; Min Zhang; Shimin Gu; Moying Wang; Feng Lin; Yunwen Hu; Zhenghong Yuan; Jun Zhang (Archives of Virology, 2013)

Cloud-Aerosol-Radiation (CAR) ensemble modeling system: Overall accuracy and efficiency - Feng Zhang; Xin-Zhong Liang; Qingcun Zeng; Yu Gu; Shenjian Su (Advances in Atmospheric Sciences, 2013)

Selection of Antiviral Peptides Against Mink Enteritis Virus Using a Phage Display Peptide Library - Qingming Zhang; Yuping Wang; Qun Ji; Jingmin Gu; Shanshan Liu; Xin Feng; Changjiang Sun; Yingying Li; Liancheng Lei (Current Microbiology, 2013)

Roles of Wnt/β-Catenin Signaling in Retinal Neuron-Like Differentiation of Bone Marrow Mesenchymal Stem Cells from Nonobese Diabetic Mice - Yue Xu; Zhifeng Gu; Biyu Shen; Guofeng Xu; Tianqiu Zhou; Jinxia Jiang; Jing Xing; Suzhe Liu; Man Li; Wei Tan; Guijuan Feng; Aimin Sang; et al. (Journal of Molecular Neuroscience, 2013)

Formaldehyde Impairs Learning and Memory Involving the Disturbance of Hydrogen Sulfide Generation in the Hippocampus of Rats - Xiao-Qing Tang; Yuan-Yuan Zhuang; Ping Zhang; Heng-Rong Fang; Cheng-Fang Zhou; Hong-Feng Gu; Hui Zhang; Chun-Yan Wang (Journal of Molecular Neuroscience, 2013)

Contribution of hydrogen sulfide and nitric oxide to exercise-induced attenuation of aortic remodeling and improvement of endothelial function in spontaneously hypertensive rats - Qi Gu; Bing Wang; Xiao-Feng Zhang; Yan-Ping Ma; Jian-Dong Liu; Xiao-Ze Wang (Molecular and Cellular Biochemistry, 2012)

Overexpression of allene oxide cyclase promoted tanshinone/phenolic acid production in Salvia miltiorrhiza - Xiao-Ce Gu; Jun-Feng Chen; Ying Xiao; Peng Di; Hong-Jiao Xuan; Xun Zhou; Lei Zhang; Wan-Sheng Chen (Plant Cell Reports, 2012)

GSA: a GPU-accelerated structure similarity algorithm and its application in progressive virtual screening - Xin Yan; Qiong Gu; Feng Lu; Jiabo Li; Jun Xu (Molecular Diversity, 2012)

Mitochondrial dysfunction and cellular metabolic deficiency in Alzheimer’s disease - Xue-Mei Gu; Han-Chang Huang; Zhao-Feng Jiang (Neuroscience Bulletin, 2012)

Neuronal autophagy in cerebral ischemia - Feng Xu; Jin-Hua Gu; Zheng-Hong Qin (Neuroscience Bulletin, 2012)

Role of ROS/RhoA/PI3K/PKB Signaling in NS1619-Mediated Blood–Tumor Barrier Permeability Increase - Yan-Ting Gu; Yi-Xue Xue; Yan-Feng Wang; Jin-Hui Wang; Qian-Ru ShangGuan; Jia-Xu Zhang; Li-Juan Qin (Journal of Molecular Neuroscience, 2012)

Genomic dissection and prioritizing of candidate genes of QTL for regulating spontaneous arthritis on chromosome 1 in mice deficient for interleukin-1 receptor antagonist - YANHONG CAO; JIFEI ZHANG; YAN JIAO; JIAN YAN; FENG JIAO; XIAOYUN LIU; ROBERT W. WILLIAMS; KAREN A. HASTY; JOHN M. STUART; WEIKUAN GU (Journal of Genetics, 2012)

The cloning of growth associated protein 43 of Gekko japonicus and its effect on cell morphology - Xiao Feng; Youlang Zhou; Mei Liu; Xingxing Gu; Yongjun Wang; Fei Ding; Xiaosong Gu; Yan Liu (Molecular Biology Reports, 2012)

Effect of intensive multifactorial treatment on the intima-media thickness of large arteries in patients with new-onset type 2 diabetes mellitus - Xiao-hong Zhao; Zhe-rong Xu; Qin Zhang; Hai-feng Gu; Yun-mei Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Development of basal endosperm transfer cells in Sorghum bicolor (L.) Moench and its relationship with caryopsis growth - Hui-Hui Wang; Zhong Wang; Feng Wang; Yun-Jie Gu; Zhi Liu (Protoplasma, 2012)

Characterization, and expression profile of a phenylalanine ammonia lyase gene from Jatropha curcas L. - Jihai Gao; Shuwen Zhang; Feng Cai; Xiaojiang Zheng; Na Lin; Xiaobo Qin; Yangchao Ou; Xiaoping Gu; Xihong Zhu; Ying Xu; Fang Chen (Molecular Biology Reports, 2012)

In vitro and in vivo evaluation of ribavirin and pleconaril antiviral activity against enterovirus 71 infection - Guofeng Zhang; Feng Zhou; Bin Gu; Chuanling Ding; Dongju Feng; Fangyi Xie; Jinfeng Wang; Chun Zhang; Qingxian Cao; Yinlai Deng; Weixing Hu; Kun Yao (Archives of Virology, 2012)

Larval settlement and metamorphosis of the mussel Mytilus coruscus in response to natural biofilms - Chong Wang; Wei-Yang Bao; Zhong-Qi Gu; Yi-Feng Li; Xiao Liang; Yun Ling; Sheng-Li Cai; He-Ding Shen; Jin-Long Yang (Biofouling, 2012)

Dietary salt modulates the sodium chloride cotransporter expression likely through an aldosterone-mediated WNK4-ERK1/2 signaling pathway - Lingyun Lai; Xiuyan Feng; Defeng Liu; Jing Chen; Yiqian Zhang; Bowen Niu; Yong Gu; Hui Cai (Pflügers Archiv - European Journal of Physiology, 2012)

Studies revealing bioremediation potential of the strain Burkholderia sp. GB-01 for abamectin contaminated soils - Shinawar Waseem Ali; Fang-bo Yu; Lian-tai Li; Xiao-hui Li; Li-feng Gu; Jian-dong Jiang; Shun-peng Li (World Journal of Microbiology and Biotechnology, 2012)

A Comparative Study of the Preventive Effects of Mitomycin C and Chitosan on Intraarticular Adhesion after Knee Surgery in Rabbits - Wang Jingcheng; Yan Lianqi; Sun Yu; Wang Daxin; Dai Shanhe; Yu Tangyun; Gu Jiaxiang; Jiang Baichuan; Feng Xinmin; Hu Hansheng; Wang Qiang; Yin Bangliang; et al. (Cell Biochemistry and Biophysics, 2012)

Synergistic interactions between Glomus mosseae and Bradyrhizobium japonicum in enhancing proton release from nodules and hyphae - Xiaodong Ding; Xinhua Sui; Fang Wang; Junhua Gao; Xinhua He; Fusuo Zhang; Juncheng Yang; Gu Feng (Mycorrhiza, 2012)

Positive feedback between acidification and organic phosphate mineralization in the rhizosphere of maize (Zea mays L.) - Xiaodong Ding; Li Fu; Chenjia Liu; Fanjun Chen; Ellis Hoffland; Jianbo Shen; Fusuo Zhang; Gu Feng (Plant and Soil, 2011)

The impact of iron oxide magnetic nanoparticles on the soil bacterial community - Shiying He; Youzhi Feng; Hongxuan Ren; Yu Zhang; Ning Gu; Xiangui Lin (Journal of Soils and Sediments, 2011)

Semi-supervised joint spatio-temporal feature selection for P300-based BCI speller - Jinyi Long; Zhenghui Gu; Yuanqing Li; Tianyou Yu; Feng Li; Ming Fu (Cognitive Neurodynamics, 2011)

Temporal and Spatial Expression of Cyclin H in Rat Spinal Cord Injury - Gang Wu; Jianhua Cao; Chen Peng; Huiguang Yang; Zhiming Cui; Jian Zhao; Qiyun Wu; Jiangli Han; Honghui Li; Xingxing Gu; Feng Zhang (NeuroMolecular Medicine, 2011)

On-site growth response of a desert ephemeral plant, Plantago minuta, to indigenous arbuscular mycorrhizal fungi in a central Asia desert - Tao Zhang; Yu Sun; Yongchun Song; Changyan Tian; Gu Feng (Symbiosis, 2011)

Trigonella arcuata-associated rhizobia—an Ensifer (Sinorhizobium) meliloti population adapted to a desert environment - Yu Rong He; Jing Yu Wang; En Tao Wang; Gu Feng; Yue Li Chang; Xin Hua Sui; Wen Xin Chen (Plant and Soil, 2011)

Imprinting and expression analysis of a non-coding RNA gene in the mouse Dlk1-Dio3 domain - Feng Wei Zhang; Tie Bo Zeng; Zheng Bin Han; Hong Juan He; Yan Chen; Ning Gu; Hui Jie Jiang; Qiong Wu (Journal of Molecular Histology, 2011)

Erratum to: Species, types, distribution, and economic potential of halophytes in China - Kefu Zhao; Jie Song; Gu Feng; Meng Zhao; Jinping Liu (Plant and Soil, 2011)

Species, types, distribution, and economic potential of halophytes in China - Kefu Zhao; Jie Song; Gu Feng; Meng Zhao; Jinping Liu (Plant and Soil, 2011)

Accumulation of ions during seed development under controlled saline conditions of two Suaeda salsa populations is related to their adaptation to saline environments - Xin Li; Xiaodong Zhang; Jie Song; Hai Fan; Gu Feng; Baoshan Wang (Plant and Soil, 2011)

Efficient Intracellular Gene Delivery Using the Formulation Composed of Poly (L-glutamic Acid) Grafted Polyethylenimine and Histone - Jingjing Deng; Yuting Wen; Cuifeng Wang; Shirong Pan; Huaiyu Gu; Xin Zeng; Lina Han; Yuefang Zhao; Min Feng; Chuanbin Wu (Pharmaceutical Research, 2011)

Ability of multicellular salt glands in Tamarix species to secrete Na+ and K+ selectively - HaiYan Ma; ChangYan Tian; Gu Feng; JunFeng Yuan (Science China Life Sciences, 2011)

Association of the NFKBIA gene polymorphisms with susceptibility to autoimmune and inflammatory diseases: a meta-analysis - Guo-Long Zhang; Yan-Feng Zou; Xiao-Liang Feng; He-Jian Shi; Xu-Feng Du; Min-Hua Shao; Yong Gu; Qing Zhou (Inflammation Research, 2011)

Slit2/Robo1 signaling in glioma migration and invasion - Yun Xu; Li Wen-Liang; Fu Li; Gu Feng; Ma Yong-Jie (Neuroscience Bulletin, 2010)

VKORC1-1639G>A, CYP2C9, EPHX1691A>G genotype, body weight, and age are important predictors for warfarin maintenance doses in patients with mechanical heart valve prostheses in southwest China - Qiang Gu; Yan Kong; Jörn Schneede; Ying-Bin Xiao; Lin Chen; Qian-Jin Zhong; Xue-Feng Wang; Jia Hao; Bai-Cheng Chen; Jing-Jin Chen (European Journal of Clinical Pharmacology, 2010)

Kinetic analysis of oxytetracycline residues in Chinese mitten crab, Eriocheir sinensis, muscle following intramuscular administration - Q Feng; T Gao; H Ji; X Jiang; T Liang; W Gu; G Wu; G Gao; W Wang (Journal of Fish Diseases, 2010)
Crab culture is a very important economic industry in China. An epidemic of tremor disease of Chinese mitten crabs, Eriocheir sinensis, has become a serious problem in recent years. A spiroplasm has been proved to be the causative agent of this disease. Oxytetracycline (OTC) is used widely in aquaculture and was confirmed to be very effective against this pathogen. In this study, the distribution and depletion patterns of OTC in crab muscle were evaluated following single intramuscular doses of 2, 8 and 40 mg kg −1 body weight. OTC was detected with a validated HPLC method. Concentration–time profiles were well described by a three‐compartment model with first‐order absorption after a single dose of 8 and 40 mg kg −1 . For comparison, a non‐compartment model was employed. A withdrawal time of 48.29 and 55.92 days was suggested prior to consumption after receiving 8 and 40 mg kg −1 . A recommended therapeutic dose of OTC in theory was calculated to be 36.37 mg kg −1 . OTC was distributed well throughout the body. The elimination of OTC in muscle was slower compared with fish and other crustaceans. A dose of 40 mg kg −1 is suggested for practical use.

Effects of NO 3 − -N on the growth and salinity tolerance of Tamarix laxa Willd - Xiaodong Ding; Changyan Tian; Shirong Zhang; Jie Song; Fusuo Zhang; Guohua Mi; Gu Feng (Plant and Soil, 2010)

Potential Challenges of Climate Change to Orchid Conservation in a Wild Orchid Hotspot in Southwestern China - Hong Liu; Chang-Lin Feng; Yi-Bo Luo; Bao-Shan Chen; Zhong-Sheng Wang; Hong-Ya Gu (The Botanical Review, 2010)

The qSD12 underlying gene promotes abscisic acid accumulation in early developing seeds to induce primary dormancy in rice - Xing-You Gu; Tianlei Liu; Jiuhuan Feng; Jeffrey C. Suttle; James Gibbons (Plant Molecular Biology, 2010)

Efficient derivation of Chinese human embryonic stem cell lines from frozen embryos - Chunliang Li; Ying Yang; Xiaowei Lu; Yijuan Sun; Junjie Gu; Yun Feng; Ying Jin (In Vitro Cellular & Developmental Biology - Animal, 2010)

Quantitative trait loci for tibial bone strength in C57BL/6J and C3H/HeJ inbred strains of mice - Feng Jiao; Hank Chiu; Yan Jiao; Waldemar G. de Rijk; Xinmin Li; Eugene C. Eckstein; Wesley G. Beamer; Weikuan Gu (Journal of Genetics, 2010)

Validation of Candidate Reference Genes for the Accurate Normalization of Real-Time Quantitative RT-PCR Data in Rice During Seed Development - Qian-Feng Li; Samuel S. M. Sun; Ding-Yang Yuan; Heng-Xiu Yu; Ming-Hong Gu; Qiao-Quan Liu (Plant Molecular Biology Reporter, 2010)

Molecular Modeling and Affinity Determination of scFv Antibody: Proper Linker Peptide Enhances Its Activity - Xin Gu; Xiaoling Jia; Jiannan Feng; Beifen Shen; Ying Huang; Shusheng Geng; Yingxun Sun; Yugang Wang; Yan Li; Mian Long (Annals of Biomedical Engineering, 2010)

Polybrominated Diphenyl Ethers in the Atmosphere of Taizhou, a Major E-Waste Dismantling Area in China - Wenliang Han; Jialiang Feng; Zeping Gu; Duohong Chen; Minghong Wu; Jiamo Fu (Bulletin of Environmental Contamination and Toxicology, 2009)

Identification and molecular mapping of the rice bacterial blight resistance gene allelic to Xa7 from an elite restorer line Zhenhui 084 - Yuchen Zhang; Jianfei Wang; Jianwei Pan; Zhimin Gu; Xifeng Chen; Yang Jin; Feng Liu; Hongsheng Zhang; Bojun Ma (European Journal of Plant Pathology, 2009)

Cloning, expression and characterization of a new agarase-encoding gene from marine Pseudoalteromonas sp. - Xinzhi Lu; Yan Chu; Qianqian Wu; Yuchao Gu; Feng Han; Wengong Yu (Biotechnology Letters, 2009)

Using remote sensing to estimate sea ice thickness in the Bohai Sea, China based on ice type - Li Ning; Feng Xie; Wei Gu; Yingjun Xu; Shuqing Huang; Shuai Yuan; Weijia Cui; Jason Levy (International Journal of Remote Sensing, 2009)

Functional analysis of calcium channel-mediated exocytosis in synaptic terminals by FM imaging technique - Feng Gu; Li Fu; Yong-Jie Ma (Neuroscience Bulletin, 2009)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Apolipoprotein E polymorphism in normal Han Chinese population: frequency and effect on lipid parameters - Shu Liang; Min Pan; Hai-Hua Geng; Hui Chen; Li-Qun Gu; Xiao-Tong Qin; Jin-Jun Qian; Jian-Hua Zhu; Chun-Feng Liu (Molecular Biology Reports, 2009)

Chitosan nanofiber scaffold enhances hepatocyte adhesion and function - Xue-Hui Chu; Xiao-Lei Shi; Zhang-Qi Feng; Zhong-Ze Gu; Yi-Tao Ding (Biotechnology Letters, 2009)

The molecular characterization of the brain protein 44-like (Brp44l) gene of Gekko japonicus and its expression changes in spinal cord after tail amputation - Maorong Jiang; Xiaosong Gu; Xiao Feng; Zheng Fan; Fei Ding; Yan Liu (Molecular Biology Reports, 2009)

Effect of salinity on growth, ion accumulation and the roles of ions in osmotic adjustment of two populations of Suaeda salsa - Jie Song; Min Chen; Gu Feng; Yonghui Jia; Baoshan Wang; Fusuo Zhang (Plant and Soil, 2009)

Simultaneous detection of human enterovirus 71 and coxsackievirus A16 in clinical specimens by multiplex real-time PCR with an internal amplification control - Xing-Long Xiao; Ya-Qing He; Yi-Gang Yu; Hong Yang; Gu Chen; Hui-Fang Li; Jing-Wei Zhang; Dong-Mei Liu; Xiao-Feng Li; Xiao-Quan Yang; Hui Wu (Archives of Virology, 2009)

Mechanisms underlying low [Ca2+]o-induced increased excitability of hippocampal neurons - Wei-Dong Yue; Yun-Hong Zhang; Feng Gu; Jing Wang; Ji-Ye Zhang; Rui-Min Gu (Neuroscience Bulletin, 2008)

Genetic variation of NBS-LRR class resistance genes in rice lines - Sihai Yang; Tingting Gu; Chunyu Pan; Zhumei Feng; Jing Ding; Yueyu Hang; Jian-Qun Chen; Dacheng Tian (Theoretical and Applied Genetics, 2008)

Identification and characterization of a major QTL responsible for erect panicle trait in japonica rice (Oryza sativa L.) - Chang-Jie Yan; Ji-Hua Zhou; Song Yan; Feng Chen; Martin Yeboah; Shu-Zhu Tang; Guo-Hua Liang; Ming-Hong Gu (Theoretical and Applied Genetics, 2007)

Biodegradation of Ethametsulfuron-Methyl by Pseudomonas sp. SW4 Isolated from Contaminated Soil - Gu Li-feng; Jiang Jian-dong; Li Xiao-hui; Shinawar Waseem Ali; Li Shun-peng (Current Microbiology, 2007)

Effects of Dietary Copper (II) Sulfate and Copper Proteinate on Performance and Blood Indexes of Copper Status in Growing Pigs - J. Feng; W. Q. Ma; Z. L. Gu; Y. Z. Wang; J. X. Liu (Biological Trace Element Research, 2007)

Diversity and geographical distribution of rhizobia associated with Lespedeza spp. in temperate and subtropical regions of China - Chun Tao Gu; En Tao Wang; Xin Hua Sui; Wen Feng Chen; Wen Xin Chen (Archives of Microbiology, 2007)

Lipopolysaccharide-induced cerebral inflammatory damage and the therapeutic effect of platelet activating factor receptor antoganist - Wen-Chao Liu; Wen-Long Ding; Hong-Yu Gu; Ming-Feng Chen; Jin-Jia Hu (Neuroscience Bulletin, 2007)

Cloning and characterization of a gene encoding the human putative ubiquitin conjugating enzyme E2Z (UBE2Z) - Xing Gu; Feng Zhao; Mei Zheng; Xiangwei Fei; Xudong Chen; Shengdong Huang; Yi Xie; Yumin Mao (Molecular Biology Reports, 2007)

Regulation of skeletal muscle differentiation in fibroblasts by exogenous MyoD gene in vitro and in vivo - Rui-feng Qin; Tian-qiu Mao; Xiao-ming Gu; Kai-jing Hu; Yan-pu Liu; Jin-wu Chen; Xin Nie (Molecular and Cellular Biochemistry, 2007)

Karyotypic evolution and phylogenetic relationships in the order Chiroptera as revealed by G-banding comparison and chromosome painting - Lei Ao; Xiuguang Mao; Wenhui Nie; Xiaoming Gu; Qing Feng; Jinhuan Wang; Weiting Su; Yingxiang Wang; Marianne Volleth; Fengtang Yang (Chromosome Research, 2007)

Cloning and Characterization of a Novel Human Prefoldin and SPEC Domain Protein Gene (PFD6L) From the Fetal Brain - Jiayi Zhang; Lingfeng Liu; Xiaomeng Zhang; Feng Jin; Jinzhong Chen; Chaoneng Ji; Shaohua Gu; Yi Xie; Yumin Mao (Biochemical Genetics, 2006)

Salinity and Temperature Effects on Germination for Three Salt-resistant Euhalophytes, Halostachys caspica, Kalidium foliatum and Halocnemum strobilaceum - Jie Song; Gu Feng; Fusuo Zhang (Plant and Soil, 2006)

Parameterization of the absorption of the H2O continuum, CO2, O2, and other trace gases in the Fu-Liou solar radiation program - Zhang Feng; Zeng Qingcun; Y. Gu; K. N. Liou (Advances in Atmospheric Sciences, 2005)

A Novel Human Gene (WDR25) Encoding a 7-WD40-Containing Protein Maps on 14q32 - Feng Jin; Jianfeng Dai; Chaoneng Ji; Shaohua Gu; Maoqing Wu; Ji Qian; Yi Xie; Yumin Mao (Biochemical Genetics, 2004)

Molecular cloning and characterization of a novel human protein phosphatase 2C cDNA (PP2C ε) - Feng Jin; Chaoneng Ji; Lingfeng Liu; Jianfeng Dai; Shaohua Gu; Xianfei Sun; Yi Xie; Yumin Mao (Molecular Biology Reports, 2004)

Effects of EDTA application and arbuscular mycorrhizal colonization on growth and zinc uptake by maize (Zea mays L.) in soil experimentally contaminated with zinc - Baodong Chen; Hong Shen; Xiaolin Li; Gu Feng; Peter Christie (Plant and Soil, 2004)

Primary analysis on groundwater, soil moisture and salinity in fukang oasis of southern Junggar basin - Feng-xue Gu; Yuan-dong Zhang; Yu Chu; Qing-dong Shi; Xiao-ling Pan (Chinese Geographical Science, 2002)

The evaluation and analysis of the tourism resources in Jilin Province - Tao-fang Yu; Chao-lin Gu; Hong Wang; Xue-jun Duan; Xiao-feng Yi (Chinese Geographical Science, 2002)

Mobilization of sparingly soluble inorganic phosphates by the external mycelium of an abuscular mycorrhizal fungus - Qing Yao; Xiaolin Li; Gu Feng; Peter Christie (Plant and Soil, 2001)

Growth of new designated cities in China - Chaolin Gu; Feng Zhen; Youliang Qiu; Shunzan Ye (Chinese Geographical Science, 1999)

Biological evaluation of running waters in Korea, with special reference to bioassessment using the PFU system - Pyung-Rim Chung; Kyu-Song Cho; Younghun Jung; Yunfen Shen; Manru Gu; Weisong Feng (Hydrobiologia, 1998)